Miocene flood basalts in NW Spitsbergen: Emplacement environment and Arctic paleoclimate context - Maria Telmon; Sten- Andreas Grundvåg; Kim Senger; Sverre Planke; Rafael Kenji Horota; Peter Betlem; Dmitrii Zastrozhnov; Alexander Minakov; Benjamin Edwards; Kasia K. Sliwinska; Matthew J. Pound; Andrea Di Capua (Journal of Volcanology and Geothermal Research, 2026)

Reflectance spectroscopy in the visible to near-infrared (VNIR, 350–2500 nm) of Martian meteorite slabs and powders: Mafic silicate compositions and abundances - Amanda Ziegler; Edward Cloutis; Dan Applin; Tegan Ledoux; Kristi Peters; Selena Lambert (Icarus, 2026)

Gloeotrichia echinulata genomes from the United States are nontoxigenic and likely geosmin producers - Theo W. Dreher; Robin Sleith; Edward W. Davis; Ryan S. Mueller; Peter D. Countway (Harmful Algae, 2026)

Smart point cloud–guided 3D gaussian splatting for urban modeling and data-driven analysis - Yingwen Yu; Zhuoyue Wang; Guanting Zhang; Peter van Oosterom; Edward Verbree; Steffen Nijhuis; Yuyang Peng (Sustainable Cities and Society, 2026)

Hormetic effects of per- and polyfluoroalkyl substances on ecologically relevant animal models: Generality, quantitative features, and risk assessment implications - Edward J. Calabrese; Peter Pressman; A. Wallace Hayes; Evgenios Agathokleous; Rachna Kapoor; Vittorio Calabrese; Tao Sun; Gaurav Dhawan (Environmental Pollution, 2026)

Hormesis in biomedical and toxicological models: A generalizable phenomenon induced by per- and polyfluoroalkyl agents - Edward J. Calabrese; Peter Pressman; A. Wallace Hayes; Evgenios Agathokleous; Rachna Kapoor; Vittorio Calabrese; Tao Sun; Gaurav Dhawan (Chemico-Biological Interactions, 2026)

Genome-wide molecular diversity analyses identify wild Cicer as reservoirs of variations for chickpea improvement - Edward Asare; Rosy Raman; Peter R. Ryan; Nay Chi Khin; Ulrike Mathesius; Harsh Raman (Genetic Resources and Crop Evolution, 2026)
As climate change intensifies abiotic and biotic stresses, expanding the genetic base of cultivated chickpea ( Cicer arietinum ) is crucial for sustaining global pulse production. Modern chickpea cultivars have a narrow genetic base, restricting genetic gain especially for adaptation to environmental stresses, soil constraints and disease resistance. The wild Cicer species, particularly Cicer reticulatum and Cicer echinospermum , represent valuable reservoirs of genetic diversity for the improvement of existing chickpea cultivars, but their potential has not been fully exploited. Here, we evaluated genome-wide diversity and population structure in 317 Cicer accessions, comprising C. reticulatum (234), C . echinospermum (68) and C. arietinum (15), using 5792 high-confidence DArTseq SNP and 4628 SilicoDArT markers. We observed moderate polymorphic information content values, ranging from 0.25 (DArTseq SNPs) to 0.30 (SilicoDArT), indicating a medium level of informativeness and demonstrating that both marker systems are appropriate for diversity analysis for identifying useful variation for chickpea breeding. Genetic diversity indices revealed high diversity in C. reticulatum accessions. Analysis of molecular variance indicated that most molecular variation occurred within species rather than among species, indicating substantial intraspecific variation that can be exploited in chickpea breeding programs. Principal coordinates and neighbour-joining analyses resolved clear clustering at the species-level, confirming close genetic relationships between C. arietinum and C. reticulatum . The probability of identity-by-descent analysis and genome-wide linkage disequilibrium revealed extensive diversity in C. reticulatum compared to C. arietinum and C. echinospermum . Overall, this study establishes that high allelic diversity present in C. reticulatum accessions can be accessed for cultivated chickpea improvement.

Shoulder Kinematic and Muscle Activity Compensations to Scapular Stabilizer Weakness: An Optimal Control Framework - Matthew S. Russell; Daanish M. Mulla; Peter J. Keir; Edward K. Chadwick; Dimitra Blana; Janessa D. M. Drake; Jaclyn N. Chopp-Hurley (Annals of Biomedical Engineering, 2026)
Purpose Shoulder kinematic and muscular redundancy promotes considerable variability, obscuring possible insights into neuromuscular control and compensation mechanisms for muscle weakness or fatigue. The current study harnessed recent advancements in optimal control formulations for computational musculoskeletal models to determine potential neuromuscular control strategies to compensate for isolated muscle weakness. Methods A computational shoulder model characterized by independent clavicular, scapular, and humeral kinematics and 138 muscle elements was used. Optimal control-predicted thoracohumeral elevation kinematics were validated against published empirical kinematics. Force-generating capacity of the upper trapezius, middle trapezius, and lower trapezius, and serratus anterior were individually limited to 75%, 50%, and 25% maximal capacity to generate subsequent optimal control predictions of scapulothoracic kinematic changes associated with muscle weakness. Combined limited maximal force-generating capacity of lower trapezius and serratus anterior was also explored. Results Model-predicted scapulothoracic kinematics showed good agreement with reference data, yet some significant differences were identified below 55° thoracohumeral elevation. Fatigue-mediated kinematic changes were most apparent during sagittal plane elevation. Serratus anterior weakness displayed the largest scapulothoracic kinematic changes at all thresholds of limited force-generating capacity. It also prompted the largest compensatory muscle activity changes from other shoulder muscles, while upper trapezius weakness prompted very little compensatory changes in muscle activity. Conclusion Optimal control simulations were used to identify potential compensation mechanisms for shoulder muscle weakness and predict their effects on scapular kinematics. Findings suggest that thoracohumeral elevation in the scapular plane displayed less trapezius coactivity, both when ‘weakened’ and ‘unweakened.’ Thus, scapular plane tasks may isolate serratus anterior, while frontal plane tasks may achieve more balanced coactivation.

Toward a terminological consensus in rock climbing - Claudia Augste; Jiří Baláš; Peter Edwards; Julian Henz; Jerry Prosper Medernach (German Journal of Exercise and Sport Research, 2026)
Introduction Rock climbing encompasses a wide range of activities varying in movement, ascent style, safety requirements, and environmental context. In light of the sport’s evolution, a contemporary challenge in this research field pertains to the inconsistent use and conceptual ambiguity of climbing-related terminology. This multi-study investigation aimed to establish a consensus framework to standardize terminology for future rock climbing research. Methods In Study 1, a scoping literature review was conducted in April 2025. All scientific publications identified (378 publications) were systematically reviewed to assess the prevalence of title terms, historical evolution of terminology, cross-linguistic influences, definitions, and contextual frameworks of climbing-related terms. Study 2 engaged leading experts in the field via an online survey and a workshop to develop standardized definitions and a shared conceptual framework for climbing terminology. Results Study 1 found substantial diversity and conceptual ambiguity in climbing terminology, with rock climbing being the most prevalent term, followed by sport climbing and bouldering . Terminological and contextual inconsistencies were evident, as multiple terms were used to describe the same climbing context, while identical terms referred to different activities. Study 2 achieved consensus on terminology and a structural model, conceptualizing rock climbing as an umbrella term encompassing various disciplines, ascent styles, and performance types. Recommendations were provided regarding titles, keywords, regulatory contexts, and environment settings. Conclusion The terminological consensus and associated recommendations provide a foundation for a common language in the field and a shared understanding among researchers.

When to stop? A visual impact assessment framework for incremental urban and community expansion in rural heritage landscapes - Yuyang Peng; Steffen Nijhuis; Zhuoyue Wang; Yingwen Yu; Edward Verbree; Peter van Oosterom (Sustainable Cities and Society, 2026)

Hormesis in plant systems: A widespread and highly generalizable phenomenon induced by per- and polyfluoroalkyl substances - Edward J. Calabrese; Peter Pressman; A. Wallace Hayes; Evgenios Agathokleous; Rachna Kapoor; Vittorio Calabrese; Tao Sun; Gaurav Dhawan (Environmental Pollution, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Host range of Colletotrichum pyricola: an aggressive pathogen of eucalypts - Aindreeya Alcova; Peter K. Ades; Jacqueline Edwards; Yu Pei Tan; Niloofar Vaghefi; Paul W.J. Taylor (Australasian Plant Pathology, 2026)
Colletotrichum is a fungal genus, comprising many plant pathogens that pose a significant threat to agriculture globally, however, their diversity and host range on Australian native plants remain poorly understood. Colletotrichum pyricola , first described as a fruit rot pathogen of Pyrus communis (common pear) in New Zealand, has also been reported in Australia, but its broader host range and potential biosecurity risk remain unknown. In this study, pathogenicity bioassays revealed that Co. pyricola can infect a range of Australian natives, including Banksia burdettii , Clematis aristata , Eucalyptus caesia , and Leptospermum grandifolium , as well as fruit trees, Malus domestica (apple) and Persea americana (avocado). Detached-leaf pathogenicity bioassays using both wound and non-wound inoculation showed Co. pyricola was also able to cause disease symptoms on a range of eucalypt species ( Angophora , Corymbia , and Eucalyptus ). Additionally, the re-isolation of Co. pyricola from asymptomatic, non-wounded tissues and microscopic observation of appressoria support a latent or hemibiotropic lifestyle. Therefore, these asymptomatic infections may allow the fungus to persist undetected across hosts and environments, facilitating long-term dispersal. These findings expand the known host range and potential geographic distribution of Co. pyricola in Australia, highlighting the importance of understanding fungal pathogens in native plant communities.

Reflectance spectroscopy (200-4200 nm) of the red-sloped C2 carbonaceous chondrites MET 00432, Tagish Lake, Tarda, and WIS 91600 (“CT” grouplet) - Edward A. Cloutis; Devin L. Schrader; Daniel M. Applin; Tomoki Nakamura; Timothy D. Glotch; Takahiro Hiroi; Moe Matsuoka; Michael E. Zolensky; Joshua P. Emery; Kristi M. Peters (Icarus, 2026)

Petrogenesis and Provenance of Unique Amphibole-Bearing Carbonaceous Chondrite Almahata Sitta 202: Further Evidence for a Ceres-Sized, Water-Rich Parent Body - Cyrena A. Goodrich; Victoria E. Hamilton; Michael E. Zolensky; Noriko Kita; Issaku Kohl; Lauren Tafla; Robert J. Macke; Takahiro Hiroi; Yoko Kebukawa; Wayne Buckley; Jacob B. Setera; Justin I. Simon; et al. (Geochimica et Cosmochimica Acta, 2026)

Emodin: Its effects are largely due to hormesis - Edward J. Calabrese; Peter Pressman; A. Wallace Hayes; Evgenios Agathokleous; Gaurav Dhawan; Rachna Kapoor; Vittorio Calabrese (Food and Chemical Toxicology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Drivers of aquatic zoosporic parasites in natural and artificial environments - Maya Stoyneva-Gärtner; Hans-Peter Grossart; Thijs Frenken; Dirk S. Schmeller; Laura Garzoli; Serena Rasconi; Elżbieta Wilk-Woźniak; Albert Reñé; Slawek Cerbin; Cécile Lepère; Caio César Pires de Paula; Adeline Loyau; et al. (Aquatic Sciences, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Increasing meatless options to decrease meat consumption - a quantitative analysis of the relationship between the percentage of meatless items offered on a specials menu and meatless purchases - Danielle Mary Edwards; Peter Ondish; Roni Neff (Food Quality and Preference, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Hormetic effects of chemical contaminants on animal development: Mechanisms, phenotypes, and ecological implications - Evgenios Agathokleous; Peter Pressman; Edward J. Calabrese; David Costantini; Raul Narciso C. Guedes; A. Wallace Hayes; Vittorio Calabrese (Environmental Pollution, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Short-term effects of Greenlandic glacial rock flour on soil physical properties and maize yield - William Akortey; Eric Oppong Danso; Christiana Dietzen; William Amponsah; Emmanuel Arthur; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Daniel Amoako Darko; Selorm Yaotse Dorvlo; Edward Benjamin Sabi; Stephen Abenney-Mickson; et al. (Nutrient Cycling in Agroecosystems, 2026)
Greenlandic glacial rock flour (GRF) serves as a valuable source of silicate minerals for CO₂ uptake through enhanced weathering. Additionally, its physico-chemical properties may influence soil hydro-physical characteristics and may also have a separate effect on crop yields. This study evaluated the effects of GRF application at 50 and 100 t/ha, along with an unamended control, on soil water content at field capacity (FC), plant-available water (PAW), saturated hydraulic conductivity (K sat ), and dry aggregate stability (DAS) over 120 days. Separately, maize dry matter yield (DMY) was assessed after 40 days of growth. The experiment was conducted across four soil textures, comprising coarse-textured soils (sand and sandy loam) and fine-textured soils (sandy clay loam and clay). The 100 t/ha application had the most significant ( p < 0.05) impact on soil properties and maize yield, while the 50 t/ha rate showed intermediate but inconsistent effects. In fine-textured soils, the 100 t/ha treatment increased FC by 15% and PAW by 27% compared to the control, whereas in coarse-textured soils, FC and PAW rose by 29% and 26%, respectively. However, Ksat decreased by 47% in fine-textured soils and 34% in coarse-textured soils compared to the control. Maize DMY for the 100 t/ha rate increased by 18% in coarse-textured soils and 38% in fine-textured soils relative to the control. These findings suggest that GRF amendment improved hydro-physical properties more in coarse-textured soils but increased yield more in fine-textured soils, and may serve as a useful co-benefit of enhanced rock weathering.

Metabolic cost of external work: a novel CPET parameter optimises characterisation of exercise performance in obese individuals - Jennifer J. Rayner; Rebecca R. Chamley; Robert Barker Davies; Oliver O’Sullivan; Peter Ladlow; Alex N. Bennett; Edward D. Nicol; Oliver J. Rider; David A. Holdsworth (European Journal of Applied Physiology, 2026)
Purpose Both obesity and cardiorespiratory fitness are crucial determinants of symptoms and prognosis. However, interpreting the gold-standard cardiopulmonary exercise test (CPET) is complicated by increasing body size and varying body composition. We hypothesised that the ‘metabolic cost of external work’ (or oxygen uptake (ml/min)/workload (Watts); V̇O 2 /W), a body weight-independent determinant of endurance capacity, would reflect metabolic health more accurately than V̇O 2 alone. Methods A test cohort of 160 fit individuals underwent anthropomorphic and metabolic assessment, maximal bicycle ergometer CPET, and six-minute walk test (6MWT). V̇O 2 /W was calculated at VT1 and peak. The performance of V̇O 2 /W was validated in 62 older, less fit individuals, undergoing the same protocol. 24 obese volunteers were assigned a weight loss intervention, and the impact on V̇O 2 /W examined. Results In both test and validation cohort, V̇O 2 /W at VT1 and peak correlated with 6MWT distance, more strongly than standard CPET parameters. Including V̇O 2 /W improved the accuracy of predicting 6MWT distance. V̇O 2 /W correlated with BMI, insulin sensitivity and waist-to-hip ratio. Metabolic cost falls with weight loss, in parallel to metabolic and functional improvements, in contrast to other CPET parameters. Conclusion Metabolic cost is strongly associated with functional capacity and metabolic health across a range of body weight and fitness, outperforming standard CPET metrics. It is a simple measure which may improve our assessment of the extent to which exertional symptoms are determined by metabolic factors in an individual, and thereby target the most appropriate intervention to those who will benefit most. Graphical Abstract

Dispersal of marine plastic litter during tropical cyclones - Edward Roome; Peter Robins; Mark Walton; Evelyn Taboada; Simon Neill (Marine Pollution Bulletin, 2026)

Emerging organic pollutants in sediments from Lake Victoria: Spatial patterns, sources and ecological risks - Merolyne Natuhwera; Patrick Ssebugere; Kenneth Arinaitwe; Peter Oswald; Edward Mubiru; Florence Nantaba; Zaccheus Shehu; Krištof Urban; Liudmyla Khvalbota; Nikiforos A. Alygizakis; Nikolaos S. Thomaidis; Dimitrios Triantafyllos Gerokonstantis; et al. (Science of The Total Environment, 2026)

Multi-phase intra-plate rifting and deformable plate modelling of the Northeast Atlantic back to the Permian - Grace E. Shephard; Mansour M. Abdelmalak; Jan Inge Faleide; Edward Clennett; Sabin Zahirovic; Sebastien Gac; Peter Haas; Carmen Gaina; Trond H. Torsvik (Gondwana Research, 2026)

Hormesis induced by persistent organic pollutants: Mechanisms, ecological implications, and challenges for risk assessment - Evgenios Agathokleous; Haitao Liu; Peter Pressman; Jian-Gang Han; A. Wallace Hayes; Edward J. Calabrese (Environmental Pollution, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Integration of Multiple Data Types to Document Spatial Effort in a Recreational Fishery for Highly Migratory Species in Relation to Offshore Wind Development - Jeff Kneebone; Matthew Davis; Ryan Knotek; Connor Capizzano; Edward Kim; Camilla T. McCandless; Peter Chaibongsai; Wessley Merten; Eric S. Orbesen (Fisheries Oceanography, 2026)
The expansion of offshore wind interests in US waters has raised concern over potential adverse impacts to fisheries activity and productivity. Yet evidence‐based platforms for assessing those impacts are lacking for many recreational fisheries. We demonstrate how data from a federal fishery survey (Large Pelagics Intercept Survey [LPIS]), cooperative tagging programs, and the direct survey of recreational fishermen can be used to characterize the spatial extent of baseline (pre‐construction) effort in a recreational fishery that targets highly migratory fishes (HMS) in US territorial waters of the Atlantic, Gulf of Mexico, and Caribbean. To document the location of effort, LPIS catch data and tag, release, and recapture (CTR) records from four cooperative tagging programs were independently aggregated onto a grid of offshore wind lease blocks. An online survey of recreational fishermen was also executed to assess the spatial extent of effort in relation to a Draft Call Area (DCA) in the Gulf of Maine region. Collectively, the LPIS and CTR data described widespread recreational fishing effort for HMS, including within and around the majority of existing and planned offshore wind lease areas. Responses to the online survey revealed more widespread effort within the Gulf of Maine DCA than both the LPIS and CTR data, but some respondents may have overrepresented true levels of fishing effort. Our results demonstrate the need for multiple data types to comprehensively assess offshore wind impacts on the recreational HMS fishery and to inform marine spatial planning in regions into which offshore wind energy development may be expanded.

Hopanoid breakdown products (HBPs) and their influence on tetracyclic and tricyclic terpane (cheilanthane) oil-source rock parameters - Tharika Liyanage; Lennart M. van Maldegem; Janet Hope; Philippe Schaeffer; Pierre Adam; Hans Peter Nytoft; Dianne Edwards; Jochen Brocks (Organic Geochemistry, 2025)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

The pluralistic natural capital values of a tropical city - Adrienne Grêt-Regamey; Justine Saunders; Peter Edwards; Daniel Richards; Jahson I. Alemu; Natasha Bhatia; Roman Carrasco; Zuzana Drillet; Tze Kwan Fung; Yan Feng Leon Gaw; Wanggi Jaung; Andrea Law; et al. (Ecosystem Services, 2025)

Repeatability of diffusion and perfusion MRI derived radiomic features in glioblastoma: a test-retest study - Philip Martin; Lois Holloway; Peter Metcalfe; Eng-Siew Koh; Farhannah Aly; Edward Chan; Caterina Brighi (Physical and Engineering Sciences in Medicine, 2025)

Community sawmills can save forests: Forest regrowth and avoided deforestation due to vertical integration of wood production in Mexican community forests - Daniela A. Miteva; Edward A. Ellis; Peter W. Ellis; Erin O. Sills; Bronson W. Griscom; Dawn Rodriguez-Ward; Colette Naples; Claire Uematsu (Ecological Economics, 2025)

Perceived discrimination, trust in physicians, and their associations with ovarian cancer mortality among women in the African American Cancer Epidemiology Study - Lindsay J. Collin; Courtney E. Johnson; Maxwell Akonde; Mary Kan; Elisa V. Bandera; Lauren C. Peres; Bo Qin; Michele L. Cote; Anthony Alberg; Edward S. Peters; Theresa A. Hastert; Joellen M. Schildkraut (Cancer Causes & Control, 2025)
Purpose Black women are 30% more likely to die of ovarian cancer than White women. Discrimination may affect cancer health disparities through pathways including socioeconomic disadvantage, chronic stress, and access to care. In this study, we evaluated associations of discrimination and trust in physicians with all-cause mortality among Black women with ovarian cancer. Methods Using data from the African American Cancer Epidemiology Study (AACES), we included 592 Black ovarian cancer patients who completed an interview. Discrimination and trust in physicians were measured using the Everyday Discrimination, Major Experiences of Discrimination, and Trust in Physicians scales, respectively. We used Cox proportional hazard models to compute multivariable-adjusted hazard ratios (HR) and 95% confidence intervals (CIs) associating everyday discrimination, major experiences of discrimination, and trust in physicians with all-cause mortality. Results Approximately 43% reported experiencing at least one major experience of discrimination, 16% reported high everyday experiences of discrimination, and the median trust in physician score was 35. The association between higher experiences of everyday discrimination was HR = 0.84 (95% CI: 0.63, 1.11), compared with low experiences of everyday discrimination. We observed that more major experiences of discrimination had 1.25-times the mortality rate compared with low experiences of major discrimination (95% CI: 0.84, 2.20). Higher trust in physicians was associated with slightly lower mortality rates (HR = 0.91, 95% CI: 0.74, 1.14). Conclusion We observed complexities in the relationships of everyday discrimination, major experiences of discrimination, and trust in physicians with mortality among Black women with ovarian cancer. Future work to understand the these relationships is likely warranted.

Can Solar‐Powered Irrigation Systems Naturally Meet Crop Water Requirements? Proof of Concept From a Case Study in Sub‐Saharan Africa - Eric Oppong Danso; Christiana Dietzen; William Akortey; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Ebenezer Agyapong; Elorm Grace Ayayi; Nana Oduro Osei Bonsu; Michael Osei Adu; Emmanuel Arthur; Jacob Ulzen; et al. (Irrigation and Drainage, 2025)
Irrigation scheduling is crucial for ensuring precise water delivery to crops. However, in many sub‐Saharan African irrigation schemes, water is applied without considering crop water needs, resulting in low crop water productivity and low yields. Solar‐powered irrigation systems can automatically meet these needs by utilizing solar radiation, which drives both evapotranspiration and solar panel power production for pumping. This study aimed to integrate irrigation scheduling into a solar‐driven irrigation system and assess the impact of meteorological variables on reference evapotranspiration (ET o ) in Ghana. A 50‐watt solar panel powered a 12‐V submersible pump, with a flow meter installed on the outlet pipe for hourly volume of water pumped (VWP) data readings. These data were used to examine correlations between solar radiation (R s ) and ET o , as well as between R s and VWP. Partial correlation analyses were used to assess the relative influences of R s , wind speed (U 2 ), relative humidity (RH) and air temperature (T air ) on ET o across 10 locations in Ghana's agroecological zones. The study revealed a strong linear correlation between the hourly R s and ET o ( R 2 > 0.9) and between the hourly R s and VWP ( R 2 = 0.8). The VWP was sufficient to meet crop‐water demand year‐round. Solar radiation was consistently the primary meteorological factor influencing ET o in Ghana.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

The Southern Ocean Time Series: a climatological view of hydrography, biogeochemistry, phytoplankton community composition, and carbon export in the Subantarctic Zone - Elizabeth H. Shadwick; Cathryn A. Wynn-Edwards; Ruth S. Eriksen; Peter Jansen; Xiang Yang; Gemma Woodward; Diana Davies (Ocean Science, 2025)
The Southern Ocean Time Series (SOTS) provides highly temporally resolved observations of the physical, chemical, and biological variability in the upper ocean, as well as the export of particulate organic and inorganic carbon to the ocean interior, in the subantarctic region south of Australia. The SOTS observatory focuses on the subantarctic region because of its importance in the formation of mode water and the associated uptake and storage of anthropogenic heat and carbon. The region is also critical for the supply of oxygen to the ocean interior and the export of nutrients to fuel primary production in broad areas of the low-latitude global ocean. The SOTS observatory is the longest running multidisciplinary initiative in the open Southern Ocean and has delivered high-quality observations from the surface to the seafloor for more than a decade and, for some parameters, for over two decades, using two deep-water moorings. The moorings are serviced annually, providing additional opportunities for shipboard sampling and sensor validation and calibration. Using observations collected at the SOTS site between 1997 and 2022, we present the seasonal variability in upper-ocean hydrography, biogeochemistry, phytoplankton and microplankton community composition, and diversity, along with particulate organic and particulate inorganic carbon export to the deep ocean. This climatological view of the region is complemented by a review of recent findings underpinned by observations collected by the SOTS observatory and highlighting the ongoing need for long time series to better understand the Subantarctic Ocean and its response to a changing climate.

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

Long-term effects of free-ranging cattle and ponies on the soil and vegetation of reseeded grasslands in the New Forest, England - Peter J. Edwards; J. Rue Ekins; Susan Hollis (Perspectives in Plant Ecology, Evolution and Systematics, 2025)

Axial variation in the properties of Antrocaryon micraster (Aprokuma) - Emmanuel Appiah-Kubi; Michael Awotwe-Mensah; Peter Kessels Dadzie; Haruna Seidu; Edward Achiaw Owusu; Felix Boakye (Journal of the Indian Academy of Wood Science, 2025)

Regional conservation genomics: insights and opportunities from northern Australia - Teigan Cremona; Brenton von Takach; Robyn Shaw; Alexander Carey; Bridget Campbell; Skye Cameron; Renee Catullo; Caroline Chong; Saul Cowen; Danielle Edwards; Emilie Ens; Tony Griffiths; et al. (Biodiversity and Conservation, 2025)
Biodiversity conservation in northern Australia is characterised by high endemism, data deficiency, and high Indigenous land tenure and population. The Northern Australia Conservation Genomics Forum brought together experts to explore current genetic research with particular emphasis on integration of genomics within conservation practices. We discuss the regional biodiversity of northern Australia, highlighting the unique biogeographic patterns, known and unknown species diversity, and ongoing threats such as habitat degradation, altered fire regimes, invasive species, and climate change. This article synthesises key themes from the forum, including the current application of genomics in conservation, gaps and areas of need and opportunity to advance species conservation in this sparsely populated, yet iconic region of Australia. We highlight the need to expand collaborative research partnerships across land tenures with Indigenous organisations, pastoralists, government and non-government organisations, which is crucial for the effective study and conservation of the region’s biodiversity. The paper identifies the challenges and opportunities in applying genomic data to conservation strategies and applied management, including species translocations and habitat management, while acknowledging the limitations and gaps in current research and collections. The insights from this forum emphasise the advantages in using genomics to inform conservation decisions, and the need for continued research and collaboration to protect northern Australia’s unique biodiversity.

The variability of the topside ionospheres of Venus and Mars as seen by recent radio science observations - Kerstin Peter; Martin Pätzold; Paul Withers; Robin Ramstad; Edward Thiemann; Markus Fränz; Silvia Tellmann; Bernd Häusler; Yoshifumi Futaana; Mats Holmström (Icarus, 2025)

Temporal trends and patterns for early- and late-onset adult liver cancer incidence vary by race/ethnicity, subsite, and histologic type in the United States from 2000 to 2019 - Mei-Chin Hsieh; Kendra L. Ratnapradipa; Laura Rozek; Shengdi Wen; Yu-Wen Chiu; Edward S. Peters (Cancer Causes & Control, 2025)
Purpose To examine incidence trends and patterns for early- and late-onset liver cancer. Methods Liver and intrahepatic bile duct (IBD) cancers diagnosed between 2000 and 2019 were acquired from 22 SEER registries. Variables included early-onset (20–49) vs. late-onset (50+), anatomic subsite, histologic type (hepatocellular carcinoma [HCC] and IBD cholangiocarcinoma [ICC]), sex, and race/ethnicity. Age-standardized incidence rates were calculated using SEER*Stat. Jointpoint regression analysis was employed to estimate the annual percent change (APC) and the average APC (AAPC) with pairwise comparisons for trend by sex and by race/ethnicity stratified by age and subsite. Results Liver cancer incidence decreased among early-onset (AAPC [95% CI] − 2.39 [− 2.74, − 2.07]) but increased among late-onset patients (2.85 [2.71, 3.01]), primarily driven by HCC (3.60 [3.50, 3.71]). IBD incidence increased for both ages with ICC incidence annually increasing 7.92% (6.84, 9.26) for early-onset and 6.32% (5.46, 8.86) for late-onset patients. Early-onset liver cancer displayed comparable trends across racial/ethnic groups; however, late-onset liver cancer showed more variation, particularly among American Indian/Alaska Native/Asian Pacific Islander (AI/AN/API) populations, which experienced a significant decrease in incidence, thereby narrowing the gap with other racial/ethnic groups. For IBD, an identical pattern of early-onset IBD among non-Hispanic Blacks (NHBs) compared to Hispanics was showed with coincidence test p = 0.1522, and a parallel pattern was observed among late-onset patients for both sexes ( p = 0.5087). Conclusion Late-onset HCC continues to rise, except for NHB and AI/AN/API, where incidence rates have started to decrease over the past 4–5 years. Early and late-onset ICC incidence continues to increase across all racial/ethnic groups.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Fisetin: hormesis accounts for many of its chemoprotective effects - Edward J. Calabrese; Peter Pressman; A. Wallace Hayes; Evgenios Agathokleous; Gaurav Dhawan; Rachna Kapoor; Japjee Parmar; Ibrahim Mssillou; Vittorio Calabrese (Biogerontology, 2025)

Towards mineralised mycelium biocomposites: Optimising fungal growth and ureolytic biomineralisation - Tria Amalia Ningsih; Simen Akkermans; Peter De Vreese; Edward Matthijs; Rachel Armstrong; Jan F.M. Van Impe (Journal of Cleaner Production, 2025)

Fate of a toxic Microcystis aeruginosa bloom introduced into a subtropical estuary from a flow-managed canal and management implications - Edward J. Phlips; Susan Badylak; Eric C. Milbrandt; Benjamin Stelling; Mauricio Arias; Cassondra Armstrong; Thomas Behlmer; Amanda Chappel; Amanda Foss; David Kaplan; Leslie Landauer; Peter Landauer; et al. (Journal of Environmental Management, 2025)

Dead leaf turnover in monodominant forest of the marcescent palm Lodoicea maldivica - Peter J. Edwards; Frauke Fleischer-Dogley (Oecologia, 2025)

Systematic conservation prioritization with the prioritizr R package - Jeffrey O. Hanson; Richard Schuster; Matthew Strimas‐Mackey; Nina Morrell; Brandon P. M. Edwards; Peter Arcese; Joseph R. Bennett; Hugh P. Possingham (Conservation Biology, 2025)
Plans for expanding protected area systems (prioritizations) need to fulfill conservation objectives. They also need to account for other factors, such as economic feasibility and anthropogenic land‐use requirements. Although prioritizations are often generated with decision support tools, most tools have limitations that hinder their use for decision‐making. We outlined how the prioritizr R package ( https://prioritizr.net ) can be used for systematic conservation prioritization. This decision support tool provides a flexible interface to build conservation planning problems. It can leverage a variety of commercial (e.g., Gurobi) and open‐source (e.g., CBC and SYMPHONY) exact algorithm solvers to identify optimal solutions in a short period. It is also compatible with a variety of spatially explicit (e.g., ESRI Shapefile, GeoTIFF) and nonspatial tabular (e.g., Microsoft Excel Spreadsheet) data formats. Additionally, it provides functionality for evaluating prioritizations, such as assessing the relative importance of different places selected by a prioritization. To showcase the prioritizr R package, we applied it to a case study based in Washington state (United States) for which we developed a prioritization to improve protected area coverage of native avifauna. We accounted for land acquisition costs, existing protected areas, places that might not be suitable for protected area establishment, and spatial fragmentation. We also conducted a benchmark analysis to examine the performance of different solvers. The prioritization identified 12,400 km 2 of priority areas for increasing the percentage of species’ distributions covered by protected areas. Although open source and commercial solvers were able to quickly solve large‐scale conservation planning problems, commercial solvers were required for complex, large‐scale problems.. The prioritizr R package is available on the Comprehensive R Archive Network (CRAN). In addition to reserve selection, it can inform habitat restoration, connectivity enhancement, and ecosystem service provisioning. It has been used in numerous conservation planning exercises to inform best practices and aid real‐world decision‐making.

Vulnerability assessment of elasmobranch species to fisheries in coastal Kenya: Implications for conservation and management policies - Benedict Kiilu; Boaz Kaunda-Arara; Remmy Oddenyo; Gladys Okemwa; Elizabeth Mueni; Peter Musembi; Bernerd Fulanda; Lameck Menya-Otieno; Maurine Okeri; Grace Nduku; Jonathan Musembei; Mohamed Omar; et al. (Marine Policy, 2025)

A phylogenomic tree of wood-warblers (Aves: Parulidae): Dealing with good, bad, and ugly samples - Min Zhao; Jessica A. Oswald; Julie M. Allen; Hannah L. Owens; Peter A. Hosner; Robert P. Guralnick; Edward L. Braun; Rebecca T. Kimball (Molecular Phylogenetics and Evolution, 2025)

Do the hormetic effects of chlorogenic acid mediate some of the beneficial effects of coffee? - Edward J. Calabrese; Peter Pressman; A. Wallace Hayes; Linda Baldwin; Evgenios Agathokleous; Gaurav Dhawan; Rachna Kapoor; Vittorio Calabrese (Chemico-Biological Interactions, 2025)

Revisiting the sustainability science research agenda - Mesfin Sahle; Shruti Ashish Lahoti; So-Young Lee; Katja Brundiers; Carena J. van Riper; Christian Pohl; Herlin Chien; Iris C. Bohnet; Noé Aguilar-Rivera; Peter Edwards; Prajal Pradhan; Tobias Plieninger; et al. (Sustainability Science, 2025)

Multisite evaluation of microtensiometer and osmotic cell stem water potential sensors in almond orchards - Isaya Kisekka; Srinivasa Rao Peddinti; Peter Savchik; Liyuan Yang; Mae Culumber; Khalid Bali; Luke Milliron; Erica Edwards; Mallika Nocco; Clarissa A. Reyes; Robert J. Mahoney; Kenneth Shackel; et al. (Computers and Electronics in Agriculture, 2024)

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

Deployment-invariant probability of detection characterization for aerial LiDAR methane detection - Michael J. Thorpe; Aaron Kreitinger; Dominic T. Altamura; Cameron D. Dudiak; Bradley M. Conrad; David R. Tyner; Matthew R. Johnson; Jason K. Brasseur; Peter A. Roos; William M. Kunkel; Asa Carre-Burritt; Jerry Abate; et al. (Remote Sensing of Environment, 2024)

Navigating integration challenges: Insights from migrant dairy farm workers in New Zealand - Jacob Kambuta; Peter Edwards; Kathryn Bicknell (Journal of Rural Studies, 2024)

Gaps in the implementation of urban forest management plans across canadian cities - Camilo Ordóñez Barona; Anusha Jain; Melissa Heppner; Annick St Denis; Daniel Boyer; James Lane; Catherine Edwards; Peter Duinker; Tenley Conway (Landscape and Urban Planning, 2024)

Oocyte maturation, blastocyst and embryonic development are mediated and enhanced via hormesis - Edward J. Calabrese; Peter Pressman; A. Wallace Hayes; Gaurav Dhawan; Rachna Kapoor; Evgenios Agathokleous; Vittorio Calabrese (Food and Chemical Toxicology, 2024)

Irrigation and oil palm empty fruit bunch mulch enhance eggplant growth, radiation interception and dry matter yield - John Bright Amoah Nyasapoh; Eric Oppong Danso; Daniel Selorm Kpodo; William Amponsah; Emmanuel Arthur; Edward Benjamin Sabi; Peter Bilson Obour; William Akortey; Bernard Kwabena Boadi Mensah; Grace Elorm Ayayi; Mathias Neumann Andersen (European Journal of Agronomy, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Enhancing the human health and lifespan: a targeted strategy emphasizing statins - Edward Calabrese; Peter Pressman (Biogerontology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Achieving net zero neighborhoods: A case study review of circular economy initiatives for South Wales - Jacob Edwards; Hanbing Xia; Qian Jan Li; Peter Wells; Jelena Milisavljevic-Syed; Alberto Gallotta; Konstantinos Salonitis (Journal of Cleaner Production, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Mercury from Icelandic geothermal activity: High enrichments in soils, low emissions to the atmosphere - Brock A. Edwards; Peter M. Outridge; Feiyue Wang (Geochimica et Cosmochimica Acta, 2024)

Pyrrhotites in asteroid 162173 Ryugu: Records of the initial changes on their surfaces with aqueous alteration - Hiroharu Yui; Shu-hei Urashima; Morihiko Onose; Mayu Morita; Shintaro Komatani; Izumi Nakai; Yoshinari Abe; Yasuko Terada; Hisashi Homma; Kazuko Motomura; Kiyohiro Ichida; Tetsuya Yokoyama; et al. (Geochimica et Cosmochimica Acta, 2024)

Impact of chickpea hummus on postprandial blood glucose, insulin and gut hormones in healthy humans combined with mechanistic studies of food structure, rheology and digestion kinetics - Rasha A. Alshaalan; Maria N. Charalambides; Cathrina H. Edwards; Peter R. Ellis; Shatha H. Alrabeah; Gary S. Frost (Food Research International, 2024)

TTCF4LAMMPS: A toolkit for simulation of the non-equilibrium behaviour of molecular fluids at experimentally accessible shear rates - Luca Maffioli; James P. Ewen; Edward R. Smith; Sleeba Varghese; Peter J. Daivis; Daniele Dini; B.D. Todd (Computer Physics Communications, 2024)

Fostering effective and sustainable scientific collaboration and knowledge exchange: a workshop-based approach to establish a national ecological observatory network (NEON) domain-specific user group - Alison Donnelly; Ankur R. Desai; Katherine A. Heckman; Lucas E. Nave; Michael J. Cramer; Marie Faust; Peter Weishampel; Caleb Slemmons; Christian G. Andresen; Edward Ayres; Stacy R. Cotey; Kathryn M. Docherty; et al. (International Journal of Biometeorology, 2024)
The decision to establish a network of researchers centers on identifying shared research goals. Ecologically specific regions, such as the USA’s National Ecological Observatory Network’s (NEON’s) eco-climatic domains, are ideal locations by which to assemble researchers with a diverse range of expertise but focused on the same set of ecological challenges. The recently established Great Lakes User Group (GLUG) is NEON’s first domain specific ensemble of researchers, whose goal is to address scientific and technical issues specific to the Great Lakes Domain 5 (D05) by using NEON data to enable advancement of ecosystem science. Here, we report on GLUG’s kick off workshop, which comprised lightning talks, keynote presentations, breakout brainstorming sessions and field site visits. Together, these activities created an environment to foster and strengthen GLUG and NEON user engagement. The tangible outcomes of the workshop exceeded initial expectations and include plans for (i) two journal articles (in addition to this one), (ii) two potential funding proposals, (iii) an assignable assets request and (iv) development of classroom activities using NEON datasets. The success of this 2.5-day event was due to a combination of factors, including establishment of clear objectives, adopting engaging activities and providing opportunities for active participation and inclusive collaboration with diverse participants. Given the success of this approach we encourage others, wanting to organize similar groups of researchers, to adopt the workshop framework presented here which will strengthen existing collaborations and foster new ones, together with raising greater awareness and promotion of use of NEON datasets. Establishing domain specific user groups will help bridge the scale gap between site level data collection and addressing regional and larger ecological challenges.

Steppe-tundra composition and deglacial floristic turnover in interior Alaska revealed by sedimentary ancient DNA (sedaDNA) - Charlotte L. Clarke; Peter D. Heintzman; Youri Lammers; Alistair J. Monteath; Nancy H. Bigelow; Joshua D. Reuther; Ben A. Potter; Paul D.M. Hughes; Inger G. Alsos; Mary E. Edwards (Quaternary Science Reviews, 2024)

Catalytic production of light Olefins: Perspective and prospective - Naif S. Almuqati; Afrah M. Aldawsari; Khalid N. Alharbi; Sergio González-Cortés; Mohammed F. Alotibi; Fawaz Alzaidi; Jonathan R. Dilworth; Peter P. Edwards (Fuel, 2024)

Speculations on the Paleozoic legacy of Gondwana amalgamation - J. Brendan Murphy; R. Damian Nance; Stephen T. Johnston; Josep M. Casas; Peter A. Cawood; Edward J. Matheson; Peir K. Pufahl; Wei Dan; J. Javier Álvaro; Philip J. Heron; Rob A. Strachan (Gondwana Research, 2024)

RUTIN, a widely consumed flavonoid, that commonly induces hormetic effects - Edward J. Calabrese; Peter Pressman; A. Wallace Hayes; Gaurav Dhawan; Rachna Kapoor; Evgenios Agathokleous; Vittorio Calabrese (Food and Chemical Toxicology, 2024)

Damage to tropical forests caused by cyclones is driven by wind speed but mediated by topographical exposure and tree characteristics - Thomas Ibanez; David Bauman; Shin‐ichiro Aiba; Thomas Arsouze; Peter J. Bellingham; Chris Birkinshaw; Philippe Birnbaum; Timothy J. Curran; Saara J. DeWalt; John Dwyer; Thierry Fourcaud; Janet Franklin; et al. (Global Change Biology, 2024)
Each year, an average of 45 tropical cyclones affect coastal areas and potentially impact forests. The proportion of the most intense cyclones has increased over the past four decades and is predicted to continue to do so. Yet, it remains uncertain how topographical exposure and tree characteristics can mediate the damage caused by increasing wind speed. Here, we compiled empirical data on the damage caused by 11 cyclones occurring over the past 40 years, from 74 forest plots representing tropical regions worldwide, encompassing field data for 22,176 trees and 815 species. We reconstructed the wind structure of those tropical cyclones to estimate the maximum sustained wind speed (MSW) and wind direction at the studied plots. Then, we used a causal inference framework combined with Bayesian generalised linear mixed models to understand and quantify the causal effects of MSW, topographical exposure to wind (EXP), tree size (DBH) and species wood density ( ρ ) on the proportion of damaged trees at the community level, and on the probability of snapping or uprooting at the tree level. The probability of snapping or uprooting at the tree level and, hence, the proportion of damaged trees at the community level, increased with increasing MSW, and with increasing EXP accentuating the damaging effects of cyclones, in particular at higher wind speeds. Higher ρ decreased the probability of snapping and to a lesser extent of uprooting. Larger trees tended to have lower probabilities of snapping but increased probabilities of uprooting. Importantly, the effect of ρ decreasing the probabilities of snapping was more marked for smaller than larger trees and was further accentuated at higher MSW. Our work emphasises how local topography, tree size and species wood density together mediate cyclone damage to tropical forests, facilitating better predictions of the impacts of such disturbances in an increasingly windier world.

Evaluating incentives to encourage native afforestation on private lands in Aotearoa–New Zealand - Maksym Polyakov; Peter Edwards; Geoff Kaine; Michael Burton; Philip Stahlmann-Brown (Landscape and Urban Planning, 2024)

Taurine induces hormesis in multiple biological models: May have transformative implications for overall societal health - Edward J. Calabrese; Peter Pressman; A. Wallace Hayes; Rachna Kapoor; Gaurav Dhawan; Evgenios Agathokleous; Vittorio Calabrese (Chemico-Biological Interactions, 2024)

Flavonoids commonly induce hormetic responses - Edward J. Calabrese; A. Wallace Hayes; Peter Pressman; Gaurav Dhawan; Rachna Kapoor; Evgenios Agathokleous; Vittorio Calabrese (Archives of Toxicology, 2024)

Exceptionally low mercury concentrations and fluxes from the 2021 and 2022 eruptions of Fagradalsfjall volcano, Iceland - Brock A. Edwards; Melissa A. Pfeffer; Evgenia Ilyinskaya; Barbara I. Kleine-Marshall; Céline L. Mandon; Adam Cotterill; Alessandro Aiuppa; Peter M. Outridge; Feiyue Wang (Science of The Total Environment, 2024)

Mineral dust optical properties for remote sensing and global modeling: A review - Patricia Castellanos; Peter Colarco; W. Reed Espinosa; Scott D. Guzewich; Robert C. Levy; Ron L. Miller; Mian Chin; Ralph A. Kahn; Osku Kemppinen; Hans Moosmüller; Edward P. Nowottnick; Adriana Rocha-Lima; et al. (Remote Sensing of Environment, 2024)

Well-to-wheels scenarios for 2050 carbon-neutral road transport in the EU - Jette Krause; Marta Yugo; Zissis Samaras; Simon Edwards; Georgios Fontaras; Roland Dauphin; Peter Prenninger; Stephan Neugebauer (Journal of Cleaner Production, 2024)

Building social licence to operate: A framework for gaining and maintaining meaningful, trustworthy relationships - Dean C. Stronge; Robyn L. Kannemeyer; Peter Edwards (Resources Policy, 2024)

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

Quercetin induces its chemoprotective effects via hormesis - Edward J. Calabrese; A. Wallace Hayes; Peter Pressman; Gaurav Dhawan; Rachna Kapoor; Evgenios Agathokleous; Vittorio Calabrese (Food and Chemical Toxicology, 2024)

Phosphorus enrichment enabled Amorpha fruticosa to invade on the floodplain of the Tagliamento River, Italy - Peter Edwards; Christian Hügli; Harry Olde Venterink; Dieter Ramseier (Biological Invasions, 2024)
The North American nitrogen-fixing shrub Amorpha fruticosa (false indigo) is an aggressive invader of riverine habitats in Europe, though the reasons for its success are poorly understood. We hypothesized that its spread on the floodplain of the Tagliamento River in Northern Italy was enabled by anthropogenic phosphorus (P) enrichment. To investigate this hypothesis, we surveyed seed production at different locations along the river and performed a growth chamber experiment in which seedlings of three common floodplain shrubs ( A. fruticosa , Salix eleagnos and Buddleja davidii ) were grown at 10 levels of both nitrogen (N) and P. As a bioassay of N and P availabilities, we analyzed concentrations of these nutrients in Salix eleagnos leaves collected at different positions along the river. P availability was significantly higher in the lower reaches of the river, where A. fruticosa was abundant, than at its upstream limit. Numbers of A. fruticosa seeds per inflorescence increased strongly in a downstream direction and there was a trend for higher seed weight. In the growth experiment, A. fruticosa was more P-demanding than the other species, producing little biomass and no rhizobial nodules at low P. It also exhibited greater plasticity than the other species in both root mass fraction and ratio of longest root length to root mass. We conclude that anthropogenic P enrichment enabled A. fruticosa to invade what was originally a very oligotrophic environment. This N 2 -fixing shrub exhibits greater phenotypic plasticity than native S. eleagnos , giving it a competitive advantage under conditions of high P availability.

A globally integrated structure of taxonomy to support biodiversity science and conservation - Emily L. Sandall; Aurore A. Maureaud; Robert Guralnick; Melodie A. McGeoch; Yanina V. Sica; Matthew S. Rogan; Douglas B. Booher; Robert Edwards; Nico Franz; Kate Ingenloff; Maisha Lucas; Charles J. Marsh; et al. (Trends in Ecology & Evolution, 2023)

Polyamines and hormesis: Making sense of a dose response dichotomy - Edward Calabrese; A. Wallace Hayes; Peter Pressman; Rachna Kapoor; Gaurav Dhawan; Vittorio Calabrese; Evgenios Agathokleous (Chemico-Biological Interactions, 2023)

Live slow, die old: larval propagation of slow-growing, stress-tolerant corals for reef restoration - James Guest; Maria Vanessa Baria-Rodriguez; Tai Chong Toh; Dexter dela Cruz; Kareen Vicentuan; Edgardo Gomez; Ronald Villanueva; Peter Steinberg; Alasdair Edwards (Coral Reefs, 2023)
Efforts to restore coral reefs usually involve transplanting asexually propagated fast-growing corals. However, this approach can lead to outplanted populations with low genotypic diversity, composed of taxa susceptible to stressors such as marine heatwaves. Sexual coral propagation leads to greater genotypic diversity, and using slow-growing, stress-tolerant taxa may provide a longer-term return on restoration efforts due to higher outplant survival. However, there have been no reports to date detailing the full cycle of rearing stress-tolerant, slow-growing corals from eggs until sexual maturity. Here, we sexually propagated and transplanted two massive slow-growing coral species to examine long-term success as part of reef restoration efforts. Coral spat were settled on artificial substrates and reared in nurseries for approximately two years, before being outplanted and monitored for survivorship and growth for a further four years. More than half of initially settled substrates supported a living coral following nursery rearing, and survivorship was also high following outplantation with yields declining by just 10 to 14% over four years. At 6-years post-fertilisation over 90% of outplanted corals were reproductively mature, demonstrating the feasibility of restoring populations of sexually mature massive corals in under a decade. Although use of slower growing, stress tolerant corals for reef restoration may provide a longer-term return on investment due to high post-transplantation survival rates, considerable time is required to achieve even modest gains in coral cover due to their relatively slow rates of growth. This highlights the need to use a mix of species with a range of life-history traits in reef restoration and to improve survivorship of susceptible fast-growing taxa that can generate rapid increases in coral cover.

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Miocene cave sediments record topographic, erosional and drainage development in the Western European Alps - François Lemot; Pierre G. Valla; Peter van der Beek; Marianna Jagercikova; Samuel Niedermann; Julien Carcaillet; Edward R. Sobel; Sergio Andò; Eduardo Garzanti; Xavier Robert; Mélanie Balvay; Matthias Bernet; et al. (Earth and Planetary Science Letters, 2023)

Observed amplification of the seasonal CO2 cycle at the Southern Ocean Time Series - Elizabeth H. Shadwick; Cathryn A. Wynn-Edwards; Richard J. Matear; Peter Jansen; Eric Schulz; Adrienne J. Sutton (Frontiers in Marine Science, 2023)
The Subantarctic Zone, the circumpolar region of the Southern Ocean between the Subtropical and Subantarctic fronts, plays an important role in air-sea CO 2 exchange, the storage of anthropogenic CO 2 , and the ventilation of the lower thermocline. Here we use a time series from moored platforms deployed between 2011 and 2021 as part of the Southern Ocean Time Series (SOTS) observatory to investigate the seasonality and interannual variability of upper ocean hydrography and seawater CO 2 partial pressure (pCO 2 ). The region is a net sink for atmospheric CO 2 over the nearly 10-year record, with trends revealing that the ocean pCO 2 may be increasing slightly faster than the atmosphere, suggesting that oceanic as well as anthropogenic atmospheric forcing contributes to the decadal change, which includes a decline in pH on the order of 0.003 yr −1 . The observations also show an amplification of the seasonal cycle in pCO 2 , potentially linked to changes in mixed layer depth and biological productivity.

Naringin commonly acts via hormesis - Edward J. Calabrese; Peter Pressman; A. Wallace Hayes; Gaurav Dhawan; Rachna Kapoor; Evgenios Agathokleous; Prabhjot Manes; Vittorio Calabrese (Science of The Total Environment, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Interactions among Sodalis, Glossina pallidipes salivary gland hypertrophy virus and trypanosomes in wild Glossina pallidipes - Deusdedit J. Malulu; Hamisi S. Nyingilili; Delphina Edward; Peter Lucas; Ismail W. R. Taifa; Imna I. Malele; Adly M. M. Abd-Alla (International Journal of Tropical Insect Science, 2023)

Long-term effects of gypsum on the chemistry of sodic soils - Hannah Green; Peter Larsen; Jack Koci; Will Edwards; Paul N. Nelson (Soil and Tillage Research, 2023)

Who knew afforestation was such a challenge? Motivations and impediments to afforestation policy in New Zealand - Geoff Kaine; Peter Edwards; Maksym Polyakov; Philip Stahlmann-Brown (Forest Policy and Economics, 2023)

Subantarctic pCO2 estimated from a biogeochemical float: comparison with moored observations reinforces the importance of spatial and temporal variability - Cathryn Ann Wynn-Edwards; Elizabeth H. Shadwick; Peter Jansen; Christina Schallenberg; Tanya Lea Maurer; Adrienne J. Sutton (Frontiers in Marine Science, 2023)
Understanding the size and future changes of natural ocean carbon sinks is critical for the projection of atmospheric CO 2 levels. The magnitude of the Southern Ocean carbon flux has varied significantly over past decades but mechanisms behind this variability are still under debate. While high accuracy observations, e.g. from ships and moored platforms, are important to improve models they are limited through space and time. Observations from autonomous platforms with emerging biogeochemical capabilities, e.g. profiling floats, provide greater spatial and temporal coverage. However, the absolute accuracy of CO 2 partial pressure ( p CO 2 ) derived from float pH sensors is not well constrained. Here we capitalize on data collected for over a year by a biogeochemical Argo float near the Southern Ocean Time Series observatory to evaluate the accuracy of p CO 2 estimates from floats beyond the initial in water comparisons at deployment. A latitudinal gradient of increasing p CO 2 southward and spatial variability contributed to observed discrepancies. Comparisons between float estimated p CO 2 and mooring observations were therefore restricted by temperature and potential density criteria (~ 7 µatm difference) and distance (1° latitude and longitude, ~ 11 µatm difference). By utilizing high quality moored and shipboard underway p CO 2 observations, and estimates from CTD casts, we therefore found that over a year, differences in p CO 2 between platforms were within tolerable uncertainties. Continued validation efforts, using measurements with known and sufficient accuracy, are vital in the continued assessment of float-based p CO 2 estimates, especially in a highly dynamic region such as the subantarctic zone of the Southern Ocean.

Lithium and hormesis: Enhancement of adaptive responses and biological performance via hormetic mechanisms - Edward J. Calabrese; Peter Pressman; A.Wallace Hayes; Gaurav Dhawan; Rachna Kapoor; Evgenios Agathokleous; Vittorio Calabrese (Journal of Trace Elements in Medicine and Biology, 2023)

Toward a ground-based and long-term meteorological forcing dataset for South Korea - Kyungtae Lee; Do Hyuk Kang; Hahn Chul Jung; Gwangha Park; Changwoo Gye; Sujay Kumar; Edward J. Kim; Christa D. Peters-lidard; EuiHo Hwang (Theoretical and Applied Climatology, 2023)
The Modern-Era Retrospective Analysis for Research and Application version 2 (MERRA-2) is a well-established reanalysis dataset and is widely used for driving global-scale hydrological models. However, owing to its relatively coarse spatial resolution (0.5°), the capability of MERRA-2 is repeatedly challenged in regional-scale studies, especially for smaller areas of interest. In addition, the availability of in situ observation data is a pressing issue for generating meteorological forcing. We developed a grid-based high spatial (0.125°) and temporal (hourly) resolution meteorological forcing dataset, which can evaluate hydrological processes in South Korea using state-of-the-art meteorological observations from 1980 to 2020. The forcing dataset was created by combining Automated Synoptic Observing System (ASOS) in situ measurement data from the Korean Meteorological Administration and MERRA-2 reanalysis datasets. Five meteorological variables were provided in the ASOS-MERRA2 (precipitation, air temperature, surface pressure, specific humidity, and wind speed). The study demonstrates that the region-based and high spatial resolution of ASOS-MERRA2 is superior to the existing MERRA-2 with improvements of all five weather variables, for example, from 5.6 to 2.8 mm root mean square error of precipitation. The ASOS-MERRA2 was more capable of reducing the biases and root mean squared error by improving the coefficient of determination compared with MERRA-2 for all five variables. The newly developed ASOS-MERRA2 provides an opportunity to drive land surface models to evaluate the hydroclimatic conditions in South Korea.

Evolutionary dynamics and adaptive benefits of deleterious mutations in crop gene pools - Sangam L. Dwivedi; Pat Heslop-Harrison; Charles Spillane; Peter C. McKeown; David Edwards; Irwin Goldman; Rodomiro Ortiz (Trends in Plant Science, 2023)

Long-term trends in nitrate and chloride in streams in an exurban watershed - Emma S. Castiblanco; Peter M. Groffman; Jonathan Duncan; Lawrence E. Band; Edward Doheny; Gary T. Fisher; Emma Rosi; Amanda K. Suchy (Urban Ecosystems, 2023)

The benefits of regular aerobic exercise training on cerebrovascular function and cognition in older adults - Edward S. Bliss; Samia M. Biki; Rachel H. X. Wong; Peter R. C. Howe; Dean E. Mills (European Journal of Applied Physiology, 2023)
We compared the differences in cerebrovascular and cognitive function between 13 aerobic exercise trained, older adults and 13 age-, height- and sex-matched sedentary, untrained controls. We determined whether other measures accounted for differences in cerebrovascular and cognitive function between these groups and examined the associations between these functions. Participants undertook anthropometric, mood, cardiovascular, exercise performance, strength, cerebrovascular, and cognitive measurements, and a blood collection. Transcranial Doppler ultrasonography determined cerebrovascular responsiveness (CVR) to hypercapnia and cognitive stimuli. The trained group had a higher CVR to hypercapnia (80.3 ± 7.2 vs 35.1 ± 6.7%, P < 0.001), CVR to cognitive stimuli (30.1 ± 2.9 vs 17.8 ± 1.4%, P = 0.001) and total composite cognitive score (117 ± 2 vs 98 ± 4, P < 0.001) than the controls. These parameters no longer remained statistically different between the groups following adjustments for covariates. There were positive correlations between the total composite cognitive score and CVR to hypercapnia ( r = 0.474, P = 0.014) and CVR to cognitive stimuli ( r = 0.685, P < 0.001). We observed a relationship between cerebrovascular and cognitive function in older adults and an interaction between regular lifelong aerobic exercise training and cardiometabolic factors that may directly influence these functions.

Boron enhances adaptive responses and biological performance via hormetic mechanisms - Edward Calabrese; Peter Pressman; Evgenios Agathokleous; Gaurav Dhawan; Rachna Kapoor; Vittorio Calabrese (Chemico-Biological Interactions, 2023)

An inter-method comparison of mercury measurements in Icelandic volcanic gases - Brock A. Edwards; Melissa A. Pfeffer; þorsteinn Jóhannsson; Peter M. Outridge; Feiyue Wang (Applied Geochemistry, 2023)

Contractile Adaptation of the Left Ventricle Post-myocardial Infarction: Predictions by Rodent-Specific Computational Modeling - Emilio A. Mendiola; Sunder Neelakantan; Qian Xiang; Samer Merchant; Ke Li; Edward W. Hsu; Richard A. F. Dixon; Peter Vanderslice; Reza Avazmohammadi (Annals of Biomedical Engineering, 2023)

Ocean monitoring, observation network and modelling of the Gulf of Mexico by CIGOM - Juan Carlos Herguera; Edward M. Peters; Julio Sheinbaum; Paula Pérez-Brunius; Sharon Z. Herzka; Alexei Licea-Navarro; Francisco Ocampo-Torres; M. Leopoldina Aguirre-Macedo; Victor M. Vidal-Martínez; Hector García-Nava; Tomas Salgado; Rosario Romero-Centeno; et al. (Frontiers in Marine Science, 2023)
The tragic accident of the Macondo platform operated by British Petroleum (BP) unleashed in 2010 one of the largest oil spills in history, lasting over three months, spilling nearly 500 million liters of oil in one of the most biodiverse ocean regions. This accident revealed the technological deficiencies for the control of a spill in deep waters of the hydrocarbon industry. Simultaneously it showed important gaps in knowledge to predict the propagation and fate of the large volumes of hydrocarbons at depth and on the surface ocean and, more importantly, on their impact on the great ecosystem of the Gulf of Mexico. The necessity to understand and predict the transport, fate and ecosystem-level impacts of large oil spills in the southern Gulf of Mexico, a key region for oil exploration and extraction, led policymakers, scientists, and industry representatives from PEMEX (the Mexican oil company) to jointly launch an ocean observation project (2015-22) aimed to provide a multi-layered environmental baseline, develop a modern monitoring and computational modeling capacity and promote scientific understanding of the marine environment throughout the Mexican Exclusive Economic Zone (EEZ). The initiative, led by the Research Consortium for the Gulf of Mexico (CIGoM), brought together more than 300 multidisciplinary researchers from more than a two dozen institutions in Mexico and abroad, including the Centre for Scientific Research and Higher Education of Ensenada (CICESE) as the leading institution, the National Autonomous University of Mexico (UNAM), the Centre for Research and Advanced Studies of the National Polytechnic Institute (CINVESTAV) in Mérida, the Autonomous University of Baja California (UABC), and the Centre for Engineering and Industrial Development (CIDESI). Financial support was provided by the National Council for Science and Technology and the Ministry of Energy Hydrocarbon Fund.

Survival of epithelial ovarian cancer in Black women: a society to cell approach in the African American cancer epidemiology study (AACES) - Joellen M. Schildkraut; Courtney Johnson; Lauren F. Dempsey; Bo Qin; Paul Terry; Maxwell Akonde; Edward S. Peters; Hannah Mandle; Michele L. Cote; Lauren Peres; Patricia Moorman; Ann G. Schwartz; et al. (Cancer Causes & Control, 2023)
Purpose The causes for the survival disparity among Black women with epithelial ovarian cancer (EOC) are likely multi-factorial. Here we describe the African American Cancer Epidemiology Study (AACES), the largest cohort of Black women with EOC. Methods AACES phase 2 (enrolled 2020 onward) is a multi-site, population-based study focused on overall survival (OS) of EOC. Rapid case ascertainment is used in ongoing patient recruitment in eight U.S. states, both northern and southern. Data collection is composed of a survey, biospecimens, and medical record abstraction. Results characterizing the survival experience of the phase 1 study population (enrolled 2010–2015) are presented. Results Thus far, ~ 650 patients with EOC have been enrolled in the AACES. The five-year OS of AACES participants approximates those of Black women in the Surveillance Epidemiology and End Results (SEER) registry who survive at least 10-month past diagnosis and is worse compared to white women in SEER, 49 vs. 60%, respectively. A high proportion of women in AACES have low levels of household income (45% < $25,000 annually), education (51% ≤ high school education), and insurance coverage (32% uninsured or Medicaid). Those followed annually differ from those without follow-up with higher levels of localized disease (28 vs 24%) and higher levels of optimal debulking status (73 vs 67%). Conclusion AACES is well positioned to evaluate the contribution of social determinants of health to the poor survival of Black women with EOC and advance understanding of the multi-factorial causes of the ovarian cancer survival disparity in Black women.

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

Foxes at your front door? Habitat selection and home range estimation of suburban red foxes (Vulpes vulpes) - Halina T. Kobryn; Edward J. Swinhoe; Philip W. Bateman; Peter J. Adams; Jill M. Shephard; Patricia A. Fleming (Urban Ecosystems, 2023)
The red fox ( Vulpes vulpes ) is one of the most adaptable carnivorans, thriving in cities across the globe. We used GPS-tracking of five suburban foxes across high-density residential suburbs of Perth, Western Australia to quantify (1) their habitat selection and (2) home range area. All five foxes showed statistically significant avoidance of residential locations (p < 0.001) and preference for parkland (p < 0.001), with native vegetation reserves, golf courses, and water reserves showing disproportionately greater use. Landuse category also influenced their movements, with foxes moving quickest (i.e., commuting) in proximity to roads and slowest (i.e., foraging) when they were further from roads. Three females had core home ranges (50% autocorrelated-corrected kernel density estimate; AKDE c ) averaging 37 ± 20 ha or 95% AKDE c averaging 208 ± 196 ha. One male had a 95 ha core home range and 349 ha 95% AKDE c but the other male covered an area ~ 20 times this: using a 371 ha core home range and 7,368 ha 95% AKDE c . The extensive movement patterns we describe are likely to be common for urban foxes, with half of published home range estimates for urban foxes (principally based on VHF data) excluding data for ‘lost’ individuals or animals that showed ‘excursions’. It is likely that the home range estimates for these urban exploiters have therefore been grossly underestimated to date. Further application of GPS trackers that allow remote download will vastly improve our understanding of habitat preference and exploitation of resources by urban foxes.

Profiling human pathogenic repeat expansion regions by synergistic and multi-level impacts on molecular connections - Cong Fan; Ken Chen; Yukai Wang; Edward V. Ball; Peter D. Stenson; Matthew Mort; Albino Bacolla; Hildegard Kehrer-Sawatzki; John A. Tainer; David N. Cooper; Huiying Zhao (Human Genetics, 2023)

A roadmap for ladybird conservation and recovery - António O. Soares; Danny Haelewaters; Olga M. C. C. Ameixa; Isabel Borges; Peter M. J. Brown; Pedro Cardoso; Michiel D. de Groot; Edward W. Evans; Audrey A. Grez; Axel Hochkirch; Milada Holecová; Alois Honěk; et al. (Conservation Biology, 2023)
Ladybirds (Coleoptera: Coccinellidae) provide services that are critical to food production, and they fulfill an ecological role as a food source for predators. The richness, abundance, and distribution of ladybirds, however, are compromised by many anthropogenic threats. Meanwhile, a lack of knowledge of the conservation status of most species and the factors driving their population dynamics hinders the development and implementation of conservation strategies for ladybirds. We conducted a review of the literature on the ecology, diversity, and conservation of ladybirds to identify their key ecological threats. Ladybird populations are most affected by climate factors, landscape composition, and biological invasions. We suggest mitigating actions for ladybird conservation and recovery. Short‐term actions include citizen science programs and education, protective measures for habitat recovery and threatened species, prevention of the introduction of non‐native species, and the maintenance and restoration of natural areas and landscape heterogeneity. Mid‐term actions involve the analysis of data from monitoring programs and insect collections to disentangle the effect of different threats to ladybird populations, understand habitat use by taxa on which there is limited knowledge, and quantify temporal trends of abundance, diversity, and biomass along a management‐intensity gradient. Long‐term actions include the development of a worldwide monitoring program based on standardized sampling to fill data gaps, increase explanatory power, streamline analyses, and facilitate global collaborations.

Solar-driven semi-conductor photocatalytic water treatment (TiO2, g-C3N4, and TiO2+g-C3N4) of cyanotoxins: Proof-of-concept study with microcystin-LR - Carlos J. Pestana; Jianing Hui; Dolores Camacho-Muñoz; Christine Edwards; Peter K.J. Robertson; John.T.S. Irvine; Linda A. Lawton (Chemosphere, 2023)

Progress of Fisheries-Oceanography Coordinated Investigations in the Gulf of Alaska and Aleutian Passes - Calvin Mordy; Nicholas Bond; Edward Cokelet; Alison Deary; Emily Lemagie; Peter Proctor; Phyllis Stabeno; Heather Tabisola; Thomas Van Pelt; Eric Wisegarver (Oceanography, 2023)
Ecosystems & Fisheries-Oceanography Coordinated Investigations (EcoFOCI) is a joint research program between the NOAA Pacific Marine Environmental Laboratory and the Alaska Fisheries Science Center (AFSC). FOCI was established by NOAA in 1984 to study the variability in recruitment success of commercially valuable fin and shellfish in Alaskan waters. The project initially studied walleye pollock (Gadus chalcogrammus) in the context of western Gulf of Alaska oceanography and meteorology. Transitioning from FOCI to EcoFOCI, the program broadened into ecosystem research in the North Pacific and US Arctic (including climate), drawing on multiple scientific disciplines, and continuing to match NOAA scientists with academic colleagues working at NOAA’s cooperative institutes and other universities. EcoFOCI is an authoritative provider of scientific information that supports decision-making and environmental stewardship in Alaskan marine ecosystems through collaborative partnerships, innovation, and scientific integrity. Here, we discuss the origins of EcoFOCI and highlight a few of the scientific accomplishments of the program in understanding the drivers and impacts of long-term oceanographic trends, as well as extreme and episodic events, in the Gulf of Alaska and Aleutian Island ecosystems.

Ocean Monitoring and Prediction Network for the Sustainable Development of the Gulf of Mexico and the Caribbean - Juan Carlos Herguera; Edward Peters; Julio Sheinbaum; Paula Pérez-Brunius; Vanesa Magar; Enric Pallàs-Sanz; Sheila Estrada Allis; Leopoldina Aguirre-Macedo; Victor Vidal-Martinez; Cecilia Enriquez; Ismael Mariño Tapia; Hector García Nava; et al. (Oceanography, 2023)
The need to understand and forecast disasters driven by anthropogenic and natural forces in the Gulf of Mexico and to support management responses to hazardous events led policymakers, scientists, and industry representatives in Mexico to launch an ocean observation and modeling project (2015–2023) aimed at collecting multi-layered baseline information and continuous monitoring of the ocean environment across the southern Gulf of Mexico. The observational network and modeling efforts, led by the Consorcio de Investigación del Golfo de México (Research Consortium for the Gulf of Mexico, CIGoM), include developing a marine hazard warning system to investigate multiple stressors that are altering the state and health of this large marine ecosystem and its coastal communities. This warning system is intended to aid in the establishment of national contingency plans and mitigate the impacts of extreme events and long-term ocean trends. Stressors include hydrocarbon spills, tropical cyclones, marine heatwaves, long-term ocean surface warming, harmful algal blooms, and massive Sargassum landings.

Ground-motion prediction models for induced earthquakes in the Groningen gas field, the Netherlands - Julian J. Bommer; Peter J. Stafford; Elmer Ruigrok; Adrian Rodriguez-Marek; Michail Ntinalexis; Pauline P. Kruiver; Benjamin Edwards; Bernard Dost; Jan van Elk (Journal of Seismology, 2022)
Small-magnitude earthquakes induced by gas production in the Groningen field in the Netherlands have prompted the development of seismic risk models that serve both to estimate the impact of these events and to explore the efficacy of different risk mitigation strategies. A core element of the risk modelling is ground-motion prediction models (GMPM) derived from an extensive database of recordings obtained from a dense network of accelerographs installed in the field. For the verification of damage claims, an empirical GMPM for peak ground velocity (PGV) has been developed, which predicts horizontal PGV as a function of local magnitude, M L ; hypocentral distance, R hyp ; and the time-averaged shear-wave velocity over the upper 30 m, V S30 . For modelling the risk due to potential induced and triggered earthquakes of larger magnitude, a GMPM for response spectral accelerations has been developed from regressions on the outputs from finite-rupture simulations of motions at a deeply buried rock horizon. The GMPM for rock motions is coupled with a zonation map defining frequency-dependent non-linear amplification factors to obtain estimates of surface motions in the region of thick deposits of soft soils. The GMPM for spectral accelerations is formulated within a logic-tree framework to capture the epistemic uncertainty associated with extrapolation from recordings of events of M L ≤ 3.6 to much larger magnitudes.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

A Multidisciplinary Computational Framework for Topology Optimisation of Offshore Helidecks - Siamak Farajzadeh Khosroshahi; Marinella Masina; Alessandro Antonini; Edward Ransley; James Mark William Brownjohn; Peter Dobson; Dina D’Ayala (Journal of Marine Science and Engineering, 2022)
Maintaining offshore steel structures is challenging and not environmentally friendly due to the frequent visits for inspection and repairs. Some offshore lighthouses are equipped with carbon steel helidecks fixed onto their lantern galleries in the 1970s to provide easy and safe access to maintenance staff and inspectors. Even though the helidecks supporting structures have maintained their integrity and are still functional in the offshore harsh environmental conditions, their inspection and maintenance remains a challenge due to the need of frequent visits which requires flying to the location of the lighthouse to bring the maintenance staff and equipment. We have developed a multidisciplinary computational framework to design new generation of aluminium helidecks for offshore lighthouses. We calculated the wind speed at the location of the Bishop Rock lighthouse based on the meteorological data, and the load distribution on the helideck due to such a wind condition, using computational fluid dynamic analysis. Then, we used the calculated wind load with other mechanical loads in the events of normal and emergency landings of a helicopter on this structure to find the best design configuration for this helideck. We generated a design space for different configurations of a beam structure and carried out, static, transient and buckling analysis to assess each case using finite element method. The selection criterion was set to find the structure with the minimum volume fraction and compliance while keeping the stress below the allowable stress. We found the structure with eight vertical and circumferential sections featuring two rows of diagonal bracing with one at the base and the other one at the third section from the base of the helideck was the optimum design for the considered loading in this work. This framework can be adopted for the design and optimisation of other offshore structures by other researchers and designers.

Long‐term drivers and timing of accelerated vegetation changes in African biomes and their management implications - Matthew Adesanya Adeleye; Simon Edward Connor; Simon Graeme Haberle; Sarah Ivory; Peter Adegbenga Adeonipekun (Global Ecology and Biogeography, 2022)
Aim Owing to its diverse bioclimatic zones, long human history and intense anthropogenic impacts, Africa provides a model system for studying how global terrestrial ecosystems might respond to accelerated socio‐environmental stress. Africa is particularly vulnerable to climate change and human impact, and insufficient baseline data hamper current environmental management efforts. Using palaeoecological data, we seek to identify the timing, pace and drivers of change in African biomes on a long‐term scale to inform current ecosystem management frameworks on the continent. Location Africa. Time period 0–12 ka. Major taxa studied African biomes. Methods Sixty‐four pollen records across Africa and nearby sites were retrieved from multiple databases/sources and grouped into biomes. Turnover (quantified using the squared chord distance dissimilarity metric) and rarefaction analyses were conducted on pollen records in each biome group to reconstruct regional temporal vegetation turnover and richness. Reconstructed vegetation turnover and richness were compared with independent records of climate, fire and human activity to identify possible drivers of change. Results We found that the most stable biomes were those with the greatest floristic richness. Southern Africa's mediterranean‐type (SAM) ecosystems were the most stable and northern Africa's mediterranean‐type (NAM) ecosystems were the most unstable (mainly owing to fire). Tropical savannas (TS) and SAM ecosystems expressed the most sensitivity to climatic shifts from ≥6 ka, whereas tropical forests (TF) were relatively stable before human activities intensified from c . 2 ka. Floristic richness also declined across the tropics from c . 2 ka. Main conclusions Our analysis pinpoints NAM ecosystems as undergoing the fastest acceleration in turnover on the continent in response to fire, whereas TF and TS have been undergoing unprecedented changes in biodiversity in the last 2,000 years. We expect further changes in biodiversity where climate becomes warmer and drier and where human impacts are novel and rapid in comparison to long‐term baselines.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Microsatellite markers as a tool for active germplasm management and bridging the gap between national and local collections of apple - Edward P. Venison; Suzanne Litthauer; Peter Laws; Caroline Denancé; Felicidad Fernández-Fernández; Charles-Eric Durel; Matthew Ordidge (Genetic Resources and Crop Evolution, 2022)
Simple sequence repeat (SSR) microsatellite markers have been extensively used to identify duplication and analyse genetic diversity in germplasm collections of apple. Here, we present findings from the use of a standard set of SSR loci in the managed repropagation of a significant international germplasm collection: the UK National Fruit Collection (NFC). A subset of eight SSR loci was deemed sufficient to distinguish all apart from the clonal relatives across a sample of 1995 accessions, with a single exception being one pair of full siblings. In total, 99% of accessions were able to be confirmed present and correct after the replacement of trees initially identified to be incorrectly propagated. In parallel to the curation of the collection itself, through an initiative led by the UK local apple enthusiast community, 3373 SSR profiles for apples held in local collections were compared to the NFC holdings. Overall, in both sets of material, diversity remained high with average gene diversity values of 0.800 and 0.812 in the NFC holdings and local collections, respectively. Accessions in local collections were not found to differ in their overall coverage of genetic diversity to that of the NFC collection (F ST = 0.0035) although significant numbers of locally valued, and genetically distinguishable individuals were identified, some of which may represent ‘lost’ cultivars.

High‐resolution water‐quality and ecosystem‐metabolism modeling in lowland rivers - Devanshi Pathak; Michael Hutchins; Lee E. Brown; Matthew Loewenthal; Peter Scarlett; Linda Armstrong; David Nicholls; Mike Bowes; François Edwards; Gareth Old (Limnology and Oceanography, 2022)
High‐resolution monitoring of water quality and ecosystem functioning over large spatial scales in expansive lowland river catchments is challenging. Therefore, we need modeling tools to predict these processes at locations where observations are absent. Here, we present a new approach to estimate ecosystem metabolism underpinned by a high‐resolution, process‐based model of in‐stream flows and water quality. The model overcomes the current challenges in metabolism modeling by accounting for oxygen transport under varying flows and oxygen transformations due to biogeochemical processes. We implement the model in a 62‐km‐long stretch of the River Thames, England, using observations spanning 2 yr. Model outputs suggest that the river is primarily autotrophic from mid‐spring to mid‐summer due to high biomass during low‐flow periods, and is heterotrophic during the rest of the year. Ecosystem respiration in upstream reaches is driven mainly by biochemical oxygen demand, autotrophic respiration, and nitrification processes, whereas downstream sites also show a control of benthic oxygen demand in addition to the aforementioned processes. Using empirical modeling, we analyze the sensitivity of our estimated metabolism rates to multiple environmental stressors. Results demonstrate that empirical models could be useful for rapid river health assessments, but need improvements to reproduce peak metabolism rates. The process‐based model, although more complex than existing in situ approaches to metabolism quantification, allows inference when gaps in continuous observations are present. The model offers additional benefits for predicting metabolism rates under future scenarios of environmental change incorporating multiple stressor effects.

Bioaccumulation of metals by algae from acid mine drainage: a case study of Frongoch Mine (UK) - Tianhao Du; Anna Bogush; Paul Edwards; Peter Stanley; Ana T. Lombardi; Luiza C. Campos (Environmental Science and Pollution Research, 2022)
In Frongoch Mine (UK), it is unclear the distribution of metals on indigenous algae and whether these species of algae can accumulate metals. This study aimed to investigate the role of indigenous algae for metal removal from acid mine drainage and understand if metals can be adsorbed on the surface of algae or/and bioaccumulated in algae. A sequential extraction procedure was applied for algae samples collected from acid mine drainage (AMD) water to identify the forms in which metals are found in algae. Concentrations of Fe, Pb, Zn, Cu and Cd were evaluated in the algae and AMD samples were collected in June and October 2019. AMDs samples had a pH value ranging between 3.5 and 6.9 and high concentrations of Zn (351 mg/L) and Pb (4.22 mg/L) that exceeded the water quality standards (Water Framework Directive, 2015). Algae Ulothrix sp . and Oedogonium sp. were the two main species in the Frongoch AMDs. The concentrations of metals in algae ranged from 0.007 to 51 mg/g, and the bioconcentration factor of metals decreased in the following order: Fe > > Pb > > Cu > Cd > Zn. It was found that Zn, Cu and Cd were adsorbed onto the surface of and bioaccumulated in the algae, while Pb and Fe were mainly bioaccumulated in the algae. Indigenous algae can be considered as a biogeochemical barrier where metals are accumulating and can be used in bioremediation methods. Also, indigenous algae could be used as a bioindicator to assess water pollution at Frongoch Mine and other similar metal mines.

Behavioural Responses of a Large, Benthic Elasmobranch to Catch-and-Release Angling - Edward Lavender; Dmitry Aleynik; Jane Dodd; Janine Illian; Mark James; Peter J. Wright; Sophie Smout; James Thorburn (Frontiers in Marine Science, 2022)
Catch-and-release angling is widespread, but the impacts of this practice for captured individuals are understudied, especially among elasmobranchs. Studies on sub-lethal behavioural impacts are particularly sparse, despite their importance for the interpretation of biologging data and for assessments of species’ tolerance to capture. In this study, the behavioural responses of flapper skate ( Dipturus intermedius ) to catch-and-release angling were described for the first time, using archival observations (depth and temperature) for 21 tag deployment/retrieval events and five recreational angling events that occurred during tagged individuals’ time at liberty from charter vessels off the west coast of Scotland in 2016–17. During capture (8–50 minutes), the changes in depth and temperature experienced by individuals typically exceeded natural variability. Post-release, behavioural change was apparent from visual inspection, regression and functional data analysis of the time series. Immediately following release, movements into deeper water and short periods of low vertical activity (usually 1–2 hours in duration) were common. However, overall average vertical activity was typically around 38% higher in the 12 hours following release than in undisturbed activity. A small number of individuals (n = 3, 14%) exhibited irregular post-release behaviour in the form of rapid, transient re-ascents towards the surface following release. Collectively, the evidence for limited, short-term behavioural changes suggests that flapper skate behaviour is relatively resilient to catch-and-release angling from charter vessels, but irregular post-release behaviour in 14% of individuals is sufficiently notable to indicate that further research is required on the impacts of this practice. This study clearly demonstrates the value of biologging data and behavioural analyses for examining the impacts of disturbance and separating ‘disturbed’ and ‘undisturbed’ behaviours in studies of animal movement.

A National Status Report on United States Coral Reefs Based on 2012–2018 Data From National Oceanic and Atmospheric Administration’s National Coral Reef Monitoring Program - Erica K. Towle; E. Caroline Donovan; Heath Kelsey; Mary E. Allen; Hannah Barkley; Jeremiah Blondeau; Russell E. Brainard; Annie Carew; Courtney S. Couch; Maria K. Dillard; C. Mark Eakin; Kimberly Edwards; et al. (Frontiers in Marine Science, 2022)
National Oceanic and Atmospheric Administration’s Coral Reef Conservation Program supports the National Coral Reef Monitoring Program (NCRMP) in the United States Pacific, Atlantic, Caribbean, and Gulf of Mexico. NCRMP conducts standardized observations of biological, climatic, and socioeconomic indicators across American Samoa, Guam, the Main Hawaiian Islands, the Northwestern Hawaiian Islands, the Northern Mariana Islands, the Pacific Remote Islands, Florida, the Flower Garden Banks, Puerto Rico, and the United States Virgin Islands. NCRMP provides periodic, national-level assessments of the status of United States coral reef ecosystems and communities connected to them. In 2014, NCRMP partnered with the University of Maryland Center for Environmental Science on an unprecedented collaboration between federal and jurisdictional/state agencies, academia, and non-governmental organizations to synthesize NCRMP data into a reporting format designed to be accessible and relevant to the public and policy makers. The process involved multi-year data analyses of key benthic, fish, and climate indicators. In populated jurisdictions, socioeconomic data were integrated to assess public support for management actions, participation in pro-environmental behaviors, and awareness of threats to coral reefs. Jurisdictions were scored using a report-card scale (0–100%) by establishing references for each indicator using best-available historical data or expert opinion where historical data did not exist or were not statistically comparable. Despite overall ecosystem scores of Fair for all combined Atlantic (70%) and Pacific (74%) jurisdictions, the current trend is downward with a majority of United States coral reefs declining and vulnerable to further degradation. Remote, uninhabited reefs had an advantage with respect to reef fish population scores, i.e., Flower Garden Banks (85%) and Pacific Remote Islands (93%), when compared to populated location scores, i.e., Puerto Rico (63%) and Main Hawaiian Islands (66%). All coral reefs are highly impacted by climate change, and climate impacts were more pronounced than expected on remote reefs, i.e., the Northwestern Hawaiian Islands (58%). Presenting results in a report-card style facilitates communication to the public and policy makers, and provides a useful mechanism to garner support for management actions such as expanding protected areas; enforcing existing regulations; increasing climate change education; reducing land-based sources of pollution; and other actions to improve the trajectory of coral reef ecosystem conditions.

Litter decomposition and infiltration capacities in soils of different tropical urban land covers - Tze Kwan Fung; Daniel R. Richards; Rachel A. T. Leong; Subhadip Ghosh; Christabel W. J. Tan; Zuzana Drillet; Kit Ling Leong; Peter J. Edwards (Urban Ecosystems, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Forests under the Southern Cross: The forest environmental frontier in Australia and New Zealand - Peter Kanowski; Peter Edwards (Ambio, 2021)

Changes in Southern Ocean Biogeochemistry and the Potential Impact on pH-Sensitive Planktonic Organisms - Elizabeth Shadwick; Andrés Rigual-Hernández; Ruth Eriksen; Peter Jansen; Diana Davies; Cathryn Wynn-Edwards; Adrienne Sutton; Christina Schallenberg; Thomas Trull (Oceanography, 2021)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Guiding principles for rewilding - Steve Carver; Ian Convery; Sally Hawkins; Rene Beyers; Adam Eagle; Zoltan Kun; Erwin Van Maanen; Yue Cao; Mark Fisher; Stephen R. Edwards; Cara Nelson; George D. Gann; et al. (Conservation Biology, 2021)
There has been much recent interest in the concept of rewilding as a tool for nature conservation, but also confusion over the idea, which has limited its utility. We developed a unifying definition and 10 guiding principles for rewilding through a survey of 59 rewilding experts, a summary of key organizations’ rewilding visions, and workshops involving over 100 participants from around the world. The guiding principles convey that rewilding exits on a continuum of scale, connectivity, and level of human influence and aims to restore ecosystem structure and functions to achieve a self‐sustaining autonomous nature. These principles clarify the concept of rewilding and improve its effectiveness as a tool to achieve global conservation targets, including those of the UN Decade on Ecosystem Restoration and post‐2020 Global Biodiversity Framework. Finally, we suggest differences in rewilding perspectives lie largely in the extent to which it is seen as achievable and in specific interventions. An understanding of the context of rewilding projects is the key to success, and careful site‐specific interpretations will help achieve the aims of rewilding.

Mean sea level and tidal change in Ireland since 1842: a case study of Cork - David T. Pugh; Edmund Bridge; Robin Edwards; Peter Hogarth; Guy Westbrook; Philip L. Woodworth; Gerard D. McCarthy (Ocean Science, 2021)
Knowledge of regional changes in mean sea level and local changes in tides are crucial to inform effective climate adaptation. An essential element is the availability of accurate observations of sea level. Sea level data in the Republic of Ireland, prior to the establishment of the National Tide Gauge Network in the mid-2000s, are limited but belie a wealth of historical data available in archival form. In this study, we digitize records located in Cork Harbour, Ireland, from 1842 and show how short-duration (6–8 weeks), high-quality data with a large interval to the present can accurately inform tidal and mean sea level changes. We consider error sources in detail. We estimate for the main M2 tidal constituent that the accuracy of these historical measurements is 1 % and 2 min for amplitude and phase, respectively, once adjustments for seasonal and nodal effects are made. Our mean sea level estimates are accurate to the 2 cm level, once adjustments for atmospheric and seasonal effects are made. Our results show tidal stability with a 2 % change in the amplitude of the M2 component, 4 min change in the phase over a period of 177 years, and mean sea level rise of 40 cm in the Cork Harbour area from 1842 to 2019, approximately in line with global mean sea level trends plus local glacial isostatic adjustment. More broadly, we show that with careful seasonal, nodal, and atmospheric corrections, together with knowledge of benchmark provenance, these historic, survey-oriented data can accurately inform of sea level changes.

Environmental cycles and individual variation in the vertical movements of a benthic elasmobranch - Edward Lavender; Dmitry Aleynik; Jane Dodd; Janine Illian; Mark James; Peter J. Wright; Sophie Smout; James Thorburn (Marine Biology, 2021)
Trends in depth and vertical activity reflect the behaviour, habitat use and habitat preferences of marine organisms. However, among elasmobranchs, research has focused heavily on pelagic sharks, while the vertical movements of benthic elasmobranchs, such as skate (Rajidae), remain understudied. In this study, the vertical movements of the Critically Endangered flapper skate ( Dipturus intermedius ) were investigated using archival depth data collected at 2 min intervals from 21 individuals off the west coast of Scotland (56.5°N, −5.5°W) in 2016–17. Depth records comprised nearly four million observations and included eight time series longer than 1 year, forming one of the most comprehensive datasets collected on the movement of any skate to date. Additive modelling and functional data analysis were used to investigate vertical movements in relation to environmental cycles and individual characteristics. Vertical movements were dominated by individual variation but included prolonged periods of limited activity and more extensive movements that were associated with tidal, diel, lunar and seasonal cycles. Diel patterns were strongest, with irregular but frequent movements into shallower water at night, especially in autumn and winter. This research strengthens the evidence for vertical movements in relation to environmental cycles in benthic species and demonstrates a widely applicable flexible regression framework for movement research that recognises the importance of both individual-specific and group-level variation.

Corrigendum: Seasonal and Ontogenetic Variation in Depth Use by a Critically Endangered Benthic Elasmobranch and Its Implications for Spatial Management - James Thorburn; Peter J. Wright; Edward Lavender; Jane Dodd; Francis Neat; Julien G. A. Martin; Caroline Lynam; Mark James (Frontiers in Marine Science, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

Seasonal and Ontogenetic Variation in Depth Use by a Critically Endangered Benthic Elasmobranch and Its Implications for Spatial Management - James Thorburn; Peter J. Wright; Edward Lavender; Jane Dodd; Francis Neat; Julien G. A. Martin; Caroline Lynam; Mark James (Frontiers in Marine Science, 2021)
Seasonal and ontogenetic variations in depth use by benthic species are often concomitant with changes in their spatial distribution. This has implications for the efficacy of spatial conservation measures such as marine protected areas (MPAs). The critically endangered flapper skate ( Dipturus intermedius ) is the designation feature of an MPA in Scotland. This species is generally associated with deeper waters >100 m; however, little is known about its seasonal or ontogenetic variation in habitat use. This study used archival depth data from 25 immature and mature flapper skate tagged in the MPA over multiple years. Time series ranged from 3 to 772 (mean = 246) days. Generalised additive mixed models and highest density intervals were used to identify home (95%) and core (50%) highest density depth regions (HDDRs) to quantify depth use in relation to time of year and body size. Skate used a total depth range of 1–312 m, but home HDDRs typically occurred between 20 and 225 m. Core HDDRs displayed significant seasonal and ontogenetic variations. Summer core HDDRs (100–150 m) suggest high occupancy of the deep trenches in the region by skate of most size classes. There was an inverse relationship between body size and depth use and a seasonal trend of skate moving into shallow water over winter months. These results suggest that flapper skate are not solely associated with deep water, as skate, especially large females, are frequently found in shallow waters (25–75 m). The current management, which protects the entire depth range, is appropriate for the protection of flapper skate through much of its life history. This research demonstrates why collecting data across seasonal scales and multiple ontogenetic stages is needed to assess the effectiveness of spatial management.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Correction to: QTL analysis and fine mapping of a QTL for yield‑related traits in wheat grown in dry and hot environments - Habtamu Tura; James Edwards; Vijay Gahlaut; Melissa Garcia; Beata Sznajder; Ute Baumann; Fahimeh Shahinnia; Matthew Reynolds; Peter Langridge; Harindra Singh Balyan; Pushpendra K. Gupta; Thorsten Schnurbusch; et al. (Theoretical and Applied Genetics, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s00122-021-03792-4

Catchment-scale groundwater-flow and recharge paradox revealed from base flow analysis during the Australian Millennium Drought (Mt Lofty Ranges, South Australia) - Thomas T. Anderson; Erick A. Bestland; Ilka Wallis; Peter J. C. Kretschmer; Lesja Soloninka; Edward W. Banks; Adrian D. Werner; Dioni I. Cendón; Markus M. Pichler; Huade Guan (Hydrogeology Journal, 2021)

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Tracing the origins of recent Queensland fruit fly incursions into South Australia, Tasmania and New Zealand - Ángel-David Popa-Báez; Siu Fai Lee; Heng Lin Yeap; Guy Westmore; Peter Crisp; Dongmei Li; Renee Catullo; Emilie C. Cameron; Owain R. Edwards; Phillip W. Taylor; John G. Oakeshott (Biological Invasions, 2021)

Are bacterial symbionts associated with gall induction in insects? - Tobin J. Hammer; Rosemarie De Clerck-Floate; John F. Tooker; Peter W. Price; Donald G. Miller; Edward F. Connor (Arthropod-Plant Interactions, 2021)

Multi-stressor Effects of Ultraviolet Light, Temperature, and Salinity on Louisiana Sweet Crude Oil Toxicity in Larval Estuarine Organisms - Marie E. DeLorenzo; Peter B. Key; Katy W. Chung; Kaitlin Aaby; Deanna Hausman; Cheldina Jean; Paul L. Pennington; Emily C. Pisarski; Edward F. Wirth (Archives of Environmental Contamination and Toxicology, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Boundary-Layer Flow Over Complex Topography - John Finnigan; Keith Ayotte; Ian Harman; Gabriel Katul; Holly Oldroyd; Edward Patton; Davide Poggi; Andrew Ross; Peter Taylor (Boundary-Layer Meteorology, 2020)

Understanding Naloxone Uptake from an Emergency Department Distribution Program Using a Low-Energy Bluetooth Real-time Location System - Jeffrey T. Lai; Brittany P. Chapman; Stephanie P. Carreiro; Kavita M. Babu; Edward W. Boyer; Peter R. Chai (Journal of Medical Toxicology, 2020)

The Human Gene Mutation Database (HGMD®): optimizing its use in a clinical diagnostic or research setting - Peter D. Stenson; Matthew Mort; Edward V. Ball; Molly Chapman; Katy Evans; Luisa Azevedo; Matthew Hayden; Sally Heywood; David S. Millar; Andrew D. Phillips; David N. Cooper (Human Genetics, 2020)
The Human Gene Mutation Database (HGMD ® ) constitutes a comprehensive collection of published germline mutations in nuclear genes that are thought to underlie, or are closely associated with human inherited disease. At the time of writing (June 2020), the database contains in excess of 289,000 different gene lesions identified in over 11,100 genes manually curated from 72,987 articles published in over 3100 peer-reviewed journals. There are primarily two main groups of users who utilise HGMD on a regular basis; research scientists and clinical diagnosticians. This review aims to highlight how to make the most out of HGMD data in each setting.

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

Modeling the interactive effects of nutrient loads, meteorology, and invasive mussels on suitable habitat for Bighead and Silver Carp in Lake Michigan - Peter J. Alsip; Hongyan Zhang; Mark D. Rowe; Edward Rutherford; Doran M. Mason; Catherine Riseng; Zhenming Su (Biological Invasions, 2020)
Anthropogenic stressors that affect ecological processes in the Laurentian Great Lakes can impact their susceptibility to bioinvasions. Bighead Hypophthalmichthys nobilis and Silver Carp H. molitrix , collectively ‘bigheaded carps’ (BHC), are planktivorous fishes threatening to invade Lake Michigan. While previous studies indicate the lake contains habitat suitable for BHC growth, there is a need to understand how anthropogenic-driven changes to the abiotic and biotic environment could alter its vulnerability to BHC. We applied a spatially explicit model of BHC growth rate potential (GRP; g g −1 d −1 ) to nine biophysical model scenarios to evaluate changes in habitat suitability in Lake Michigan. Scenarios differed in meteorology (cool, reference, warm), annual tributary phosphorus loads (0, 3300, and 5600 MTA), and the presence/absence of invasive dreissenid mussels. Mussel effects on BHC GRP relied on their contact with the surface mixed layer (SML), the depth of which was affected by meteorology. The warm year advanced the expansion of Bighead Carp habitat by increasing temperature-dependent foraging rates and lessening the time of competitive interaction with mussels due to earlier stratification separating mussels from the SML. Phosphorus loads were the most influential driver of the lake’s suitability. Compared to present conditions, we estimate BHC could have grown an additional 8–40% annually in the 1980s when mussels were not in the lake and phosphorus loads were higher. Our study demonstrates how climate change and nutrient enrichment can increase Lake Michigan’s vulnerability to BHC by affecting thermal regime and productivity, thereby limiting negative effects of dreissenid mussels on BHC growth.

Phylogeny and diversification of the gallopheasants (Aves: Galliformes): Testing roles of sexual selection and environmental niche divergence - Peter A. Hosner; Hannah L. Owens; Edward L. Braun; Rebecca T. Kimball (Zoologica Scripta, 2020)
The gallopheasants comprise a clade of 22 species including some of the most elaborately plumaged and highly ornamented birds in the world. They also occupy a remarkable breath of environments and habitats, ranging from lowland rainforests to high grasslands and steppes of the Tibetan plateau. Here, we provide the first well‐resolved species phylogeny of this charismatic group, inferred from ultraconserved elements, nuclear introns and mitochondrial DNA sequences. Unlike previous studies which found unresolvable relationships and suggested a rapid initial burst of diversification, we identified a well‐resolved phylogeny supported in both concatenated and coalescent analytical frameworks, and a steady accrual of lineages through time. Morphological trait reconstructions demonstrated strong phylogenetic signal, not only for highly ornamented males, but also in more cryptically plumaged females. Environmental niche similarly exhibited strong phylogenetic signal. Moreover, evolution of male traits, female traits and environmental niche were all significantly correlated, making it difficult to disentangle their individual roles in gallopheasant diversification.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Individual variations of the human corticospinal tract and its hand-related motor fibers using diffusion MRI tractography - Kyriakos Dalamagkas; Magdalini Tsintou; Yogesh Rathi; Lauren J. O’Donnell; Ofer Pasternak; Xue Gong; Anne Zhu; Peter Savadjiev; George M. Papadimitriou; Marek Kubicki; Edward H. Yeterian; Nikos Makris (Brain Imaging and Behavior, 2020)

Factors determining variation in colour morph frequencies in invasive Harmonia axyridis populations - Alois Honek; Peter M. J. Brown; Zdenka Martinkova; Jiri Skuhrovec; Marek Brabec; Giovanni Burgio; Edward W. Evans; Marc Fournier; Audrey A. Grez; Jan Kulfan; Francesco Lami; Eric Lucas; et al. (Biological Invasions, 2020)

The importance of naturally attenuated SARS‐CoV ‐2 in the fight against COVID ‐19 - Jean Armengaud; Agnès Delaunay‐Moisan; Jean‐Yves Thuret; Eelco van Anken; Diego Acosta‐Alvear; Tomás Aragón; Carolina Arias; Marc Blondel; Ineke Braakman; Jean‐François Collet; René Courcol; Antoine Danchin; et al. (Environmental Microbiology, 2020)
The current SARS‐CoV‐2 pandemic is wreaking havoc throughout the world and has rapidly become a global health emergency. A central question concerning COVID‐19 is why some individuals become sick and others not. Many have pointed already at variation in risk factors between individuals. However, the variable outcome of SARS‐CoV‐2 infections may, at least in part, be due also to differences between the viral subspecies with which individuals are infected. A more pertinent question is how we are to overcome the current pandemic. A vaccine against SARS‐CoV‐2 would offer significant relief, although vaccine developers have warned that design, testing and production of vaccines may take a year if not longer. Vaccines are based on a handful of different designs (i), but the earliest vaccines were based on the live, attenuated virus. As has been the case for other viruses during earlier pandemics, SARS‐CoV‐2 will mutate and may naturally attenuate over time (ii). What makes the current pandemic unique is that, thanks to state‐of‐the‐art nucleic acid sequencing technologies, we can follow in detail how SARS‐CoV‐2 evolves while it spreads. We argue that knowledge of naturally emerging attenuated SARS‐CoV‐2 variants across the globe should be of key interest in our fight against the pandemic.

The Rapid Regenerative Response of a Model Sea Anemone Species Exaiptasia pallida Is Characterised by Tissue Plasticity and Highly Coordinated Cell Communication - Chloé A. van der Burg; Ana Pavasovic; Edward K. Gilding; Elise S. Pelzer; Joachim M. Surm; Hayden L. Smith; Terence P. Walsh; Peter J. Prentis (Marine Biotechnology, 2020)

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

Identification and QTL mapping of resistance to Turnip yellows virus (TuYV) in oilseed rape, Brassica napus - Dieter Hackenberg; Elvis Asare-Bediako; Adam Baker; Peter Walley; Carol Jenner; Shannon Greer; Lawrence Bramham; Jacqueline Batley; David Edwards; Regine Delourme; Guy Barker; Graham Teakle; et al. (Theoretical and Applied Genetics, 2020)
Key message Partially dominant resistance to Turnip yellows virus associated with one major QTL was identified in the natural allotetraploid oilseed rape cultivar Yudal. Abstract Turnip yellows virus (TuYV) is transmitted by the peach-potato aphid ( Myzus persicae ) and causes severe yield losses in commercial oilseed rape crops ( Brassica napus ). There is currently only one genetic resource for resistance to TuYV available in brassica, which was identified in the re-synthesised B. napus line ‘R54’. In our study, 27 mostly homozygous B. napus accessions, either doubled-haploid (DH) or inbred lines, representing a diverse subset of the B. napus genepool, were screened for TuYV resistance/susceptibility. Partial resistance to TuYV was identified in the Korean spring oilseed rape, B. napus variety Yudal, whilst the dwarf French winter oilseed rape line Darmor- bzh was susceptible. QTL mapping using the established Darmor- bzh × Yudal DH mapping population (DYDH) revealed one major QTL explaining 36% and 18% of the phenotypic variation in two independent experiments. A DYDH line was crossed to Yudal, and reciprocal backcross (BC 1 ) populations from the F 1 with either the susceptible or resistant parent revealed the dominant inheritance of the TuYV resistance. The QTL on ChrA04 was verified in the segregating BC 1 population. A second minor QTL on ChrC05 was identified in one of the two DYDH experiments, and it was not observed in the BC 1 population. The TuYV resistance QTL in ‘R54’ is within the QTL interval on Chr A04 of Yudal; however, the markers co-segregating with the ‘R54’ resistance are not conserved in Yudal, suggesting an independent origin of the TuYV resistances. This is the first report of the QTL mapping of TuYV resistance in natural B. napus .

Characteristics of free air carbon dioxide enrichment of a northern temperate mature forest - Kris M. Hart; Giulio Curioni; Phillip Blaen; Nicholas J. Harper; Peter Miles; Keith F. Lewin; John Nagy; Edward J. Bannister; Xiaoming M. Cai; Rick M. Thomas; Stefan Krause; Michael Tausz; et al. (Global Change Biology, 2020)
In 2017, the Birmingham Institute of Forest Research (BIFoR) began to conduct Free Air Carbon Dioxide Enrichment (FACE) within a mature broadleaf deciduous forest situated in the United Kingdom. BIFoR FACE employs large‐scale infrastructure, in the form of lattice towers, forming ‘arrays’ which encircle a forest plot of ~30 m diameter. BIFoR FACE consists of three treatment arrays to elevate local CO 2 concentrations (e[CO 2 ]) by +150 µmol/mol. In practice, acceptable operational enrichment (ambient [CO 2 ] + e[CO 2 ]) is ±20% of the set point 1‐min average target. There are a further three arrays that replicate the infrastructure and deliver ambient air as paired controls for the treatment arrays. For the first growing season with e[CO 2 ] (April to November 2017), [CO 2 ] measurements in treatment and control arrays show that the target concentration was successfully delivered, that is: +147 ± 21 µmol/mol (mean ± SD ) or 98 ± 14% of set point enrichment target. e[CO 2 ] treatment was accomplished for 97.7% of the scheduled operation time, with the remaining time lost due to engineering faults (0.6% of the time), CO 2 supply issues (0.6%) or adverse weather conditions (1.1%). CO 2 demand in the facility was driven predominantly by wind speed and the formation of the deciduous canopy. Deviations greater than 10% from the ambient baseline CO 2 occurred 80 µmol/mol (i.e. >53% of the treatment increment) into control arrays accounted for 2 ] values in reconstructed three‐dimensional [CO 2 ] fields show enrichment somewhat lower than the target but still well above ambient. The data presented here provide confidence in the facility setup and can be used to guide future next‐generation forest FACE facilities built into tall and complex forest stands.

QTL analysis and fine mapping of a QTL for yield-related traits in wheat grown in dry and hot environments - Habtamu Tura; James Edwards; Vijay Gahlaut; Melissa Garcia; Beata Sznajder; Ute Baumann; Fahimeh Shahinnia; Matthew Reynolds; Peter Langridge; Harindra Singh Balyan; Pushpendra K. Gupta; Thorsten Schnurbusch; et al. (Theoretical and Applied Genetics, 2020)
Genetic control of grain yield and phenology was examined in the Excalibur/Kukri doubled haploid mapping population grown in 32 field experiments across the climatic zones of southern Australia, India and north-western Mexico where the wheat crop experiences drought and heat stress. A total of 128 QTL were identified for four traits: grain yield, thousand grain weight (TGW), days to heading and grain filling duration. These QTL included 24 QTL for yield and 27 for TGW, showing significant interactions with the environment ( Q * E ). We also identified 14 QTL with a significant, small main effects on yield across environments. The study focussed on a region of chromosome 1B where two main effect QTL were found for yield and TGW without the confounding effect of phenology. Excalibur was the source of favourable alleles: QYld.aww - 1B.2 with a peak at 149.5–150.1 cM and QTgw.aww - 1B at 168.5–171.4 cM. We developed near isogenic lines (NIL) for the interval including QYld.aww - 1B.2 and QTgw.aww - 1B and evaluated them under semi-controlled conditions. Significant differences in four pairs of NIL were observed for grain yield but not for TGW, confirming a positive effect of the Excalibur allele for QYld.aww - 1B.2 . The interval containing QYld.aww - 1B.2 was narrowed down to 2.9 cM which corresponded to a 2.2 Mbp genomic region on the chromosome 1B genomic reference sequence of cv. Chinese Spring and contained 39 predicted genes.

Respiratory and non-respiratory symptoms associated with pesticide management practices among farmers in Ghana’s most important vegetable hub - Reginald Quansah; John R. Bend; Frederick Ato Armah; Felix Bonney; Joshua Aseidu; David Oscar Yawson; Michael Osei Adu; Isaac Luginaah; David Kofi Essumang; Abukari Abdul-Rahaman; Samuel Cobbina; Samuel Iddi; et al. (Environmental Monitoring and Assessment, 2019)

Ground-motion networks in the Groningen field: usability and consistency of surface recordings - Michail Ntinalexis; Julian J. Bommer; Elmer Ruigrok; Benjamin Edwards; Rui Pinho; Bernard Dost; António A. Correia; Jeroen Uilenreef; Peter J. Stafford; Jan van Elk (Journal of Seismology, 2019)
Several strong-motion networks have been installed in the Groningen gas field in the Netherlands to record ground motions associated with induced earthquakes. There are now more than 450 permanent surface accelerographs plus a mobile array of 450 instruments, which, in addition to many instrumented boreholes, yield a wealth of data. The database of recordings has been of fundamental importance to the development of ground-motion models that form a key element of the seismic hazard and risk estimations for the field. In order to maximise the benefit that can be derived from these recordings, this study evaluates the usability of the recordings from the different networks, in general terms and specifically with regards to the frequency ranges with acceptable signal-to-noise ratios. The study also explores the consistency among the recordings from the different networks, highlighting in particular how a configuration error was identified and resolved. The largest accelerograph network consists of instruments housed in buildings around the field, frequently installed on the lower parts of walls rather than on the floor. A series of experiments were conducted, using additional instruments installed adjacent to these buildings and replicating the installation configuration in full-scale shake table tests, to identify the degree to which structural response contaminated the recordings. The general finding of these efforts was that for PGV and oscillator periods above 0.1 s, the response spectral ordinates from these recordings can be used with confidence.

Large-Eddy Simulations of the Steady Wintertime Antarctic Boundary Layer - Steven J. A. van der Linden; John M. Edwards; Chiel C. van Heerwaarden; Etienne Vignon; Christophe Genthon; Igor Petenko; Peter Baas; Harmen J. J. Jonker; Bas J. H. van de Wiel (Boundary-Layer Meteorology, 2019)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Observational Needs of Sea Surface Temperature - Anne G. O’Carroll; Edward M. Armstrong; Helen M. Beggs; Marouan Bouali; Kenneth S. Casey; Gary K. Corlett; Prasanjit Dash; Craig J. Donlon; Chelle L. Gentemann; Jacob L. Høyer; Alexander Ignatov; Kamila Kabobah; et al. (Frontiers in Marine Science, 2019)

Advancing Research for the Management of Long-Lived Species: A Case Study on the Greenland Shark - Jena E. Edwards; Elizabeth Hiltz; Franziska Broell; Peter G. Bushnell; Steven E. Campana; Jørgen S. Christiansen; Brynn M. Devine; Jeffrey J. Gallant; Kevin J. Hedges; M. Aaron MacNeil; Bailey C. McMeans; Julius Nielsen; et al. (Frontiers in Marine Science, 2019)

The effects of training population design on genomic prediction accuracy in wheat - Stefan McKinnon Edwards; Jaap B. Buntjer; Robert Jackson; Alison R. Bentley; Jacob Lage; Ed Byrne; Chris Burt; Peter Jack; Simon Berry; Edward Flatman; Bruno Poupard; Stephen Smith; et al. (Theoretical and Applied Genetics, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

A differential k-mer analysis pipeline for comparing RNA-Seq transcriptome and meta-transcriptome datasets without a reference - Chon-Kit Kenneth Chan; Nedeljka Rosic; Michał T. Lorenc; Paul Visendi; Meng Lin; Paulina Kaniewska; Brett J. Ferguson; Peter M. Gresshoff; Jacqueline Batley; David Edwards (Functional & Integrative Genomics, 2019)

Multi-level emulation of complex climate model responses to boundary forcing data - Giang T. Tran; Kevin I. C. Oliver; Philip B. Holden; Neil R. Edwards; András Sóbester; Peter Challenor (Climate Dynamics, 2019)

A Computational Cardiac Model for the Adaptation to Pulmonary Arterial Hypertension in the Rat - Reza Avazmohammadi; Emilio A. Mendiola; João S. Soares; David S. Li; Zhiqiang Chen; Samer Merchant; Edward W. Hsu; Peter Vanderslice; Richard A. F. Dixon; Michael S. Sacks (Annals of Biomedical Engineering, 2019)

Pharmacologic Treatment of Opioid Use Disorder: a Review of Pharmacotherapy, Adjuncts, and Toxicity - Michael S. Toce; Peter R. Chai; Michele M. Burns; Edward W. Boyer (Journal of Medical Toxicology, 2018)

Benign gynecologic conditions are associated with ovarian cancer risk in African-American women: a case–control study - Hyo K. Park; Joellen M. Schildkraut; Anthony J. Alberg; Elisa V. Bandera; Jill S. Barnholtz-Sloan; Melissa Bondy; Sydnee Crankshaw; Ellen Funkhouser; Patricia G. Moorman; Edward S. Peters; Paul Terry; Frances Wang; et al. (Cancer Causes & Control, 2018)

Machine Learning to Predict, Detect, and Intervene Older Adults Vulnerable for Adverse Drug Events in the Emergency Department - Kei Ouchi; Charlotta Lindvall; Peter R. Chai; Edward W. Boyer (Journal of Medical Toxicology, 2018)

Temporal variation in abundance of leaf litter beetles and ants in an Australian lowland tropical rainforest is driven by climate and litter fall - Peter S. Grimbacher; Will Edwards; Michael J. Liddell; Paul N. Nelson; Cassandra Nichols; Carl W. Wardhaugh; Nigel E. Stork (Biodiversity and Conservation, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Arundic Acid Increases Expression and Function of Astrocytic Glutamate Transporter EAAT1 Via the ERK, Akt, and NF-κB Pathways - Pratap Karki; Peter Hong; James Johnson; Edward Pajarillo; Deok-Soo Son; Michael Aschner; Eunsook Y. Lee (Molecular Neurobiology, 2018)

Management regime is the most important factor influencing ectomycorrhizal species community in Norway spruce forests after windthrow - Martina Vašutová; Magda Edwards-Jonášová; Petra Veselá; Lenka Effenberková; Peter Fleischer; Pavel Cudlín (Mycorrhiza, 2018)

Glucosamine use and risk of colorectal cancer: results from the Cancer Prevention Study II Nutrition Cohort - Elizabeth D. Kantor; Christina C. Newton; Edward L. Giovannucci; Marjorie L. McCullough; Peter T. Campbell; Eric J. Jacobs (Cancer Causes & Control, 2018)

Avoided economic impacts of climate change on agriculture: integrating a land surface model (CLM) with a global economic model (iPETS) - Xiaolin Ren; Matthias Weitzel; Brian C. O’Neill; Peter Lawrence; Prasanth Meiyappan; Samuel Levis; Edward J. Balistreri; Michael Dalton (Climatic Change, 2018)

Recreational physical activity and survival in African-American women with ovarian cancer - Sarah E. Abbott; Fabian Camacho; Lauren C. Peres; Anthony J. Alberg; Elisa V. Bandera; Melissa Bondy; Michele L. Cote; Ellen Funkhouser; Patricia G. Moorman; Edward S. Peters; Bo Qin; Ann G. Schwartz; et al. (Cancer Causes & Control, 2018)

The Differential Absorption of a Series of P-Glycoprotein Substrates in Isolated Perfused Lungs from Mdr1a/1b Genetic Knockout Mice can be Attributed to Distinct Physico-Chemical Properties: an Insight into Predicting Transporter-Mediated, Pulmonary Specific Disposition - Daniel F. Price; Chris N. Luscombe; Peter J. Eddershaw; Chris D. Edwards; Mark Gumbleton (Pharmaceutical Research, 2017)

A Novel Oral Fluid Assay (LC-QTOF-MS) for the Detection of Fentanyl and Clandestine Opioids in Oral Fluid After Reported Heroin Overdose - Matthew K. Griswold; Peter R. Chai; Alex J. Krotulski; Melissa Friscia; Brittany P. Chapman; Neha Varma; Edward W. Boyer; Barry K. Logan; Kavita M. Babu (Journal of Medical Toxicology, 2017)

Creating the Art of Deep-Sea Experimental Chemistry with MBARI ROVs - Peter Brewer; Edward Peltzer; Peter Walz; William Kirkwood (Oceanography, 2017)

Tubal ligation and ovarian cancer risk in African American women - Chrissy McNamara; Sarah E. Abbott; Elisa V. Bandera; Bo Qin; Lauren C. Peres; Fabian Camacho; Patricia G. Moorman; Anthony J. Alberg; Jill S. Barnholtz-Sloan; Melissa Bondy; Michele L. Cote; Ellen Funkhouser; et al. (Cancer Causes & Control, 2017)

Music as an Adjunct to Opioid-Based Analgesia - Peter R. Chai; Stephanie Carreiro; Megan L. Ranney; Ketki Karanam; Marko Ahtisaari; Robert Edwards; Kristin L. Schreiber; Lubabah Ben-Ghaly; Timothy B. Erickson; Edward W. Boyer (Journal of Medical Toxicology, 2017)

Cattle utilization of coniferous cut blocks under open range grazing and associated impact on tree seedlings - Jillian Kaufmann; Edward W. Bork; Mike J. Alexander; Peter V. Blenis (Agroforestry Systems, 2017)

Cigarette smoking and the association with serous ovarian cancer in African American women: African American Cancer Epidemiology Study (AACES) - Linda E. Kelemen; Sarah Abbott; Bo Qin; Lauren Cole Peres; Patricia G. Moorman; Kristin Wallace; Elisa V. Bandera; Jill S. Barnholtz-Sloan; Melissa Bondy; Kathleen Cartmell; Michele L. Cote; Ellen Funkhouser; et al. (Cancer Causes & Control, 2017)

Integrating Personalized Technology in Toxicology: Sensors, Smart Glass, and Social Media Applications in Toxicology Research - Stephanie Carreiro; Peter R Chai; Jennifer Carey; Brittany Chapman; Edward W Boyer (Journal of Medical Toxicology, 2017)

The Human Gene Mutation Database: towards a comprehensive repository of inherited mutation data for medical research, genetic diagnosis and next-generation sequencing studies - Peter D. Stenson; Matthew Mort; Edward V. Ball; Katy Evans; Matthew Hayden; Sally Heywood; Michelle Hussain; Andrew D. Phillips; David N. Cooper (Human Genetics, 2017)

Markers of physiological stress during exercise under conditions of normoxia, normobaric hypoxia, hypobaric hypoxia, and genuine high altitude - David Richard Woods; John Paul O’Hara; Christopher John Boos; Peter David Hodkinson; Costas Tsakirides; Neil Edward Hill; Darren Jose; Amanda Hawkins; Kelly Phillipson; Antonia Hazlerigg; Nicola Arjomandkhah; Liam Gallagher; et al. (European Journal of Applied Physiology, 2017)

History of hypertension, heart disease, and diabetes and ovarian cancer patient survival: evidence from the ovarian cancer association consortium - Albina N. Minlikeeva; Jo L. Freudenheim; Rikki A. Cannioto; J. Brian Szender; Kevin H. Eng; Francesmary Modugno; Roberta B. Ness; Michael J. LaMonte; Grace Friel; Brahm H. Segal; Kunle Odunsi; Paul Mayor; et al. (Cancer Causes & Control, 2017)

Lifetime number of ovulatory cycles and epithelial ovarian cancer risk in African American women - Lauren C. Peres; Patricia G. Moorman; Anthony J. Alberg; Elisa V. Bandera; Jill Barnholtz-Sloan; Melissa Bondy; Michele L. Cote; Ellen Funkhouser; Edward S. Peters; Ann G. Schwartz; Paul D. Terry; Sarah E. Abbott; et al. (Cancer Causes & Control, 2017)

Rotor Tracking Using Phase of Electrograms Recorded During Atrial Fibrillation - Caroline H. Roney; Chris D. Cantwell; Norman A. Qureshi; Rasheda A. Chowdhury; Emmanuel Dupont; Phang Boon Lim; Edward J. Vigmond; Jennifer H. Tweedy; Fu Siong Ng; Nicholas S. Peters (Annals of Biomedical Engineering, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Development of a Novel Quantitative Structure-Activity Relationship Model to Accurately Predict Pulmonary Absorption and Replace Routine Use of the Isolated Perfused Respiring Rat Lung Model - Chris D. Edwards; Chris Luscombe; Peter Eddershaw; Edith M. Hessel (Pharmaceutical Research, 2016)

The emergence of molecular profiling and omics techniques in seagrass biology; furthering our understanding of seagrasses - Peter A. Davey; Mathieu Pernice; Gaurav Sablok; Anthony Larkum; Huey Tyng Lee; Agnieszka Golicz; David Edwards; Rudy Dolferus; Peter Ralph (Functional & Integrative Genomics, 2016)

Fine-scale spatial variation in ice cover and surface temperature trends across the surface of the Laurentian Great Lakes - Lacey A. Mason; Catherine M. Riseng; Andrew D. Gronewold; Edward S. Rutherford; Jia Wang; Anne Clites; Sigrid D. P. Smith; Peter B. McIntyre (Climatic Change, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

A Framework to Assess Biogeochemical Response to Ecosystem Disturbance Using Nutrient Partitioning Ratios - J. Marty Kranabetter; Kendra K. McLauchlan; Sara K. Enders; Jennifer M. Fraterrigo; Philip E. Higuera; Jesse L. Morris; Edward B. Rastetter; Rebecca Barnes; Brian Buma; Daniel G. Gavin; Laci M. Gerhart; Lindsey Gillson; et al. (Ecosystems, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Native and alien herbaceous plants in the Brazilian Cerrado are (co-)limited by different nutrients - Luciola S. Lannes; Mercedes M. C. Bustamante; Peter J. Edwards; Harry Olde Venterink (Plant and Soil, 2016)

Soil respiration under three different land use types in a tropical mountain region of China - Jun-jie Wu; Stefanie Daniela Goldberg; Peter Edward Mortimer; Jian-chu Xu (Journal of Mountain Science, 2016)

Evaluation of cystatin C as an early biomarker of cadmium nephrotoxicity in the rat - Walter C. Prozialeck; Aaron VanDreel; Christopher D. Ackerman; Ian Stock; Alexander Papaeliou; Christian Yasmine; Kristen Wilson; Peter C. Lamar; Victoria L. Sears; Joshua Z. Gasiorowski; Karyn M. DiNovo; Vishal S. Vaidya; et al. (BioMetals, 2016)

Contrasting the roles of the I-II loop gating brake in CaV3.1 and CaV3.3 calcium channels - Mária Karmažínová; Katarína Jašková; Peter Griac; Edward Perez-Reyes; Ľubica Lacinová (Pflügers Archiv - European Journal of Physiology, 2015)

Utilizing an Ingestible Biosensor to Assess Real-Time Medication Adherence - Peter R. Chai; Jose Castillo-Mancilla; Eric Buffkin; Chad Darling; Rochelle K. Rosen; Keith J. Horvath; Edwin D. Boudreaux; Gregory K. Robbins; Patricia L. Hibberd; Edward W. Boyer (Journal of Medical Toxicology, 2015)

Digital innovation through partnership between nature conservation organisations and academia: A qualitative impact assessment - Carlos Galán-Díaz; Peter Edwards; John D. Nelson; René van der Wal (Ambio, 2015)

Cosmogenic dating of Late Pleistocene glaciation, southern tropical Andes, Peru - Jeremy D. Shakun; Peter U. Clark; Shaun A. Marcott; Edward J. Brook; Nathaniel A. Lifton; Marc Caffee; William R. Shakun (Journal of Quaternary Science, 2015)
We present 30 10 Be dates on three moraines formed by small glaciers in the southern tropical Andes of Peru to determine the timing of the local Last Glacial Maximum (LGM) and subsequent deglaciation. Two terminal moraines indicate that the local LGM ended at 23.5 ± 0.5 and 21.2 ± 0.8 ka, or well before the end of the global LGM (20–19 ka). A recessional moraine perched at the base of a steep valley wall has a 10 Be age of 19.8 ± 0.3 ka, suggesting that glaciers had largely retreated from the area during the earliest stages of the last termination and before the onset of the deglacial CO 2 rise and increase in tropical sea surface temperatures. These ages generally agree with other tropical glacial chronologies and reflect a broad synchroneity between low‐ and high‐latitude deglaciation at the LGM, but the trigger for early deglaciation of the tropics remains unclear.

Edge-Centered DTI Connectivity Analysis: Application to Schizophrenia - Edward H. Herskovits; L. Elliot Hong; Peter Kochunov; Hemalatha Sampath; Rong Chen (Neuroinformatics, 2015)

Widespread Chemical Detoxification of Alkaloid Venom by Formicine Ants - Edward G. LeBrun; Peter J. Diebold; Matthew R. Orr; Lawrence E. Gilbert (Journal of Chemical Ecology, 2015)

Seascape drivers of M acrocystis pyrifera population genetic structure in the northeast P acific - Mattias L. Johansson; Filipe Alberto; Daniel C. Reed; Peter T. Raimondi; Nelson C. Coelho; Mary A. Young; Patrick T. Drake; Christopher A. Edwards; Kyle Cavanaugh; Jorge Assis; Lydia B. Ladah; Tom W. Bell; et al. (Molecular Ecology, 2015)
At small spatial and temporal scales, genetic differentiation is largely controlled by constraints on gene flow, while genetic diversity across a species' distribution is shaped on longer temporal and spatial scales. We assess the hypothesis that oceanographic transport and other seascape features explain different scales of genetic structure of giant kelp, M acrocystis pyrifera . We followed a hierarchical approach to perform a microsatellite‐based analysis of genetic differentiation in M acrocystis across its distribution in the northeast P acific. We used seascape genetic approaches to identify large‐scale biogeographic population clusters and investigate whether they could be explained by oceanographic transport and other environmental drivers. We then modelled population genetic differentiation within clusters as a function of oceanographic transport and other environmental factors. Five geographic clusters were identified: A laska/ C anada, central C alifornia, continental S anta B arbara, C alifornia C hannel I slands and mainland southern C alifornia/ B aja C alifornia peninsula. The strongest break occurred between central and southern C alifornia, with mainland S anta B arbara sites forming a transition zone between the two. Breaks between clusters corresponded approximately to previously identified biogeographic breaks, but were not solely explained by oceanographic transport. An isolation‐by‐environment ( IBE ) pattern was observed where the northern and southern C hannel I slands clustered together, but not with closer mainland sites, despite the greater distance between them. The strongest environmental association with this IBE pattern was observed with light extinction coefficient, which extends suitable habitat to deeper areas. Within clusters, we found support for previous results showing that oceanographic connectivity plays an important role in the population genetic structure of M acrocystis in the Northern hemisphere.

Land connectivity changes and global cooling shaped the colonization history and diversification of New World quail (Aves: Galliformes: Odontophoridae) - Peter A. Hosner; Edward L. Braun; Rebecca T. Kimball (Journal of Biogeography, 2015)
Aim Range disjunctions are frequent in birds, but the relative roles of vicariance and long‐distance dispersal in producing them are debated. Odontophorid quail are widespread in tropical and temperate habitats in the Americas, yet recent phylogenetic studies support the view that they are sister to sub‐Saharan African Ptilopachus rather than the widespread Phasianidae as formerly believed. To understand how this 10,000 km range disjunction arose in relatively non‐vagile birds, we reconstructed colonization history and diversification of odontophorids with respect to hypothesized dry‐land connections between continents (North Atlantic, Beringian, Panamanian) that would have facilitated faunal exchange. Location Africa, Nearctic and Neotropics. Methods We inferred a fossil‐calibrated odontophorid phylogeny from DNA sequences (three mitochondrial genes and eight nuclear introns) and modelled ancestral ranges with six probabilistic biogeographical models. We used the Akaike information criterion ( AIC ) to select the best‐fit biogeographical model. Results Ptilopachus and New World quail shared an Old World ancestor c . 32 Ma. During this period, Beringia connected the Nearctic and Palaearctic, and global temperatures were high, such that presence of temperate organisms at high latitudes and direct dispersal across land connections were feasible. The extant New World quail began diversifying in Central America c . 18 Ma; timing estimates and ancestral range reconstructions support the hypothesis that New World quail colonized and diversified in South America following closure of the Isthmus of Panama. Main conclusions The Africa/New World range disjunction between New World quail and Ptilopachus is the result of changes in Earth and climate history, combined with range expansion and diversification in the New World, and range contraction in the Old World. We find no evidence for overwater dispersal in New World quail.

The Feasibility and Acceptability of Google Glass for Teletoxicology Consults - Peter R. Chai; Kavita M. Babu; Edward W. Boyer (Journal of Medical Toxicology, 2015)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

Human cytomegalovirus: taking the strain - Gavin W. G. Wilkinson; Andrew J. Davison; Peter Tomasec; Ceri A. Fielding; Rebecca Aicheler; Isa Murrell; Sepher Seirafian; Edward C. Y. Wang; Michael Weekes; Paul J. Lehner; Gavin S. Wilkie; Richard J. Stanton (Medical Microbiology and Immunology, 2015)

Impacts on the metabolome of down-regulating polyphenol oxidase in potato tubers - Louise Vida Traill Shepherd; Colin James Alexander; Christine Anne Hackett; Diane McRae; Julia Anne Sungurtas; Susan Ramsay Verrall; Jennifer Anne Morris; Peter Edward Hedley; David Rockhold; William Belknap; Howard Vivian Davies (Transgenic Research, 2015)

Females Exceed Males in Mercury Concentrations of Burbot Lota lota - Charles P. Madenjian; Martin A. Stapanian; Peter A. Cott; David P. Krabbenhoft; William H. Edwards; Lynn M. Ogilvie; Justin G. Mychek-Londer; John F. DeWild (Archives of Environmental Contamination and Toxicology, 2015)

Engineered VEGF-releasing PEG–MAL hydrogel for pancreatic islet vascularization - Edward A. Phelps; Kellie L. Templeman; Peter M. Thulé; Andrés J. García (Drug Delivery and Translational Research, 2015)

Performance of the herb Verbascum thapsus along environmental gradients in its native and non‐native ranges - Tim Seipel; Jake M. Alexander; Curtis C. Daehler; Lisa J. Rew; Peter J. Edwards; Pervaiz A. Dar; Keith McDougall; Bridgett Naylor; Catherine Parks; Fredric W. Pollnac; Zafar A. Reshi; Mel Schroder; et al. (Journal of Biogeography, 2015)
Aim We evaluated whether the performance of individuals and populations of the invasive plant Verbascum thapsus differs between its native and non‐native ranges, across climate gradients, and in response to its position in a global‐scaled niche model. Location India (Kashmir) and Switzerland (native range) and Australia and USA (Hawaii, Montana and Oregon) (non‐native range). Methods We measured population characteristics (density of flowering individuals, population size), plant traits (plant height, number of flowering branches) and seed germination for 50 populations of V. thapsus growing along elevational gradients in six mountain regions around the world (two in the native range, and four in the non‐native range). We fitted linear regression models to determine the relationship of plant and population level performance variables to range, region, climate and probability of occurrence from a global niche model. Results Plant height, number of flowering branches and population density of V. thapsus did not differ consistently between the native and non‐native ranges, but the area covered by populations in the non‐native range was on average two orders of magnitude larger than the area of native populations. Within and among regions, individual plant performance traits responded variably to precipitation and mean annual temperature, depending on the climatic range of the observed populations; however, performance was greater for populations that had a greater modelled probability of occurrence. Seed germination under controlled conditions was highest between 20 and 35 °C and consistent across populations, although germination at low temperatures was substantially higher for native populations from Kashmir. Main conclusions The introduction of V. thapsus to its non‐native range is not associated with consistent increases in plant performance. Instead, plant performance is more strongly influenced by position within the climate niche of the species, position along environmental gradients, and climatic or other differences among regions. We demonstrate that individual‐level and population‐level performance traits can yield different predictors of plant performance. Therefore, future studies comparing plant performance in native and non‐native ranges should include both plant and population characteristics and should also sample the target species from multiple regions in both ranges and along environmental gradients that comprehensively represent the niche of the species.

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

The Virtual Toxicology Service: Wearable Head-Mounted Devices for Medical Toxicology - Peter R. Chai; Roger Y. Wu; Megan L. Ranney; Paul S. Porter; Kavita M. Babu; Edward W. Boyer (Journal of Medical Toxicology, 2014)

Conserving the World's Finest Grassland Amidst Ambitious National Development - NYAMSUREN BATSAIKHAN; BAYARBAATAR BUUVEIBAATAR; BAZAAR CHIMED; OIDOV ENKHTUYA; DAVAA GALBRAKH; OYUNSAIKHAN GANBAATAR; BADAMJAV LKHAGVASUREN; DEJID NANDINTSETSEG; JOEL BERGER; JUSTIN M. CALABRESE; ANN E. EDWARDS; WILLIAM F. FAGAN; et al. (Conservation Biology, 2014)

Mapping the shadow of experience of extreme weather events - Peter D. Howe; Hilary Boudet; Anthony Leiserowitz; Edward W. Maibach (Climatic Change, 2014)

Towards a phylogenetic classification of reef corals: the I ndo‐ P acific genera M erulina , G oniastrea and S capophyllia ( S cleractinia, M erulinidae) - Danwei Huang; Francesca Benzoni; Roberto Arrigoni; Andrew H. Baird; Michael L. Berumen; Jessica Bouwmeester; Loke Ming Chou; Hironobu Fukami; Wilfredo Y. Licuanan; Edward R. Lovell; Rudolf Meier; Peter A. Todd; et al. (Zoologica Scripta, 2014)
Recent advances in scleractinian systematics and taxonomy have been achieved through the integration of molecular and morphological data, as well as rigorous analysis using phylogenetic methods. In this study, we continue in our pursuit of a phylogenetic classification by examining the evolutionary relationships between the closely related reef coral genera M erulina , G oniastrea , P araclavarina and S capophyllia (Merulinidae). In particular, we address the extreme polyphyly of F avites and G oniastrea that was discovered a decade ago. We sampled 145 specimens belonging to 16 species from a wide geographic range in the I ndo‐ P acific, focusing especially on type localities, including the Red Sea, western Indian Ocean and central Pacific. Tree reconstructions based on both nuclear and mitochondrial markers reveal a novel lineage composed of three species previously placed in F avites and G oniastrea . Morphological analyses indicate that this clade, P aragoniastrea H uang, B enzoni & B udd, gen. n., has a unique combination of corallite and subcorallite features observable with scanning electron microscopy and thin sections. Molecular and morphological evidence furthermore indicates that the monotypic genus Paraclavarina is nested within Merulina , and the former is therefore synonymised.

The Third GABLS Intercomparison Case for Evaluation Studies of Boundary-Layer Models. Part B: Results and Process Understanding - Fred C. Bosveld; Peter Baas; Gert-Jan Steeneveld; Albert A. M. Holtslag; Wayne M. Angevine; Eric Bazile; Evert I. F. de Bruijn; Daniel Deacu; John M. Edwards; Michael Ek; Vincent E. Larson; Jonathan E. Pleim; et al. (Boundary-Layer Meteorology, 2014)

Chronic water stress reduces tree growth and the carbon sink of deciduous hardwood forests - Edward R. Brzostek; Danilo Dragoni; Hans Peter Schmid; Abdullah F. Rahman; Daniel Sims; Craig A. Wayson; Daniel J. Johnson; Richard P. Phillips (Global Change Biology, 2014)
Predicted decreases in water availability across the temperate forest biome have the potential to offset gains in carbon (C) uptake from phenology trends, rising atmospheric CO 2 , and nitrogen deposition. While it is well established that severe droughts reduce the C sink of forests by inducing tree mortality, the impacts of mild but chronic water stress on forest phenology and physiology are largely unknown. We quantified the C consequences of chronic water stress using a 13‐year record of tree growth ( n = 200 trees), soil moisture, and ecosystem C balance at the Morgan–Monroe State Forest ( MMSF ) in Indiana, and a regional 11‐year record of tree growth ( n > 300 000 trees) and water availability for the 20 most dominant deciduous broadleaf tree species across the eastern and midwestern USA . We show that despite ~26 more days of C assimilation by trees at the MMSF , increasing water stress decreased the number of days of wood production by ~42 days over the same period, reducing the annual accrual of C in woody biomass by 41%. Across the deciduous forest region, water stress induced similar declines in tree growth, particularly for water‐demanding ‘mesophytic’ tree species. Given the current replacement of water‐stress adapted ‘xerophytic’ tree species by mesophytic tree species, we estimate that chronic water stress has the potential to decrease the C sink of deciduous forests by up to 17% (0.04 Pg C yr −1 ) in the coming decades. This reduction in the C sink due to mesophication and chronic water stress is equivalent to an additional 1–3 days of global C emissions from fossil fuel burning each year. Collectively, our results indicate that regional declines in water availability may offset the growth‐enhancing effects of other global changes and reduce the extent to which forests ameliorate climate warming.

Genetic control of grain yield and grain physical characteristics in a bread wheat population grown under a range of environmental conditions - Lancelot Maphosa; Peter Langridge; Helen Taylor; Boris Parent; Livinus C. Emebiri; Haydn Kuchel; Matthew P. Reynolds; Ken J. Chalmers; Anzu Okada; James Edwards; Diane E. Mather (Theoretical and Applied Genetics, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Population-based surveillance for cervical cancer precursors in three central cancer registries, United States 2009 - Elaine W. Flagg; S. Deblina Datta; Mona Saraiya; Elizabeth R. Unger; Edward Peters; Lauren Cole; Vivien W. Chen; Thomas Tucker; Mary Jane Byrne; Glenn Copeland; Won Silva; Meg Watson; et al. (Cancer Causes & Control, 2014)

Spring-summer temperatures since AD 1780 reconstructed from stable oxygen isotope ratios in white spruce tree-rings from the Mackenzie Delta, northwestern Canada - Trevor J. Porter; Michael F. J. Pisaric; Robert D. Field; Steven V. Kokelj; Thomas W. D. Edwards; Peter deMontigny; Richard Healy; Allegra N. LeGrande (Climate Dynamics, 2014)

The Human Gene Mutation Database: building a comprehensive mutation repository for clinical and molecular genetics, diagnostic testing and personalized genomic medicine - Peter D. Stenson; Matthew Mort; Edward V. Ball; Katy Shaw; Andrew D. Phillips; David N. Cooper (Human Genetics, 2014)
The Human Gene Mutation Database (HGMD ® ) is a comprehensive collection of germline mutations in nuclear genes that underlie, or are associated with, human inherited disease. By June 2013, the database contained over 141,000 different lesions detected in over 5,700 different genes, with new mutation entries currently accumulating at a rate exceeding 10,000 per annum. HGMD was originally established in 1996 for the scientific study of mutational mechanisms in human genes. However, it has since acquired a much broader utility as a central unified disease-oriented mutation repository utilized by human molecular geneticists, genome scientists, molecular biologists, clinicians and genetic counsellors as well as by those specializing in biopharmaceuticals, bioinformatics and personalized genomics. The public version of HGMD ( https://www.hgmd.cf.ac.uk ) is freely available to registered users from academic institutions/non-profit organizations whilst the subscription version (HGMD Professional) is available to academic, clinical and commercial users under license via BIOBASE GmbH.

How comparable are species distributions along elevational and latitudinal climate gradients? - Aud H. Halbritter; Jake M. Alexander; Peter J. Edwards; Regula Billeter (Global Ecology and Biogeography, 2013)
Aim Because climatic factors, especially temperature, show similar trends with elevation and latitude, it is often assumed that elevational gradients can be used as a proxy for understanding ecological processes along latitudinal gradients. We investigated the validity of this assumption for herbaceous plants, testing the hypotheses that (1) species reach the same climate limits, and (2) exhibit similar distribution patterns along both types of gradient. Location S wiss A lps and S candinavia. Methods We recorded the occurrence of 155 ruderal plant species along an elevational gradient in the Swiss Alps and a latitudinal gradient, both reaching beyond the distribution limit of most species. Principal components analysis was used to summarize climatic variation in temperature and precipitation across these gradients and assessed the relationship across species between climatic limits along the two gradients. We used logistic regressions to compare how the probability of occurrence of individual species changed with climate along the two gradients. Results We found no correlation of species principal components analysis ( PCA ) values (climate limit) along an elevational and latitudinal precipitation gradient ( PC1 ) but a positive correlation along a temperature gradient ( PC2 ). Species reached a colder climate limit (on average 244 growing degree days lower) and decreased in occurrence more gradually along the elevational compared to the latitudinal gradient. Main conclusions We suggest that the differences in distribution patterns and limits along similar climatic gradients are mainly due to the much shorter dispersal distances along elevational than latitudinal gradients, although other explanations are also possible. We can therefore expect plants in mountains and lowland regions to respond differently to rapid climate change, and so caution must be exercised when using elevation as a proxy for latitude in studies of species distribution. Nonetheless, comparative studies along such gradients can yield important insights into the factors that limit species distributions.

Factors Controlling Phytoplankton Biomass in a Subtropical Coastal Lagoon: Relative Scales of Influence - Nicole Dix; Edward Phlips; Peter Suscy (Estuaries and Coasts, 2013)

Modeling Physical-Biological Responses to Climate Change in the California Current System - Peter Franks; Emanuele Di Lorenzo; Nicole Goebel; Fanny Chenillat; Pascal Riviere; Christopher Edwards; Arthur Miller (Oceanography, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Environmental heterogeneity affects input, storage, and transformation of coarse particulate organic matter in a floodplain mosaic - Simone Daniela Langhans; Urs Richard; Janine Rueegg; Urs Uehlinger; Peter Edwards; Michael Doering; Klement Tockner (Aquatic Sciences, 2013)

Vascular plants as surrogates of butterfly and grasshopper diversity on two Swiss subalpine summer pastures - Bärbel Koch; Peter J. Edwards; Wolf U. Blanckenhorn; Serge Buholzer; Thomas Walter; Rafael O. Wüest; Gabriela Hofer (Biodiversity and Conservation, 2013)

Six Common Mistakes in Conservation Priority Setting - EDWARD T. GAME; PETER KAREIVA; HUGH P. POSSINGHAM (Conservation Biology, 2013)
A vast number of prioritization schemes have been developed to help conservation navigate tough decisions about the allocation of finite resources. However, the application of quantitative approaches to setting priorities in conservation frequently includes mistakes that can undermine their authors’ intention to be more rigorous and scientific in the way priorities are established and resources allocated. Drawing on well‐established principles of decision science, we highlight 6 mistakes commonly associated with setting priorities for conservation: not acknowledging conservation plans are prioritizations; trying to solve an ill‐defined problem; not prioritizing actions; arbitrariness; hidden value judgments; and not acknowledging risk of failure. We explain these mistakes and offer a path to help conservation planners avoid making the same mistakes in future prioritizations. Seis Errores Comunes en la Definición de Prioridades de Conservación

A toxicokinetic model for thiamethoxam in rats: implications for higher-tier risk assessment - Agnieszka J. Bednarska; Peter Edwards; Richard Sibly; Pernille Thorbek (Ecotoxicology, 2013)

Increases of Soil C, N, and P Pools Along an Acacia Tree Density Gradient and Their Effects on Trees and Grasses - Judith Sitters; Peter J. Edwards; Harry Olde Venterink (Ecosystems, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Repeat oral dose toxicity studies of melamine in rats and monkeys - Richard J. Early; Hong Yu; Xueyan Peter Mu; Haiyan Xu; Lei Guo; Qingxue Kong; Junma Zhou; Bruce He; Xiuying Yang; Hailiang Huang; Edward Hu; Ying Jiang (Archives of Toxicology, 2013)

Estimating global arthropod species richness: refining probabilistic models using probability bounds analysis - Andrew J. Hamilton; Vojtech Novotný; Edward K. Waters; Yves Basset; Kurt K. Benke; Peter S. Grimbacher; Scott E. Miller; G. Allan Samuelson; George D. Weiblen; Jian D. L. Yen; Nigel E. Stork (Oecologia, 2013)

Effects of cadmium on the sub-cellular localization of β-catenin and β-catenin-regulated gene expression in NRK-52E cells - Joshua R. Edwards; Kevin Kolman; Peter C. Lamar; Nalini Chandar; Michael J. Fay; Walter C. Prozialeck (BioMetals, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Prospective study of effect modification by Toll-like receptor 4 variation on the association between Trichomonas vaginalis serostatus and prostate cancer - Yen Ching Chen; Yi Ling Huang; Elizabeth A. Platz; John F. Alderete; Lu Zheng; Jennifer R. Rider; Peter Kraft; Edward Giovannucci; Siobhan Sutcliffe (Cancer Causes & Control, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)

Microstructure characteristics during hydrate formation and dissociation revealed by X-ray tomographic microscopy - Stephan A. Klapp; Frieder Enzmann; Peter Walz; Thomas Huthwelker; Jürgen Tuckermann; J.-Oliver Schwarz; Thomas Pape; Edward T. Peltzer; Rajmund Mokso; David Wangner; Federica Marone; Michael Kersten; et al. (Geo-Marine Letters, 2012)

Application of large-scale sequencing to marker discovery in plants - Robert J Henry; Mark Edwards; Daniel L E Waters; Gopala Krishnan S; Peter Bundock; Timothy R Sexton; Ardashir K Masouleh; Catherine J Nock; Julie Pattemore (Journal of Biosciences, 2012)

Regular dental visits are associated with earlier stage at diagnosis for oral and pharyngeal cancer - Scott M. Langevin; Dominique S. Michaud; Melissa Eliot; Edward S. Peters; Michael D. McClean; Karl T. Kelsey (Cancer Causes & Control, 2012)

Clusters of genes encoding fructan biosynthesizing enzymes in wheat and barley - Bao-Lam Huynh; Diane E. Mather; Andreas W. Schreiber; John Toubia; Ute Baumann; Zahra Shoaei; Nils Stein; Ruvini Ariyadasa; James C. R. Stangoulis; James Edwards; Neil Shirley; Peter Langridge; et al. (Plant Molecular Biology, 2012)

Statistical Variability of Dispersion in the Convective Boundary Layer: Ensembles of Simulations and Observations - Jeffrey C. Weil; Peter P. Sullivan; Edward G. Patton; Chin-Hoh Moeng (Boundary-Layer Meteorology, 2012)

Genetically based differentiation in growth of multiple non-native plant species along a steep environmental gradient - Sylvia Haider; Christoph Kueffer; Peter J. Edwards; Jake M. Alexander (Oecologia, 2012)

Elemental and isotopic carbon and nitrogen records of organic matter accumulation in a Holocene permafrost peat sequence in the East European Russian Arctic - Rina Argelia Andersson; Philip Meyers; Edward Hornibrook; Peter Kuhry; Carl‐Magnus Mörth (Journal of Quaternary Science, 2012)
A peat deposit from the East European Russian Arctic, spanning nearly 10 000 years, was investigated to study soil organic matter degradation using analyses of bulk elemental and stable isotopic compositions and plant macrofossil remains. The peat accumulated initially in a wet fen that was transformed into a peat plateau bog following aggradation of permafrost in the late Holocene (∼2500 cal a BP). Total organic carbon and total nitrogen (N) concentrations are higher in the fen peat than in the moss‐dominated bog peat layers. Layers in the sequence that have lower concentrations of total hydrogen (H) are associated with degraded vascular plant residues. C/N and H/C atomic ratios indicate better preservation of organic matter in peat material dominated by bryophytes as opposed to vascular plants. The presence of permafrost in the peat plateau stage and water‐saturated conditions at the bottom of the fen stage appear to lead to better preservation of organic plant material. δ 15 N values suggest N isotopic fractionation was driven primarily by microbial decomposition whereas differences in δ 13 C values appear to reflect mainly changes in plant assemblages. Positive shifts in both δ 15 N and δ 13 C values coincide with a local change to drier conditions as a result of the onset of permafrost and frost heave of the peat surface. This pattern suggests that permafrost aggradation not only resulted in changes in vegetation but also aerated the underlying fen peat, which enhanced microbial denitrification, causing the observed 15 N‐enrichment. Copyright © 2012 John Wiley & Sons, Ltd.

The effect of experimental warming and precipitation change on proteolytic enzyme activity: positive feedbacks to nitrogen availability are not universal - Edward R. Brzostek; John M. Blair; Jeffrey S. Dukes; Serita D. Frey; Sarah E. Hobbie; Jerry M. Melillo; Robert J. Mitchell; Elise Pendall; Peter B. Reich; Gaius R. Shaver; Artur Stefanski; Mark G. Tjoelker; et al. (Global Change Biology, 2012)
Nitrogen regulates the E arth's climate system by constraining the terrestrial sink for atmospheric CO 2 . Proteolytic enzymes are a principal driver of the within‐system cycle of soil nitrogen, yet there is little to no understanding of their response to climate change. Here, we use a single methodology to investigate potential proteolytic enzyme activity in soils from 16 global change experiments. We show that regardless of geographical location or experimental manipulation (i.e., temperature, precipitation, or both), all sites plotted along a single line relating the response ratio of potential proteolytic activity to soil moisture deficit, the difference between precipitation and evapotranspiration. In particular, warming and reductions in precipitation stimulated potential proteolytic activity in mesic sites – temperate and boreal forests, arctic tundra – whereas these manipulations suppressed potential activity in dry grasslands. This study provides a foundation for a simple representation of the impacts of climate change on a central component of the nitrogen cycle.

Effects of exposure to amphetamine derivatives on passive avoidance performance and the central levels of monoamines and their metabolites in mice: Correlations between behavior and neurochemistry - Kevin Sean Murnane; Shane Alan Perrine; Brendan James Finton; Matthew Peter Galloway; Leonard Lee Howell; William Edward Fantegrossi (Psychopharmacology, 2012)

Identification of novel quantitative trait loci for days to ear emergence and flag leaf glaucousness in a bread wheat (Triticum aestivum L.) population adapted to southern Australian conditions - Dion Bennett; Ali Izanloo; James Edwards; Haydn Kuchel; Ken Chalmers; Mark Tester; Matthew Reynolds; Thorsten Schnurbusch; Peter Langridge (Theoretical and Applied Genetics, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Innovation for sustainability: toward a sustainable urban future in industrialized cities - Ji Han; Psyche Fontanos; Kensuke Fukushi; Srikantha Herath; Niko Heeren; Vincenzo Naso; Claudio Cecchi; Peter Edwards; Kazuhiko Takeuchi (Sustainability Science, 2012)

Processes at multiple scales affect richness and similarity of non‐native plant species in mountains around the world - Tim Seipel; Christoph Kueffer; Lisa J. Rew; Curtis C. Daehler; Aníbal Pauchard; Bridgett J. Naylor; Jake M. Alexander; Peter J. Edwards; Catherine G. Parks; José Ramon Arevalo; Lohengrin A. Cavieres; Hansjörg Dietz; et al. (Global Ecology and Biogeography, 2012)
Aim To investigate how species richness and similarity of non‐native plants varies along gradients of elevation and human disturbance. Location Eight mountain regions on four continents and two oceanic islands. Methods We compared the distribution of non‐native plant species along roads in eight mountainous regions. Within each region, abundance of plant species was recorded at 41–84 sites along elevational gradients using 100‐m 2 plots located 0, 25 and 75 m from roadsides. We used mixed‐effects models to examine how local variation in species richness and similarity were affected by processes at three scales: among regions (global), along elevational gradients (regional) and with distance from the road (local). We used model selection and information criteria to choose best‐fit models of species richness along elevational gradients. We performed a hierarchical clustering of similarity to investigate human‐related factors and environmental filtering as potential drivers at the global scale. Results Species richness and similarity of non‐native plant species along elevational gradients were strongly influenced by factors operating at scales ranging from 100 m to 1000s of km. Non‐native species richness was highest in the New World regions, reflecting the effects of colonization from Europe. Similarity among regions was low and due mainly to certain Eurasian species, mostly native to temperate Europe, occurring in all New World regions. Elevation and distance from the road explained little of the variation in similarity. The elevational distribution of non‐native species richness varied, but was always greatest in the lower third of the range. In all regions, non‐native species richness declined away from roadsides. In three regions, this decline was steeper at higher elevations, and there was an interaction between distance and elevation. Main conclusions Because non‐native plant species are affected by processes operating at global, regional and local scales, a multi‐scale perspective is needed to understand their patterns of distribution. The processes involved include global dispersal, filtering along elevational gradients and differential establishment with distance from roadsides.

Experimental Study of Brittle Behavior of Clay Shale in Rapid Triaxial Compression - Florian Amann; Peter Kaiser; Edward Alan Button (Rock Mechanics and Rock Engineering, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Physiology and cell biology of acupuncture observed in calcium signaling activated by acoustic shear wave - Geng Li; Jie-Ming Liang; Pei-Wen Li; Xiaoqiang Yao; Peter Zhong Pei; Wei Li; Qi-Hua He; Xifei Yang; Queenie C. C. Chan; Paul Y. S. Cheung; Qi Yuan Ma; Siu Kam Lam; et al. (Pflügers Archiv - European Journal of Physiology, 2011)

Village environs as source of nitrate contamination in groundwater: a case study in basaltic geo-environment in central India - D. V. Reddy; P. Nagabhushanam; Edward Peters (Environmental Monitoring and Assessment, 2011)

Localization of AQP5 during development of the mouse submandibular salivary gland - Helga S. Larsen; Marit H. Aure; Sarah B. Peters; Melinda Larsen; Edward B. Messelt; Hilde Kanli Galtung (Journal of Molecular Histology, 2011)

Distribution, growth performance and genetic variation of Erigeron annuus in the Swiss Alps - Miluse Trtikova; Sabine Güsewell; Matthias Baltisberger; Peter J. Edwards (Biological Invasions, 2011)

Interdecadal declines in flood frequency increase primary production in lakes of a northern river delta - SUZANNE McGOWAN; PETER R. LEAVITT; ROLAND I. HALL; BRENT B. WOLFE; THOMAS W. D. EDWARDS; TAMMY KARST‐RIDDOCH; SHEILA R. VARDY (Global Change Biology, 2011)
Human activities and climate change have greatly altered flooding regimes in many of the world's river deltas, but the impact of such changes remains poorly quantified on decadal to multidecadal timescales. This study identified the response of delta lake primary production (measured as the concentration of sedimentary pigments) to variations in flood frequency using spatial surveys and paleolimnological analyses of lakes in the Peace‐Athabasca Delta (PAD), Canada. Surveys of 61 lakes spanning a range of hydrological conditions showed that those lakes that received flood waters less frequently were associated with elevated algal production (surface sedimentary pigments) and, in some lakes, increased growth of emergent macrophytes and epiphytic diatoms. Paleolimnological analyses of five lakes corroborated the contemporary spatial survey results by showing that production of pigments from most algal groups increased during recent periods of lower flood frequency in the 20th century as determined from increases in cellulose‐inferred lake‐water oxygen isotope composition and plant macrofossils, but remained stable in a ‘reference’ basin. In general, past periods of elevated algal production coincided with the increased abundance of submerged macrophytes or emergent vegetation that provide habitat for attached algae. These results suggest that interdecadal declines in river discharge arising from increased aridity, hydrologic regulation or consumptive water use will cause long‐term increases in primary production and alter ecosystem processes (carbon sequestration, biological diversity) in aquatic delta ecosystems similar to the PAD where lakes become nutrient‐rich in the absence of flooding.

Reserve design for uncertain responses of coral reefs to climate change - Peter J. Mumby; Ian A. Elliott; C. Mark Eakin; William Skirving; Claire B. Paris; Helen J. Edwards; Susana Enríquez; Roberto Iglesias‐Prieto; Laurent M. Cherubin; Jamie R. Stevens (Ecology Letters, 2011)
Ecology Letters (2011) 14: 132–140 Abstract Rising sea temperatures cause mass coral bleaching and threaten reefs worldwide. We show how maps of variations in thermal stress can be used to help manage reefs for climate change. We map proxies of chronic and acute thermal stress and develop evidence‐based hypotheses for the future response of corals to each stress regime. We then incorporate spatially realistic predictions of larval connectivity among reefs of the Bahamas and apply novel reserve design algorithms to create reserve networks for a changing climate. We show that scales of larval dispersal are large enough to connect reefs from desirable thermal stress regimes into a reserve network. Critically, we find that reserve designs differ according to the anticipated scope for phenotypic and genetic adaptation in corals, which remains uncertain. Attempts to provide a complete reserve design that hedged against different evolutionary outcomes achieved limited success, which emphasises the importance of considering the scope for adaptation explicitly. Nonetheless, 15% of reserve locations were selected under all evolutionary scenarios, making them a high priority for early designation. Our approach allows new insights into coral holobiont adaptation to be integrated directly into an adaptive approach to management.

Scaling an Instantaneous Model of Tundra NEE to the Arctic Landscape - Michael M. Loranty; Scott J. Goetz; Edward B. Rastetter; Adrian V. Rocha; Gaius R. Shaver; Elyn R. Humphreys; Peter M. Lafleur (Ecosystems, 2011)

The role of bioclimatic origin, residence time and habitat context in shaping non-native plant distributions along an altitudinal gradient - Sylvia Haider; Jake Alexander; Hansjörg Dietz; Ludwig Trepl; Peter J. Edwards; Christoph Kueffer (Biological Invasions, 2010)

N and P Cycling in Tanzanian Humid Savanna: Influence of Herbivores, Fire, and N2-Fixation - Patrick G. Cech; Harry Olde Venterink; Peter J. Edwards (Ecosystems, 2010)

A proposal to change existing virus species names to non-Latinized binomials - Marc H. V. Van Regenmortel; Donald S. Burke; Charles H. Calisher; Ralf G. Dietzgen; Claude M. Fauquet; Said A. Ghabrial; Peter B. Jahrling; Karl M. Johnson; Michael R. Holbrook; Marian C. Horzinek; Günther M. Keil; Jens H. Kuhn; et al. (Archives of Virology, 2010)

PCR primers for microsatellite loci in a Madagascan waterbird, the Sakalava Rail (Amaurornis olivieri) - Edward G. Brede; Peter Long; Sama Zefania; Marc Rabenandrasana; Tamás Székely; Michael Bruford (Conservation Genetics Resources, 2010)

Wastewater‐fed aquaculture in the East Kolkata Wetlands, India: anachronism or archetype for resilient ecocultures? - Stuart W. Bunting; Jules Pretty; Peter Edwards (Reviews in Aquaculture, 2010)
Wastewater‐fed aquaculture is generally in decline. The 12 500 ha East Kolkata Wetlands (EKW) Ramsar site in peri‐urban Kolkata, India, is the only large‐scale formal system still operating and appears to demonstrate a high degree of resilience. This paper identifies aspects of wastewater‐fed aquaculture in the EKW that contribute to its sustained operation. The Driving Forces, Pressures, State, Impact, Response (DPSIR) framework was used to structure the assessment. Resilience within the EKW can be attributed to the scale of operation, adaptive production strategies that optimise resource utilisation while minimising risks, self‐organisation among stakeholders and timely legislation and institutional interventions to preserve the natural character of the wetlands. The introduction of externalising technologies, erosion of social capital and loss of traditional ecological knowledge threaten to undermine this resilience. Outcomes from this analysis should inform future management of the EKW to ensure that resilience is retained and enhanced.

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Why only tetraploid Solidago gigantea (Asteraceae) became invasive: a common garden comparison of ploidy levels - Daniel R. Schlaepfer; Peter J. Edwards; Regula Billeter (Oecologia, 2010)

Morphological controls in sandy estuaries: the influence of tidal flats and bathymetry on sediment transport - Peter Edward Robins; Alan G. Davies (Ocean Dynamics, 2010)

Data integration for European marine biodiversity research: creating a database on benthos and plankton to study large-scale patterns and long-term changes - Leen Vandepitte; Bart Vanhoorne; Alexandra Kraberg; Natalie Anisimova; Chryssanthi Antoniadou; Rita Araújo; Inka Bartsch; Beatriz Beker; Lisandro Benedetti-Cecchi; Iacopo Bertocci; Sabine Cochrane; Keith Cooper; et al. (Hydrobiologia, 2010)

Plant species from mesotrophic wetlands cause relatively high methane emissions from peat soil - Albert Koelbener; Lena Ström; Peter J. Edwards; Harry Olde Venterink (Plant and Soil, 2010)

Applications of open geospatial web services in precision agriculture: a review - Edward Nash; Peter Korduan; Ralf Bill (Precision Agriculture, 2009)

Rapid effects of hypoxia on H+ homeostasis in articular chondrocytes - John S. Gibson; David McCartney; Joanna Sumpter; Thomas P. A. Fairfax; Peter I. Milner; Hannah L. Edwards; Robert J. Wilkins (Pflügers Archiv - European Journal of Physiology, 2009)

Lake sediment evidence for late Holocene climate change and landscape erosion in western Iceland - Freddy J. Gathorne-Hardy; Egill Erlendsson; Peter G. Langdon; Kevin J. Edwards (Journal of Paleolimnology, 2009)

Influence of light and nutrient conditions on seedling growth of native and invasive trees in the Seychelles - Eva Schumacher; Christoph Kueffer; Peter J. Edwards; Hansjörg Dietz (Biological Invasions, 2009)

Perspectives on biogeomorphology, ecosystem engineering and self-organisation in island-braided fluvial ecosystems - Robert A. Francis; Dov Corenblit; Peter J. Edwards (Aquatic Sciences, 2009)

Measurement and calculation of OH reactivity at a United Kingdom coastal site - James D. Lee; Jennifer C. Young; Katie A. Read; Jacqueline F. Hamilton; James R. Hopkins; Alastair C. Lewis; Brian J. Bandy; James Davey; Peter Edwards; Trevor Ingham; Daniel E. Self; Shona C. Smith; et al. (Journal of Atmospheric Chemistry, 2009)

APPLICATIONS IN COASTAL MODELING AND FORECASTING - Pierre De Mey; Peter Craig; Fraser Davidson; Christopher Edwards; Yoichi Ishikawa; John Kindle; Roger Proctor; Keith Thompson; Jiang Zhu (Oceanography, 2009)

THE GODAE HIGH-RESOLUTION SEA SURFACE TEMPERATURE PILOT PROJECT - Craig Donlon; Kenneth Casey; Ian Robinson; Chelle Gentemann; Richard Reynolds; Ian Barton; Olivier Arino; John Stark; Nick Rayner; Pierre LeBorgne; David Poulter; Jorge Vazquez-Cuervo; et al. (Oceanography, 2009)

Fishery‐induced demographic changes in the timing of spawning: consequences for reproductive success* - Peter J. Wright; Edward A. Trippel (Fish and Fisheries, 2009)
Demography can have a significant effect on reproductive timing and the magnitude of such an effect can be comparable to environmentally induced variability. This effect arises because the individuals of many fish species spawn progressively earlier within a season and may produce more egg batches over a longer period as they get older, thus extending their lifetime spawning duration. Inter‐annual variation in spawning time is a critical factor in reproductive success because it affects the early environmental conditions experienced by progeny and the period they have to complete phases of development. By reducing the average lifetime spawning duration within a fish stock, fishing pressure could be increasing the variability in reproductive success and reducing long‐term stock reproductive potential. Empirical estimates of selection on birth date, from experiments and using otolith microstructure, demonstrate that there is considerable variation in selection on birth date both within a spawning season and between years. The few multi‐year studies that have linked egg production with the survival of progeny to the juvenile stage further highlight the uncertainty that adults face in timing their spawning to optimize offspring survival. The production of many small batches of eggs over a long period of time within a season and over a lifetime is therefore likely to decrease variance and increase mean progeny survival. Quantifying this effect of demography on variability in survival requires a focus on lifetime reproductive success rather than year specific relationships between recruitment and stock reproductive potential. Modelling approaches are suggested that can better quantify the likely impact of changing spawning times on year‐class strength and lifetime reproductive potential. The evidence presented strengthens the need to avoid fishing severely age truncated fish stocks.

Genetic linkage map of Phaeosphaeria nodorum, the causal agent of stagonospora nodorum blotch disease of wheat - Arkadiusz Malkus; Qijian Song; Perry Cregan; Edward Arseniuk; Peter P. Ueng (European Journal of Plant Pathology, 2009)

Disturbance‐Response Analysis: a Method for Rapid Assessment of the Threat to Species in Disturbed Areas - CARLOS MARTORELL; EDWARD M. PETERS (Conservation Biology, 2009)
We developed a method with which to analyze a specie's response to chronic anthropogenic disturbance (CAD). We regressed density of individuals on the intensity of 3 disturbance agents (human activities, raising livestock, and land degradation) along CAD gradients to determine how much CAD is experienced by a species; whether species are ruderal (achieving maximum densities in disturbed sites); whether density declines as a result of CAD; which disturbance agents are responsible for this reduction; and the number of populations that decline as a result of CAD. We tested the method on 9 threatened Mammillaria species (Cactaceae). Seven species were ruderal. In 4 species, actual disturbance surpassed the CAD intensity in which plants achieved their maximum densities; thus, the density of those 4 species appeared to be declining. For 7 species, some populations were threatened by human activities or livestock, whereas others were favored by them. Land degradation negatively affected all species. Our results allowed us to distinguish 4 groups of species that had similar responses and thus may require different forms of management. Our method provided an estimation of the growth rate (λ) of the studied populations that was significantly correlated with λs obtained from demographic studies. The size structures of populations were consistent with the predictions of the analysis, which suggests our results are consistent and reliable. Disturbance–response analysis provides a basis for management in heavily populated areas, where conservation must be achieved along with development activities that cause CAD. The method provides readily interpretable information, which facilitates participative decision making; the data are rapidly generated, which makes it appropriate when results are required promptly or for assessment of large numbers of species; and it provides a comprehensive perception of how threatened species behave in the real world.

Changes over three decades in the floristic composition of nutrient-poor grasslands in the Swiss Alps - Markus Peter; Andreas Gigon; Peter J. Edwards; Andreas Lüscher (Biodiversity and Conservation, 2009)

Establishment of parallel altitudinal clines in traits of native and introduced forbs - Jake M. Alexander; Peter J. Edwards; Myriam Poll; Catherine G. Parks; Hansjörg Dietz (Ecology, 2009)
Due to altered ecological and evolutionary contexts, we might expect the responses of alien plants to environmental gradients, as revealed through patterns of trait variation, to differ from those of the same species in their native range. In particular, the spread of alien plant species along such gradients might be limited by their ability to establish clinal patterns of trait variation. We investigated trends in growth and reproductive traits in natural populations of eight invasive Asteraceae forbs along altitudinal gradients in their native and introduced ranges (Valais, Switzerland, and Wallowa Mountains, Oregon, USA). Plants showed similar responses to altitude in both ranges, being generally smaller and having fewer inflorescences but larger seeds at higher altitudes. However, these trends were modified by region‐specific effects that were independent of species status (native or introduced), suggesting that any differential performance of alien species in the introduced range cannot be interpreted without a fully reciprocal approach to test the basis of these differences. Furthermore, we found differences in patterns of resource allocation to capitula among species in the native and the introduced areas. These suggest that the mechanisms underlying trait variation, for example, increasing seed size with altitude, might differ between ranges. The rapid establishment of clinal patterns of trait variation in the new range indicates that the need to respond to altitudinal gradients, possibly by local adaptation, has not limited the ability of these species to invade mountain regions. Studies are now needed to test the underlying mechanisms of altitudinal clines in traits of alien species.

Dynamic imaging of cancer growth and invasion: a modified skin-fold chamber model - Stephanie Alexander; Gudrun E. Koehl; Markus Hirschberg; Edward K. Geissler; Peter Friedl (Histochemistry and Cell Biology, 2008)

Phylogeography of native ploidy levels and invasive tetraploids of Solidago gigantea - DANIEL R. SCHLAEPFER; PETER J. EDWARDS; ALEX WIDMER; REGULA BILLETER (Molecular Ecology, 2008)
Ploidy level is an important aspect of the genetic makeup of a plant, and can strongly influence ecological characteristics such as invasiveness. We used a phylogeographical approach to elucidate the history of polyploidization and colonization success of diploid and tetraploid Solidago gigantea Aiton (Asteraceae) within its native range in North America. We were also able to identify the probable source material of the haplotype lineages invasive in Europe and Asia, where only tetraploid plants occur. To do this, we sequenced 1275 bp of chloroplast intergenic spacer DNA in 268 individuals from 57 populations. In addition, we performed a crossing experiment, which supported the hypothesis that chloroplast inheritance in this species is maternal. The phylogeographical analysis showed a complex pattern of 20 haplotypes of diploid and tetraploid plants. In North America, we found significant differentiation among regions, private haplotypes, and isolation by distance. Ploidy levels were more differentiated in the northern regions than in the South. The haplotype network was shallow and included one tetraploid‐only, star‐shaped cluster of haplotypes that were particularly successful colonizers. Post‐glacial migration of diploid S. gigantea occurred mainly northwards east of the Appalachian Mountains, and to a lesser degree also southward. Our data suggest that tetraploids have formed several times in North America. Haplotype number and diversity were lower in European populations than in the native range, and we found evidence that four haplotypes were introduced to Europe from two source areas, New England and the Southern Appalachian Mountains.

Sub‐millennial climate shifts in the western Mediterranean during the last glacial period recorded in a speleothem from Mallorca, Spain - Edward J. Hodge; David A. Richards; Peter L. Smart; Angel Ginés; David P. Mattey (Journal of Quaternary Science, 2008)
Very few high‐resolution and directly dated terrestrial archives of the last glacial period exist for the western Mediterranean region, yet this is a key locality for recording sub‐millennial North Atlantic and Mediterranean climate change. Here, we present evidence of effective precipitation changes based on growth history and δ 13 C of calcite in a Mallorcan stalagmite that grew between 112 and 48 ka. Effective precipitation in Mallorca appears to have been sensitive to proximal sea surface temperature variations and at certain times, ca. 76 ka for example, changed rapidly from moist to arid conditions in only a few centuries. A sea‐level highstand during Marine Isotope Stage (MIS) 5a interrupted growth. Regrowth started promptly after this, but effective precipitation decreased markedly for much of the later part of MIS 5a, and also for shorter periods correlative with Heinrich events H8 (ca. 90 ka) and H6 (ca. 65 ka), with growth ceasing during H5 (ca. 48 ka). Arid episodes in Mallorca appear to be expressions of extremely cold periods recorded further north in Europe and occur contemporaneously with rapid decreases in Greenland temperature. Copyright © 2008 John Wiley & Sons, Ltd.

Cytogeography of Solidago gigantea (Asteraceae) and its invasive ploidy level - Daniel R. Schlaepfer; Peter J. Edwards; John C. Semple; Regula Billeter (Journal of Biogeography, 2008)
Aim Newly formed polyploids experience problems of establishment and spread similar to those faced by newly introduced alien species. To understand the significance of polyploidy in biological invasions, we mapped the distribution of ploidy levels in Solidago gigantea Aiton in its native range in North America, and in Europe and East Asia where it is invasive. Location North America, Europe and East Asia. Methods Flow cytometry was used to measure ploidy levels in a total of 834 plants from 149 locations. Together with data from contributors and a literature review, ploidy‐level data were assembled for 336 locations. Cytogeographical maps from North America and Europe were prepared, incorporating new and previously published ploidy‐level data. Results In the native range, diploid, tetraploid and hexaploid plants were found, and also one triploid and one pentaploid plant (2 n = 3 x and 2 n = 5 x , respectively, each being new reports for this species). There was a high degree of geographical separation among the ploidy levels, and populations with mixed ploidy were rare. However, four zones were identified where plants of different ploidy could come into contact. In Europe and East Asia, only tetraploid plants were found. Main conclusions The geographical pattern in North America suggests that the ploidy levels are ecologically differentiated, although further investigations are needed to identify the nature of these differences. Alien populations appear to be exclusively tetraploid, but it is not clear whether this is because tetraploids were selectively introduced or because diploids were unsuccessful. In any case, comparisons between native and introduced populations need to account for ploidy level.

Effects of Herbivory, Fire and N2-fixation on Nutrient Limitation in a Humid African Savanna - Patrick G. Cech; Thomas Kuster; Peter J. Edwards; Harry Olde Venterink (Ecosystems, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Nitrogen versus phosphorus limitation of phytoplankton growth in Ten Mile Creek, Florida, USA - Youjian Lin; Zhenli He; Yuangen Yang; Peter J. Stoffella; Edward J. Phlips; Charles A. Powell (Hydrobiologia, 2008)

Phylogeography, historical demography, and the role of post-settlement ecology in two Hawaiian damselfish species - Marina L. Ramon; Peter A. Nelson; Edward De Martini; William J. Walsh; Giacomo Bernardi (Marine Biology, 2008)

Macroinvertebrate drift density in relation to abiotic factors in the Missouri River - Christopher H. Hay; Thomas G. Franti; David B. Marx; Edward J. Peters; Larry W. Hesse (Hydrobiologia, 2008)

The global trend in plant twining direction - Will Edwards; Angela T. Moles; Peter Franks (Global Ecology and Biogeography, 2007)
Aim To examine, at a global scale, patterns in the direction in which climbing plants twine. We tested three hypotheses: (1) that twining direction is determined randomly; (2) that twining direction is determined by apices following the apparent movement of the sun across the sky; and (3) that twining direction is determined by the Coriolis effect. Location Seventeen sites spanning nine countries, both hemispheres and 65° of latitude. Methods Twining direction was recorded for the first c . 100 stems encountered along transects through natural vegetation at each site. Results Ninety‐two per cent of the 1485 twining stems we recorded grew in right‐handed helices, i.e. they twined in an anticlockwise direction. This is significantly ( P P = 0.33) and hemisphere ( P = 0.63). These data are inconsistent with the idea that twining direction is determined by either the relative passage of the sun through the celestial sphere or by the Coriolis effect. Thus, we reject all three of our hypotheses. Main conclusions The predominance of right‐handed helical growth in climbing plants cannot be explained by hypotheses attempting to link plant growth behaviour and global location. One alternative hypothesis for our findings is that the widespread phenomenon of anticlockwise twining arises as a function of microtubule orientation operating at a subcellular level.

KILLER WHALES, WHALING, AND SEQUENTIAL MEGAFAUNAL COLLAPSE IN THE NORTH PACIFIC: A COMPARATIVE ANALYSIS OF THE DYNAMICS OF MARINE MAMMALS IN ALASKA AND BRITISH COLUMBIA FOLLOWING COMMERCIAL WHALING - Andrew W. Trites; Volker B. Deecke; Edward J. Gregr; John K.B. Ford; Peter F. Olesiuk (Marine Mammal Science, 2007)
The hypothesis that commercial whaling caused a sequential megafaunal collapse in the North Pacific Ocean by forcing killer whales to eat progressively smaller species of marine mammals is not supported by what is known about the biology of large whales, the ecology of killer whales, and the patterns of ecosystem change that took place in Alaska, British Columbia, and elsewhere in the world following whaling. A comparative analysis shows that populations of seals, sea lions, and sea otters increased in British Columbia following commercial whaling, unlike the declines noted in the Gulf of Alaska and Aleutian Islands. The declines of seals and sea lions that began in western Alaska around 1977 were mirrored by increases in numbers of these species in British Columbia. A more likely explanation is that the seal and sea lion declines and other ecosystem changes in Alaska stem from a major oceanic regime shift that occurred in 1977. Killer whales are unquestionably a significant predator of seals, sea lions, and sea otters—but not because of commercial whaling.

The natural furanone ( 5Z )‐4‐bromo‐5‐(bromomethylene)‐3‐butyl‐2( 5H )‐furanone disrupts quorum sensing‐regulated gene expression in Vibrio harveyi by decreasing the DNA‐binding activity of the transcriptional regulator protein luxR - Tom Defoirdt; Carol M. Miyamoto; Thomas K. Wood; Edward A. Meighen; Patrick Sorgeloos; Willy Verstraete; Peter Bossier (Environmental Microbiology, 2007)
Summary This study aimed at getting a deeper insight in the molecular mechanism by which the natural furanone ( 5Z )‐4‐bromo‐5‐(bromomethylene)‐3‐butyl‐2( 5H )‐furanone disrupts quorum sensing in Vibrio harveyi . Bioluminescence experiments with signal molecule receptor double mutants revealed that the furanone blocks all three channels of the V. harveyi quorum sensing system. In further experiments using mutants with mutations in the quorum sensing signal transduction pathway, the compound was found to block quorum sensing‐regulated bioluminescence by interacting with a component located downstream of the Hfq protein. Furthermore, reverse transcriptase real‐time polymerase chain reaction with specific primers showed that there was no effect of the furanone on luxR Vh mRNA levels in wild‐type V. harveyi cells. In contrast, mobility shift assays showed that in the presence of the furanone, significantly lower levels of the LuxR Vh response regulator protein were able to bind to its target promoter sequences in wild‐type V. harveyi . Finally, tests with purified LuxR Vh protein also showed less shifts with furanone‐treated LuxR Vh , whereas the LuxR Vh concentration was found not to be altered by the furanone (as determined by SDS‐PAGE). Therefore, our data indicate that the furanone blocks quorum sensing in V. harveyi by rendering the quorum sensing master regulator protein LuxR Vh unable to bind to the promoter sequences of quorum sensing‐regulated genes.

Evidence for a male-produced pheromone in Tetropium fuscum (F.) and Tetropium cinnamopterum (Kirby) (Coleoptera: Cerambycidae) - Peter J. Silk; Jon Sweeney; Junping Wu; Jessica Price; Jerzy M. Gutowski; Edward G. Kettela (The Science of Nature, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A note on the top-down and bottom-up gradient functions over a forested site - Weiguo Wang; Kenneth J. Davis; Chuixiang Yi; Edward G. Patton; Martha P. Butler; Daniel M. Ricciuto; Peter S. Bakwin (Boundary-Layer Meteorology, 2007)

Toxicity of cobalt-complexed cyanide to Oncorhynchus mykiss, Daphnia magna, and Ceriodaphnia dubia - Edward E. Little; Robin D. Calfee; Peter Theodorakos; Zoe Ann Brown; Craig A. Johnson (Environmental Science and Pollution Research, 2007)

In vitro rooting of microshoots of Cotinus coggygria Mill, a woody ornamental plant - Peter S. R. Metivier; Edward C. Yeung; Kamlesh R. Patel; Trevor A. Thorpe (In Vitro Cellular & Developmental Biology - Plant, 2007)

AAPS-FDA Workshop White Paper: Microdialysis Principles, Application and Regulatory Perspectives - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (Pharmaceutical Research, 2007)

AAPS-FDA workshop white paper: Microdialysis principles, application, and regulatory perspectives report from the Joint AAPS-FDA Workshop, November 4–5, 2005, Nashville, TN - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (The AAPS Journal, 2007)

Degradation of water quality in Lough Neagh, Northern Ireland, by diffuse nitrogen flux from a phosphorus‐rich catchment - Lynda Bunting; Peter R. Leavitt; Christopher E. Gibson; Edward J. McGee; Valerie A. Hall (Limnology and Oceanography, 2007)
Annually resolved fossil records of nitrogen (N) inputs (as sedimentary δ 15 N, N content), aquatic production (δ 13 C, C content), and algal abundance and gross community composition (pigments, nonsiliceous microfossils) from Lough Neagh, Northern Ireland (NI), were compared with annual records of climatic variability, atmospheric and urban nutrient loading, whole‐catchment nutrient budgets, and limnological monitoring data to identify the unique effects of N on the eutrophication of a phosphorus (P)‐rich lake during ca. 1933‐1995. Cluster analysis revealed two major biostratigraphic zones. Zone I (ca. 1933–1955) was characterized by moderate lake production, as inferred from low concentrations of most fossil pigments and reduced δ 15 N signatures but elevated δ 13 C values and chlorophyte microfossil concentrations. In contrast, Zone II (ca. 1955‐1995) exhibited greatly increased contents of 15 N, N, C, and algal pigments, combined with strongly reduced δ 13 C ratios and chlorophyte fossil abundance, a pattern consistent with recent severe eutrophication. Overall, microfossils of diazotrophic cyanobacteria were most abundant during the transition period between zones (ca. 1955‐1964). Regression analysis revealed that past N influx to the lake (as δ 15 N; r 2 = 0.916, p 2 = 0.837, p 2 = 0.388, p 2 δ 15 N = 0.503, p 2 cyanobacteria = 0.296, p 2 total algae = 0.046, p

Separating climatic and possible human impacts in the early Holocene: biotic response around the time of the 8200 cal. yr BP event - Kevin J. Edwards; Peter G. Langdon; Heather Sugden (Journal of Quaternary Science, 2007)
The early Holocene is characterised by rapid climate change events, which in the North Atlantic region are often associated with changes in thermohaline circulation. Superimposed on this in northwest Europe is localised evidence for human impact on the landscape, although separating climatic and anthropogenic mechanisms for environmental change is often difficult. Biotic and sedimentological evidence from a lacustrine sequence from the Inner Hebrides, Scotland, shows a considerable reduction in inferred local woodland centred upon 8250 cal. yr BP. These data correlate precisely with a distinctive rise in the charcoal:pollen ratio and hence suggest a possible Mesolithic human impact upon the vegetation around this time. A quantitative temperature reconstruction from chironomid analyses from the same sequence, supported by sedimentological data, indicates that the fall in arboreal pollen taxa occurred as climate warmed significantly during the early Holocene. This warming was followed by a significant cold event, with mean July temperatures reduced by 2°C, that lasted for at least 320 years ca. 7790–7470 cal. yr BP. Woodland recovered during this phase suggesting that the vegetation during the 8250 cal. yr BP interval was likely to have been responding to human activity, and not climate, and hence it is possible at specific sites to separate the influence of these key drivers of environmental change. Copyright © 2006 John Wiley & Sons, Ltd.

The Influence of Habitat Variables on Bird Communities in Forest Remnants in Costa Rica - Robert B. Matlock; Peter J. Edwards (Biodiversity and Conservation, 2006)

Phosphorus Translocation by Red Deer on a Subalpine Grassland in the Central European Alps - Martin Schütz; Anita C. Risch; Gérald Achermann; Conny Thiel-Egenter; Deborah S. Page-Dumroese; Martin F. Jurgensen; Peter J. Edwards (Ecosystems, 2006)

hAT element population genetics in Anopheles gambiae s.l. in Mozambique - David A. O’Brochta; Ramanand A. Subramanian; Jamison Orsetti; Edward Peckham; Nicole Nolan; Peter Arensburger; Peter W. Atkinson; Derek J. Charlwood (Genetica, 2006)

“Agouti NOD”: identification of a CBA-derived Idd locus on Chromosome 7 and its use for chimera production with NOD embryonic stem cells - Jing Chen; Peter C. Reifsnyder; Felix Scheuplein; William H. Schott; Maria Mileikovsky; Sharon Soodeen-Karamath; Andras Nagy; Michael H. Dosch; James Ellis; Friedrich Koch-Nolte; Edward H. Leiter (Mammalian Genome, 2005)

Monomorphic subtelomeric DNA in the filamentous fungus, Metarhizium anisopliae,contains a RecQ helicase-like gene - Peter W. Inglis; Daniel J. Rigden; Luciane V. Mello; Edward J. Louis; M. Cléria. Valadares-Inglis (Molecular Genetics and Genomics, 2005)

Nitrogen/phosphorus leaf stoichiometry and the scaling of plant growth - Karl J. Niklas; Thomas Owens; Peter B. Reich; Edward D. Cobb (Ecology Letters, 2005)
We adopted previous N : P stoichiometric models for zooplankton relative growth to predict the relative growth rates of the leaves μ L of vascular plants assuming that annual leaf growth in dry mass is dictated by how leaf nitrogen N L is allocated to leaf proteins and how leaf phosphorus P L is allocated to rRNA. This model is simplified provided that N L scales as some power function of P L across the leaves of different species. This approach successfully predicted the μ L of 131 species of vascular plants based on the observation that, across these species, N L scaled, on average, as the 3/4 power of P L , i.e. N L ∝ P . When juxtaposed with prior allometric theory and observations, our findings suggest that a transformation in N : P stoichiometry occurs when the plant body undergoes a transition from primary to secondary growth.

Construction of a Festuca pratensis BAC library for map-based cloning in Festulolium substitution lines - Iain S. Donnison; Donal M. O’Sullivan; Ann Thomas; Peter Canter; Beverley Moore; Ian Armstead; Howard Thomas; Keith J. Edwards; Ian P. King (Theoretical and Applied Genetics, 2005)

Epithermal gold veins in a caldera setting: Banská Hodruša, Slovakia - Peter Koděra; Jaroslav Lexa; Andrew Hugh Rankin; Anthony Edward Fallick (Mineralium Deposita, 2005)

Climate variability and campylobacter infection: an international study - R. Sari Kovats; Sally J. Edwards; Dominique Charron; John Cowden; Rennie M. D’Souza; Kristie L. Ebi; Charmaine Gauci; Peter Gerner-Smidt; Shakoor Hajat; Simon Hales; Gloria Hernández Pezzi; Bohumir Kriz; et al. (International Journal of Biometeorology, 2005)

Effects of heterogeneous habitat use by cattle on nutrient availability and litter decomposition in soils of an Alpine pasture - Sabine Güsewell; Peter L. Jewell; Peter J. Edwards (Plant and Soil, 2005)

A high-density microsatellite consensus map for bread wheat (Triticum aestivum L.) - Daryl J. Somers; Peter Isaac; Keith Edwards (Theoretical and Applied Genetics, 2004)

Quaternary ecological and geomorphic changes associated with rainfall events in presently semi‐arid northeastern Brazil - Augusto S. Auler; Xianfeng Wang; R. Lawrence Edwards; Hai Cheng; Patrícia S. Cristalli; Peter L. Smart; David A. Richards (Journal of Quaternary Science, 2004)
Several geomorphic features and palaeobiotic remains in now semi‐arid northeastern Brazil indicate major palaeoenvironmental changes during past periods of increased rainfall. 230 Th mass spectrometric ages of speleothems and travertines have allowed the determination of the timing and duration of wetter than present conditions. The data demonstrate that wet events have occurred throughout much of the Pleistocene, present dry conditions having been established at the end of the Younger Dryas. A markedly different fauna comprising megafaunal elements not adapted to the present low arboreal scrubland caatinga vegetation existed in the area. Palaeobotanical remains embedded in travertine indicate forested vegetation at these wetter intervals, suggesting that the caatinga was then replaced or mixed with a semi‐deciduous forest. Due to the abundance of travertine sites containing fossil botanical remains in northeastern Brazil, it is believed that forest expansion occurred over large areas of the now semi‐arid zone, showing that the long hypothesised forested links between biodiversity‐rich Amazon and Atlantic rainforests may indeed have existed during these moister phases. Copyright © 2004 John Wiley & Sons, Ltd.

Small Scale Field Study of an Ocean CO2 Plume - Peter G. Brewer; Edward Peltzer; Izuo Aya; Peter Haugan; Richard Bellerby; Kenji Yamane; Ryuji Kojima; Peter Walz; Yasuharu Nakajima (Journal of Oceanography, 2004)

Effects of Direct Ocean CO2 Injection on Deep-Sea Meiofauna - James P. Barry; Kurt R. Buck; Chris F. Lovera; Linda Kuhnz; Patrick J. Whaling; Edward T. Peltzer; Peter Walz; Peter G. Brewer (Journal of Oceanography, 2004)

Rain forest invasion of eucalypt‐dominated woodland savanna, Iron Range, north‐eastern Australia: II. Rates of landscape change - Jeremy Russell‐Smith; Peter J. Stanton; Andrew C. Edwards; Peter J. Whitehead (Journal of Biogeography, 2004)
Aim To explore rates of rain forest expansion and associated ecological correlates in Eucalyptus ‐dominated woodland savanna vegetation in north‐eastern Australia, over the period 1943–91. Location Iron Range National Park and environs, north‐east Queensland, Australia. This remote region supports probably the largest extent of lowland ( c. 1700 mm p.a.) occurs mostly between November and June, with some rain typically occurring even in the driest months July–October. Methods Interpretation of change in lowland rain forest vegetation cover was undertaken for a 140 km 2 area comprising complex vegetation, geology and physiography using available air photos (1943, 1970 and 1991). A GIS database was assembled comprising rain forest extent for the three time periods, geology, elevation, slope, aspect, proximity to streams and roads. Using standard GIS procedures, a sample of 6996 10 × 10 m cells (0.5% of study area) was selected randomly and attributed for vegetation structure (rain forest and non‐rain forest), and landscape features. Associations of rain forest expansion with landscape features were examined with logistic regression using the subset of cells that had changed from other vegetation types to rain forest, and remained rain forest over the assessment period, and comparing them with cells that showed no change from their original, non‐rain forest condition. Results Rain forest in the air photo study area increased from 45 km 2 in 1943 to 78.1 km 2 by 1970, and to 82.6 km 2 by 1991. Rainfall (and atmospheric CO 2 concentration) was markedly lower in the first assessment period (1943–70). Modelled rates of rain forest invasion differed predominantly with respect to substrate type, occurring faster on substrates possessing better moisture retention properties, and across all elevation classes. Greatest expansion, at least in the first assessment period, occurred on the most inherently infertile substrates. Expansion was little constrained by slope, aspect and proximity to streams and roads. On schist substrates, probability of invasion remained high (> 60%) over distances up to 1500 m from mature rain forest margins; on less favourable substrates (diorite, granites), probability of expansion was negligible at sites more than 400 m from mature margins. Main conclusions (i) Rain forest expansion was associated primarily with release from burning pressure from c . the 1920s, following major disruption of customary Aboriginal lifestyles including hunting and burning practices. (ii) Decadal‐scale expansion of rain forest at Iron Range supports extensive observations from the palaeoecological literature concerning rapid rain forest invasion under conducive environmental conditions. (iii) The generality of these substrate‐mediated observations requires further testing, especially given that landscape‐scale rain forest invasion of sclerophyll‐dominated communities is reported from other regions of north‐eastern Australia.

Rain forest invasion of eucalypt‐dominated woodland savanna, Iron Range, north‐eastern Australia: I. Successional processes - Jeremy Russell‐Smith; Peter J. Stanton; Peter J. Whitehead; Andrew Edwards (Journal of Biogeography, 2004)
Aim To explore successional processes associated with rain forest expansion in Eucalyptus ‐dominated woodland savanna vegetation in north‐eastern Australia. Location Iron Range National Park and environs, northeast Queensland, Australia. This remote region supports probably the largest extent of lowland ( c. 1700 mm p.a.) occurs mostly between November and June, with some rain typically occurring even in the driest months July–October. Methods (1) Sampling of rain forest seedling distributions, and other vegetation structural attributes, in fifteen 10 × 10 m quadrats distributed equi‐distantly between mature rain forest margins (range: 70–840 m), at each of 10 sites which were open‐canopied vegetation in 1943. (2) Assessment of relationships between rain forest seedling densities and structural characteristics, including distance‐to‐rain forest‐margin, canopy height, stem density. (3) Assessment of lifeform and dispersal spectra for defined vegetation structural types. Results Rates of rain forest invasion were found to be substrate‐mediated. Transects established on hematite schist, diorite, riverine alluvium, and granite developed closed canopies (termed phase III sites) by 1991. The remainder (four transects on poorly drained colluvial/alluvial sediments; one on dune sands) continued to occur either as grassy woodland (phase I), or with developing rain forest understoreys (phase II). Rain forest seedlings were observed at maximum sampled distances from mature rain forest margins at all sites. Lifeform and dispersal spectra data illustrated that: (1) the proportions of woodland trees, shrubs and graminoids declined with successional phase, with concomitant increases in rain forest primary trees and all other lifeform categories save rain forest trees; (2) the proportions of major dispersal syndromes did not vary between successional phases, neither for rain forest nor woodland taxa. Main conclusions Rain forest seedling distribution data for phases I and II sites illustrate three successional processes: margin extension – seedling density significantly negatively correlated with distance from mature rain forest margins at two sites; nucleation – seedling densities significantly positively correlated with tall trees at two sites; and irruption – seedling densities at two sites neither correlated with distance from mature rain forest margins, nor with measured vegetation structural features. The observation of irruptive rain forest regeneration at these sites, combined with decadal‐scale rain forest canopy development at the five remaining sites, illustrates that under conditions conducive to growth (moisture, substrate), low fire disturbance, and maintenance of diverse dispersal processes (high frugivore richness), rain forest can rapidly invade regional landscapes.

P-glycoprotein Expression, Localization, and Function in Sandwich-Cultured Primary Rat and Human Hepatocytes: Relevance to the Hepatobiliary Disposition of a Model Opioid Peptide - Keith A. Hoffmaster; Ryan Z. Turncliff; Edward L. LeCluyse; Richard B. Kim; Peter J. Meier; Kim L. R. Brouwer (Pharmaceutical Research, 2004)

QTL controlling partial resistance to Stagonospora nodorum leaf blotch in winter wheat cultivar Alba - Edward Arseniuk; Pawel C. Czembor; Andrzej Czaplicki; Qijian Song; Perry B. Cregan; David L. Hoffman; Peter P. Ueng (Euphytica, 2004)

Characterisation of early transcriptional changes involving multiple signalling pathways in the Mla13 barley interaction with powdery mildew ( Blumeria graminis f. sp. hordei ) - Ingo Hein; Edward I. Campbell; Mary Woodhead; Peter E. Hedley; Vanessa Young; Wayne L. Morris; Luke Ramsay; Joerg Stockhaus; Paul R. J. Birch; Gary D. Lyon; Adrian C. Newton (Planta, 2004)

Moth pollination of woody species in the Cerrados of Central Brazil: a case of so much owed to so few? - Paulo Eugnio Oliveira; Peter Edward Gibbs; Ana Anglica Barbosa (Plant Systematics and Evolution, 2004)

Parasitism of non-target lepidoptera by mass released Trichogramma brassicae and its implication for the larval parasitoid Lydella thompsoni - Stefan Kuske; Dirk Babendreier; Peter Edwards; Ted C.J. Turlings; Franz Bigler (BioControl, 2004)

Impact of soil warming and shading on colonization and community structure of arbuscular mycorrhizal fungi in roots of a native grassland community - Andreas Heinemeyer; Karyn P. Ridgway; Everard J. Edwards; David G. Benham; J. Peter W. Young; Alastair H. Fitter (Global Change Biology, 2004)
Arbuscular mycorrhizal (AM) fungi have a major influence on the structure, responses and below‐ground C allocation of plant communities. Our lack of understanding of the response of AM fungi to factors such as light and temperature is an obstacle to accurate prediction of the impact of global climate change on ecosystem functioning. In order to investigate this response, we divided a grassland site into 24 plots, each either unshaded or partly shaded with soil either unheated or heated by 3°C at 2 cm depth. In both short‐term studies in spring and autumn, and in a 1‐year‐long study, we measured root length colonization (L R C) by AM and non‐AM fungi. For selected root samples, DNA sequences were amplified by PCR with fungal‐specific primers for part of the small sub‐unit (SSU) rRNA gene. In spring, the total L R C increased over 6 weeks from 12% to 25%. Shading significantly reduced AM but increased non‐AM fungal colonization, while soil warming had no effect. In the year‐long study, colonization by AM fungi peaked in summer, whereas non‐AM colonization peaked in autumn, when there was an additive effect of shading and soil warming that reduced AM but increased non‐AM fungi. Stepwise regression revealed that light received within the 7 days prior to sampling was the most significant factor in determining AM L R C and that mean temperature was the most important influence on non‐AM L R C. Loglinear analysis confirmed that there were no seasonal or treatment effects on the host plant community. Ten AM fungal sequence types were identified that clustered into two families of the Glomales, Glomaceae and Gigasporaceae. Three other sequence types were of non‐AM fungi, all Ascomycotina. AM sequence types showed seasonal variation and shading impacts: loglinear regression analysis revealed changes in the AM fungal community with time, and a reduction of one Glomus sp. under shade, which corresponded to a decrease in the abundance of Trifolium repens. We suggest that further research investigating any impacts of climate change on ecosystem functioning must not only incorporate their natural AM fungal communities but should also focus on niche separation and community dynamics of AM fungi.

Strategies for the Control of Fusarium Head Blight in Cereals - Stoyan R. Pirgozliev; Simon G. Edwards; Martin C. Hare; Peter Jenkinson (European Journal of Plant Pathology, 2003)

The Tagliamento River: A model ecosystem of European importance - Klement Tockner; James V. Ward; David B. Arscott; Peter J. Edwards; Johannes Kollmann; Angela M. Gurnell; Geoffrey E. Petts; Bruno Maiolini (Aquatic Sciences, 2003)

Reduced hybrid cluster proteins (HCP) from Desulfovibrio desulfuricans ATCC 27774 and Desulfovibrio vulgaris (Hildenborough): X-ray structures at high resolution using synchrotron radiation - David Aragão; Sofia Macedo; Edward P. Mitchell; Célia V. Romão; Ming Y. Liu; Carlos Frazão; Lígia M. Saraiva; António V. Xavier; Jean LeGall; Walter M. A. M. van Dongen; Wilfred R. Hagen; Miguel Teixeira; et al. (JBIC Journal of Biological Inorganic Chemistry, 2003)

Examples of high-frequency EPR studies in bioinorganic chemistry - K. Kristoffer Andersson; Peter P. Schmidt; Bettina Katterle; Kari R. Strand; Amy E. Palmer; Sang-Kyu Lee; Edward I. Solomon; Astrid Gräslund; Anne-Laure Barra (JBIC Journal of Biological Inorganic Chemistry, 2003)

Monitoring the Penetration Enhancer Dimethyl Sulfoxide in Human Stratum Corneum in Vivo by Confocal Raman Spectroscopy - Peter J. Caspers; Adrian C. Williams; Elizabeth A. Carter; Howell G. M. Edwards; Brian W. Barry; Hajo A. Bruining; Gerwin J. Puppels (Pharmaceutical Research, 2002)

Reproduction of hatchery-reared and transplanted wild bay scallops, Argopecten irradians irradians, relative to natural populations - Stephen T. Tettelbach; Christopher F. Smith; Peter Wenczel; Edward Decort (Aquaculture International, 2002)

The stratigraphic evolution of the Indus Fan and the history of sedimentation in the Arabian Sea - Peter Clift; Christoph Gaedicke; Rosemary Edwards; Jae Il Lee; Peter Hildebrand; Shahid Amjad; Robert S. White; Hans-Ulrich Schlüter (Marine Geophysical Research, 2002)

Hybrid cluster proteins (HCPs) from Desulfovibrio desulfuricans ATCC 27774 and Desulfovibrio vulgaris (Hildenborough): X-ray structures at 1.25 Å resolution using synchrotron radiation - Sofia Macedo; Edward P. Mitchell; Célia V. Romão; Serena J. Cooper; Ricardo Coelho; Ming Y. Liu; António V. Xavier; Jean LeGall; Susan Bailey; David C. Garner; Wilfred R. Hagen; Miguel Teixeira; et al. (JBIC Journal of Biological Inorganic Chemistry, 2002)

Toward positional cloning of Vgt1, a QTL controlling the transition from the vegetative to the reproductive phase in maize - Silvio Salvi; Roberto Tuberosa; Elena Chiapparino; Marco Maccaferri; Stanislas Veillet; Leon van Beuningen; Peter Isaac; Keith Edwards; Ronald L. Phillips (Plant Molecular Biology, 2002)

Dipole Localization of Human Induced Focal Afterdischarge Seizure in Simultaneous Magnetoencephalography and Electrocorticography - William W. Sutherling; Massoud Akhtari; Adam N. Mamelak; John Mosher; Deborah Arthur; Steve Sands; Peter Weiss; Nancy Lopez; Mauricio DiMauro; Edward Flynn; Richard Leahy (Brain Topography, 2001)

Cumulative exposure to tamoxifen: DNA adducts and liver cancer in the rat - Philip Carthew; Peter Lee; Richard Edwards; Robert Heydon; Barbara Nolan; Elizabeth Martin (Archives of Toxicology, 2001)

Decaying Scalars Emitted By A Forest Canopy: A Numerical Study - Edward G. Patton; Kenneth J. Davis; Mary C. Barth; Peter P. Sullivan (Boundary-Layer Meteorology, 2001)

Tissue distribution and functional expression of the human voltage-gated sodium channel β3 subunit - Edward B. Stevens; Peter J. Cox; Bhaval S. Shah; Alistair K. Dixon; Peter J. Richardson; Robert D. Pinnock; Kevin Lee (Pflügers Archiv - European Journal of Physiology, 2001)

Changes in primary DNA sequence complexity influence the phenotypic consequences of mutations in human gene regulatory regions - Michael Krawczak; Nadia Chuzhanova; Peter Stenson; Bent Johansen; Edward Ball; David Cooper (Human Genetics, 2000)

Phylogeny of Marine Bacillus Isolates from the Gulf of Mexico - Janet L. Siefert; Maia Larios-Sanz; Lawrence K. Nakamura; Ralph A. Slepecky; John H. Paul; Edward R. B. Moore; George E. Fox; Peter Jurtshuk, Jr. (Current Microbiology, 2000)

Aminergic neuron systems of lobsters: morphology and electrophysiology of octopamine-containing neurosecretory cells - Ralf Heinrich; Peter Bräunig; Ismeni Walter; Henning Schneider; Edward A. Kravitz (Journal of Comparative Physiology A, 2000)

Genetic variability and gene flow in the globally, critically-endangered Taita thrush - Peter Galbusera; Luc Lens; Tine Schenck; Edward Waiyaki; Erik Matthysen (Conservation Genetics, 2000)

Surface pollen‐vegetation relationships on the Atlantic seaboard: South Uist, Scotland - Barbara A. Brayshay; David D. Gilbertson; Martin Kent*; Kevin J. Edwards; Peter Wathern; Ruth E. Weaver (Journal of Biogeography, 2000)
Studies of modern pollen rain from remote islands have raised a number of interesting issues concerning the spatial precision of present‐day pollen spectra in relation to their parent plant community types. This paper examines the relationships and degree of correlation between a sequence of contemporary vegetation types, environments and their associated surface pollen spectra from a transect across the island of South Uist in the Outer Hebrides of Scotland. Paired data on both contemporary vegetation and associated surface pollen assemblages have been collected and analysed using methods of numerical classification and ordination. In general terms, the modern pollen rain on South Uist reflects the major changes in vegetation pattern and the major community types fairly closely. The major boundary between the alkaline machair sand dune communities and the various acidic upland vegetation types is particularly clear. However, both variability in the vegetation and the effects of the strong prevailing westerly and south‐westerly winds tend to blur the boundaries of the various communities within each of these larger categories. On average 86.6% of the palynomorphs come from in‐community quadrat sources, while only 1.3% are from off‐island sources. The limited present‐day tree distribution on the transect is discussed in the context of the more widespread distribution of arboreal pollen. Overall, there is a strong numerical correspondence between vegetation, pollen and environmental variables. The various problems inherent in examining surface pollen spectra are reviewed.

Assessing Trace Element Uptake by Vegetation on a Coal Fly Ash Landfill - Peter B. Woodbury; Gail Rubin; D. C. McCune; Leonard H. Weinstein; Edward F. Neuhauser (Water, Air, & Soil Pollution, 1999)

Genotypic and phenotypic characterization of six new recombinant congenic strains derived from NOD/Shi and CBA/J genomes - Peter C. Reifsnyder; Jeffry C. Flynn; Amanda L. Gavin; Eric A. Simone; John J. Sharp; Lieselotte Herberg; Edward H. Leiter (Mammalian Genome, 1999)

Greigite (Fe3S4) as an indicator of drought – The 1912–1994 sediment magnetic record from White Rock Lake, Dallas, Texas, USA - Richard L. Reynolds; Joseph G. Rosenbaum; Peter van Metre; Michele Tuttle; Edward Callender; Alan Goldin (Journal of Paleolimnology, 1999)

Enhanced neointimal growth in cultured rabbit aorta following in vivo balloon angioplasty - William E. Dale; Peter S. Batra; Edward H. Blaine (In Vitro Cellular & Developmental Biology - Animal, 1998)

CO2 and O2 dependence of PS II activity in C4 plants having genetically produced deficiencies in the C3 or C4 cycle - João P. Maroco; Maurice S. B. Ku; Robert T. Furbank; Peter J. Lea; Richard C. Leegood; Gerald E. Edwards (Photosynthesis Research, 1998)

Partial Maintenance of Taurocholate Uptake by Adult Rat Hepatocytes Cultured in a Collagen Sandwich Configuration - Xingrong Liu; Kim L. R. Brouwer; Liang-Sheng L. Gan; Kenneth R. Brouwer; Bruno Stieger; Peter J. Meier; Kenneth L. Audus; Edward L. LeCluyse (Pharmaceutical Research, 1998)

Devensian organic interstadial deposits and ice sheet extent in Buchan, Scotland - Graeme Whittington; Rodger E. Connell; G. Russell Coope; Kevin J. Edwards; Adrian M. Hall; Peter D. Hulme; Jack Jarvis (Journal of Quaternary Science, 1998)

Devensian organic interstadial deposits and ice sheet extent in Buchan, Scotland - Graeme Whittington; Rodger E. Connell; G. Russell Coope; Kevin J. Edwards; Adrian M. Hall; Peter D. Hulme; Jack Jarvis (Journal of Quaternary Science, 1998)

Assignment of Gpam to distal mouse Chromosome 19 by linkage analysis - Carrie L. Welch; Yu-Rong Xia; Peter A. Edwards; Aidons J. Lusis; Johan Ericsson (Mammalian Genome, 1998)

Sources of inorganic carbon for marine microalgal photosynthesis: A reassessment of δ 13 C data from batch culture studies of Thalassiosira pseudonana and Emiliania huxleyi - Edward A. Laws; Peter A. Thompson; Brian N. Popp; Robert R. Bidigure (Limnology and Oceanography, 1998)
A reevaluation of previously published analyses of stable carbon isotope fractionation by batch cultures of Thalassiosira pseudonana and Emiliania huxleyi indicates that the Rayleigh distillation model was used to model δ 13 C uptake incorrectly. Correct use of the model shows that the relationship between the δ 13 C of the particulate organic carbon (δ p ) and the concentration of the dissolved inorganic carbon (DIC) at the time of harvest can be equally well described by a model assuming bicarbonate or CO 2 uptake. The lack of a correlation between growth rate and δ p in the T. pseudonana results suggests that growth rate and the intracellular CO 2 concentration are directly proportional. Theoretical considerations indicate that the T. pseudonana cultures started at a pH of 9.2 would have become CO 2 limited before harvest and that this species must have the ability to utilize bicarbonate when CO 2 becomes limiting. The similarity of the T. pseudonana δ p results from cultures started at pH 8.2 and 9.2 suggests that the form of DIC entering the cells was the same in both sets of experiments. The results are consistent with (1) uptake of bicarbonate or (2) uptake of CO 2 , with external carbonic anhydrasemediated conversion of bicarbonate to CO 2 supplementing the uncatalyzed supply of CO 2 when the latter becomes limiting. Analysis of the δ 13 C of both particulate organic carbon and coccolith carbon in the case of E. huxleyi suggests that the cells were taking up primarily bicarbonate at low growth rates, but that at high growth rates the DIC used for photosynthesis was derived almost entirely from uptake of CO 2 . The DIC utilized for coccolith formation seems to have been substantially diluted by isotopically light DIC derived from respiration at high growth rates.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Dating prehistoric bog‐fires in northern England to calendar years by long‐distance cross‐matching of pine chronologies - Frank M. Chambers; Jonathan G. A. Lageard; Gretel Boswijk; Peter A. Thomas; Kevin J. Edwards; Jennifer Hillam (Journal of Quaternary Science, 1997)

Dating prehistoric bog-fires in northern England to calendar years by long-distance cross-matching of pine chronologies - Frank M. Chambers; Jonathan G. A. Lageard; Gretel Boswijk; Peter A. Thomas; Kevin J. Edwards; Jennifer Hillam (Journal of Quaternary Science, 1997)

Water-quality trends in White Rock Creek Basin from 1912-1994 identified using sediment cores from White Rock Lake reservoir, Dallas, Texas - Peter C. Van Metre; Edward Callender (Journal of Paleolimnology, 1997)

The role of glutathione in L -2-chloropropionic acid induced cerebellar granule cell necrosis in the rat - I. Wyatt; Andrew Gyte; Michael G. Simpson; Peter S. Widdowson; Edward A. Lock (Archives of Toxicology, 1996)

Mass spectrometric dating of flowstones from Stump Cross Caverns and Lancaster Hole, Yorkshire: palaeoclimate implications - ANDY BAKER; PETER L. SMART; R. LAWRENCE EDWARDS (Journal of Quaternary Science, 1996)

Mass spectrometric dating of flowstones from Stump Cross Caverns and Lancaster Hole, Yorkshire: palaeoclimate implications - ANDY BAKER; PETER L. SMART; R. LAWRENCE EDWARDS (Journal of Quaternary Science, 1996)

Chloropropionic acid-induced alterations in glucose metabolic status: possible relevance to cerebellar granule cell necrosis - Edward A. Lock; Andrew Gyte; Peter Widdowson; Michael Simpson; Ian Wyatt (Archives of Toxicology, 1995)

Cloning of erect, thornless, non-browsed nitrogen fixing trees of Haiti's principal fuelwood species (Prosopis juliflora) - Timothy wojtusik; Peter Felker; Edward J. Russell; Michael D. Benge (Agroforestry Systems, 1993)

Lead exposure from conventional and cottage lead smelting in Jamaica - Thomas D. Matte; J. Peter Figueroa; Stephanie Ostrowski; Gregory Burr; Linnette Jackson-Hunt; Edward L. Baker (Archives of Environmental Contamination and Toxicology, 1991)

Estimation of endothelial receptor sites with the mean transit time approach - Richard M. Effros; Peter Dodek; Jack Edwards (Annals of Biomedical Engineering, 1987)

A determination and estimation of trend in Maine’s fresh potato shipments - Alan S. Kezis; Edward F. Johnston; Peter Baldwin (American Journal of Potato Research, 1980)

A noninvasive tissue reflectance oximeter - Setsuo Takatani; Peter W. Cheung; Edward A. Ernst (Annals of Biomedical Engineering, 1980)

RNA virus-like particles in the chytridiomycete Allomyces arbuscula - Edward W. Khandjian; Urs-Peter Roos; William E. Timberlake; Lorenza Eder; Gilbert Turian (Archives of Microbiology, 1974)